Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

Gelatin-sodium alginate-polyphenol emulsion filled hydrogel beads: preparation, characterization and encapsulation ability of Lactobacillus plantarum - Wanting Zhang; Jinjing Chen; Xiwen Zheng; Chenrui Fu; Xiuli Wu; Chang Liu (Food Hydrocolloids, 2026)

Laser pyrolysis of poly(methyl methacrylate) to high-yield and high-purity methyl methacrylate monomer: A solvent- and catalyst-free strategy for chemical recycling - Xu-Zhen Zhu; Guang-Jian He; Meng-Meng Wang; Fu-Lu Chang; Zi-Yang Hua; Hao-Bo Wang; Xuan-Qi Wu; Lun Chen (Chemical Engineering Journal, 2026)

A dual-channel hydrogel sensor for body temperature and exercise monitoring with simultaneous strain-temperature discrimination - Tiantian Wang; Jiayi Fu; Chengrui Jiang; Xun Wang; Panpan Shen; Fan Wang; Dehua Li; Ruoxin Li; Yi Hu; Guangtao Chang (Chemical Engineering Journal, 2026)

Interface chemical bonding triggered rapid charge transfer for efficient photocatalytic H2 evolution on indium proximal to sulfur vacancy - Hui Chang; Cheng Luo; Pengrong Gu; Xiaojun Zheng; Wenjuan Fan; Hao Fu; Yufeng Li; Hu Li; Zhiqiang Jiang (Chemical Engineering Journal, 2026)

Efficient one-pot lactic acid production from cellulose via a Trichoderma reesei and Bacillus coagulans cooperation leveraging substrate-induced secretomes - Shuai Liang; Chang Yu; Jiaming Fu; Yuanming Tao; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

Flash Joule heating as a novel thermal treatment for heavy metal detoxification from municipal solid waste incineration fly ash - Zili Yang; Qiongyu Yang; Yanzhen Fu; Yangchao Xia; Yuhao Chang; Shiqi Dai; Haoqiang Cheng; Xiahui Gui (Journal of Environmental Chemical Engineering, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Spatial dominance over temporal dynamics in urban soil bacterial communities and its implications for forensic geolocation - Qing Zhang; Chang Zhao; Xiao Fu; Jiasheng Wu; Hengjun Zhang; Haiyan Chu; Meiqing Yuan; Teng Yang (Soil Ecology Letters, 2026)

Microscopic deformation mechanism of clay aggregates in view of the montmorillonite particles rearrangements under cyclic loading-unloading conditions - Zi-Yu Ding; Kai-Wen Tong; Yong-Gui Chen; Qiong Wang; Wen-Jie Dai; Xing-Guang Zhao; Chang-Fu Wei; Zhi-Jun Zhang (Applied Clay Science, 2026)

Numerical investigation on hydrodynamic interference in parallel water entry of vehicles with deflection angles - Xiao-Qiang Chen; Jia-Jie Wang; Chang Liu; Meng-Chao Zhang; Fu-Ren Ming (Ocean Engineering, 2026)

Nitrogen dioxide exposure promotes CD8+T cell infiltration and contributes to increased susceptibility to ulcerative colitis: An integrative multi‑omics, artificial intelligence, and mouse model study - Zhijie Wang; Xin Chang; Tian Fu; Dan Xu; Yuanhong Ma; Hao Zhang; Hubin Xia; Xiaofeng Zhang; Yingdong Hou (Journal of Hazardous Materials, 2026)

Averageness is not enough: Different perceptual codes for body attractiveness versus typicality - Zihan Zhu; Xiaolan Fu; Lan Chen; Chang Hong Liu; Connor J. Parde; Ying Hu (Evolution and Human Behavior, 2026)

Cosolvent-driven exciton delocalization and dual dissociation pathways enable high-efficiency inverted all-polymer solar cells - Jia-Fu Chang; Hui Chan Ahn; Sunil V. Barma; Cheng-Yu Yeh; Yu-Cheng Tseng; Hyun Min Kwon; Hyerin Jeon; Hsu-Tzu Cheng; Bumjoon J. Kim; Sae Byeok Jo; Chu-Chen Chueh (Chemical Engineering Journal, 2026)

Nanozyme-enabled antibacterial sponge hydrogel-based electronic skin for underwater tactile sensing and slip-direction recognition - Jinli Fu; Lingling Zhang; Jiahao Yuan; Zhenyu Li; Chang Yang; Chunhua Luo; Hechun Lin; Xiaodong Tang; Hui Peng (Chemical Engineering Journal, 2026)

Cholesterol-directed MnO2 nanoplatform coated with metal-phenolic network for O2-elevated sonodynamic and chemodynamic elimination of bacterial infections - Yutong Huang; Qian Wang; Zhongjia Liu; Mengyu Fu; Wei He; Changchun Tu; Zhongtao Wu; Bingcheng Chang; Yun Liu (Chemical Engineering Journal, 2026)

Interdigitated electric-magnetic gradient MXene-based nanocomposite films for concurrent high-efficiency electromagnetic shielding and sensitive detection - Lingfeng Yu; Yanni Yang; Shulong Chang; Yihao Xiao; Song Luo; Shichun Hao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Temperature-responsive carbon dots-spiropyran photochromic films for stepwise-decryption optical anti-counterfeiting with information self-destruction - Meichen Meng; Zhimeng Ma; Mingbo Yue; Chang Liu; Xiaoyu Xu; Qiang Fu (Chemical Engineering Journal, 2026)

Heavy sulfur isotope of arc ultramafic cumulates revealed by S-rich apatite from the Dongwanzi intrusion, North China - Huan Jennifer Chang; Mei-Fu Zhou; Wen-Jun Hu; Shengbiao Yang; Jian-Feng Gao (Chemical Geology, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Outcome-specific park-catchment assessment of age-supportive neighborhood parks using field audits and street-view imagery - Li-Chih Ho; Yu-Sheng Shen; Sin-Rou Fu; Po-Ju Chang (Landscape and Ecological Engineering, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Corrigendum to ‘The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China’ [Palaeoworld 34 (2025) 200995] - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2026)

Simulation and parameter optimization of the temperature field in mild moxibustion using physics-informed neural networks - Honghua Liu; Zhenhua Fu; Jiayi Liao; Jiamin Hu; Mailan Liu; Chang She (Journal of Thermal Biology, 2026)

Corrigendum to “Construction of a multiplex biosensor for the on-site rapid detection of phthalates in biological fluids based on single-stranded DNA aptamers” [J Hazard Mater 499 (2025) 140164] - Kun Fu; Jia Zheng; Yichao Zhang; Chang Liu; Wenxiang Zhang; Siyu Chen (Journal of Hazardous Materials, 2026)

Microplastics impair cadmium adsorption in soils via changes in dissolved organic matter and Fe/Mn oxides - Zhenbo Wang; Peng Zhao; Shuanglong Ma; Linglu Wang; Xiaoyu Li; Mengchan Xie; Wenfeng Guo; Fuqing Sui; Chang Li; Shiyu Qin; Hongen Liu; Haichao Fu (Journal of Hazardous Materials, 2026)

A ceRNA axis of lncRNA MSTRG.14394.1/miR-144-3p/NR1H3 responds to diverse bacterial PAMPs in teleost fish - Yishuai Li; Mengyang Chang; Suxu Tan; Wenwen Wang; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Qingyang Fu; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Interactive effect between different growth duration variety and cutting height on grain yield and quality in ratoon rice - Jinjuan Zhu; Qimeng Lan; Xinchen Zhang; Hongshun Xiang; Yifan Fu; Huiping Wang; Changzai Zhou; Chen Yang; Guodong Yang; Xing Yu; Chang Zheng; Shen Yuan; et al. (Field Crops Research, 2026)

Core-shell biochar-zeolite fertilizer with starch coating: Boosting nutrient use in saline-alkaline rice soils via smart drone delivery & economic assessment - Chang Dong; Aosheng Bai; Xu Zhao; Yang Cheng; Qinglong Chen; Phoutthasone Sibounavong; Xin-Fu Ye; Yongfu Li; Yanjiang Cai; Jie Zhu; Ruohui Lu; Bing Yu (Environmental Research, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

The role of fractional crystallization in the formation of unzoned Li-mineralized pegmatites: insights from in situ apatite geochemistry - Shuaijie Liu; Mei-Fu Zhou; Huan Chang; Bin Chen; Hui Zhao (Contributions to Mineralogy and Petrology, 2026)

IRF1-mediated sensing of oxidized mitochondrial DNA drives macrophage PANoptosis in lung ischemia–reperfusion injury - Nan Zhang; Zhiyuan Zhang; Jing Yu; Yu Fu; Jiameng Gao; Xuemei Jiang; Yang Jin; Chang Chen; Zongmei Wen (Apoptosis, 2026)
Lung ischemia–reperfusion injury (IRI), a significant factor contributing to early mortality following lung transplantation (LTx), is driven by molecular mechanisms that are not yet fully understood. In this study, we elucidate a crucial signaling pathway initiated by extracellular histones (ex-His), which connects mitochondrial damage to inflammatory cell death. Through the use of a murine model of lung IRI and in vitro experiments with alveolar macrophages, we demonstrate that ex-His facilitate Drp1-dependent mitochondrial fission, resulting in the release of oxidized mitochondrial DNA (ox-mtDNA) into the cytosol. Our mechanistic analysis reveals that cytosolic ox-mtDNA is detected by the transcription factor IRF1, which subsequently upregulates NLRC5 at the transcriptional level. Additionally, we identify NLRC5 as a non-canonical scaffold that is essential for the assembly of the PANoptosome, a multi-protein complex that mediates PANoptosis, an inflammatory cell death pathway that aggravates tissue damage. The clinical relevance of this pathway was then examined in lung transplant recipients. An analysis of their peripheral blood mononuclear cells (PBMCs) revealed that patients who developed primary graft dysfunction (PGD) exhibited markedly elevated levels of circulating histones and cytosolic ox-mtDNA. This was associated with hyperactivation of the core signaling axis, characterized by increased Drp1 phosphorylation and elevated expression of IRF1 and NLRC5. Collectively, our study elucidates a comprehensive pathogenic cascade from an extracellular danger signal to a specific cell death program, identifying the ex-His-mitochondria-IRF1-NLRC5 axis as a critical driver of macrophage PANoptosis and a promising therapeutic target for alleviating lung IRI.

Synergistic Interactions Between Warming and Elevated Atmospheric CO 2 Increase Soil Organic Carbon Sequestration - Ruiqi Yao; Yike Zhang; Wolfgang Wanek; Zhongkui Luo; Haoran Fu; Scott X. Chang; Cesar Terrer; Mingkai Jiang; Tida Ge; Guopeng Liang; Yuanhe Yang; Yiqi Luo; et al. (Global Change Biology, 2026)
Warming and elevated CO 2 (eCO 2 ) are two potentially opposing climate‐carbon (C) feedback mechanisms that modulate the magnitude of the land C sink, with warming decreasing and eCO 2 increasing C sequestration. However, their net effect on soil organic C (SOC)—the largest terrestrial C stock—remains uncertain. Here, we quantify how warming, eCO 2 , and their interactions influence SOC by using 5558 paired observations from 1392 global studies across ecosystem types. Our study shows that warming reduces SOC by 8.0%, primarily by suppressing aboveground C inputs (−1.0%) and decreasing microbial C use efficiency (−9.9%). Concurrent warming and eCO 2 increase SOC by 7.6%—a synergistic effect larger than eCO 2 alone (+4.8%), primarily contributed by croplands. This outcome may result from increases in plant C inputs and soil nitrogen availability under eCO 2 , which facilitate microbial C assimilation and necromass formation (+3.9%). These processes promote the accumulation of mineral‐associated C (+9.9%) and offset the negative effects of warming. The combined effect of warming and eCO 2 is projected to increase SOC by 27.4 Pg C by 2100. Our findings highlight that synergistic interaction between warming and eCO 2 increases SOC sequestration and enhances SOC stability under future climate change.

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Biodegradable nanoplastics pose a greater risk: Polylactic acid exceeds polystyrene in phytotoxicity and bioaccumulation in lettuce - Xiaoyu Li; Chang Li; Peng Zhao; Fuqing Sui; Hongen Liu; Shiyu Qin; Zhenbo Wang; Mengchan Xie; Wenfeng Guo; Haichao Fu (Journal of Hazardous Materials, 2026)

Driving mechanisms of adaptive strategies and heavy metal remediation potential in Artemisia lavandulaefolia during succession of abandoned Pb–Zn mining areas - Sichen Wang; Tianyi Pu; Xinqi Yuan; Chenyang Zhang; Shuaijie Sun; Dapeng Zong; Chang'e Liu; Changqun Duan; Liqiang Chen; Denggao Fu (Journal of Environmental Management, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

pH/ROS dual-responsive release of oleanolic acid from amino acid–modified HG-type pectin hydrogel via dynamic crosslinking - Lingtao Kang; Shuangshuang Ma; Zhipeng Su; Huan Li; Junren Wen; Weidan Guo; Xia Chang; Fan Huang; Zengenni Liang; Xiaopeng Li; Fuhua Fu; Gaoyang Li (Food Hydrocolloids, 2026)

Variations in semi- and non-volatile organic substances during physical recycling and their migration from rPET bottles - Yi-Qi Liu; Yan Zeng; Shao-Fu Zeng; Zhi-Wei Wang; Lei Zhu; Li-Li Jin; Gui-Qin Shang; Gui-Hua Liu; Chang-Ying Hu (Food Packaging and Shelf Life, 2026)

Heavy rainfall shifts microbial control from nutrient–temperature to precipitation dependence in subtropical coastal waters - Chien-Fu Chao; Madeline Olivia; Clara Natalie Annabel; Patrichka Wei-Yi Chen; Chih-hao Hsieh; Tzong-Yueh Chen; Feng-Hsun Chang; Pei-Chi Ho; Yi-Chun Yeh; Chia-Te Chien; Fuh-Kwo Shiah; Vladimir Mukhanov; et al. (Estuarine, Coastal and Shelf Science, 2026)

Alginate-based composite hydrogel derived from Azotobacter vinelandii Av1: Preparation, properties, and wound-healing efficacy - Peng Yang; Rongqiang Chen; Siyuan Peng; Lin Zhu; Yifei Chang; Zhi Bao; Xiaodan Fu; Mengshi Xiao; Min Yang; Haijin Mou (Carbohydrate Polymers, 2026)

Generating Microglia-Integrated Cortical Organoids from Human Embryonic Stem Cells - Hongxin Quan; Xianglin Liu; Min Yan; Zongyong Ai; Baohua Niu; Jing Jiang; Hong Chang; Wenxiang Fu; Runrui Zhang (Stem Cell Reviews and Reports, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The Earth’s mantle fuels our future by hosting and emanating natural hydrogen - Tong Liu; Yong-Qiang Hu; Chuan-Zhou Liu; Chang Zhang; Chenhui Fei; Fu-Yuan Wu (Science Bulletin, 2026)

Leverage-based nutrient governance for drinking water sources using hydro-ecological zoning and source apportionment in the Yangtze River Basin - Haizhen Hu; Qing Fu; Sheng Chang; Yinying Zhu; Asaad Y. Shamseldin; Fan Zhang; Guang Yang; Chun Ye; Yueting Fan; Enrui Wang (Journal of Environmental Chemical Engineering, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

The Lhasa Terrane: A tale of two origins and its convergence at the Northern Margin of Gondwana - Chang-Sheng Yu; Mei-Fu Zhou; Ming Wang; Jian-Bo Zhou; Wen-Jun Hu (Earth-Science Reviews, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Self-sustaining singlet oxygen Fenton-like catalysis for scalable water remediation - Fu-Qiao Yang; Chang-Wei Bai; Jing Wang; Xin-Jia Chen; Pi-Jun Duan; Zhi-Quan Zhang; Ying Shao; Meng Zhang; Fei Chen (Chemical Engineering Journal, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Neurovascular decoupling is associated with altered glymphatic function as assessed by the DTI-ALPS index in patients on dialysis - Wenbo Yang; Lijun Song; Mingan Li; Xiaoyan Bai; Boyan Xu; Min Li; Zhenghan Yang; Tiantian Ma; Yong Gong; Gang Fu; Wenjing Zhao; Jing Zhao; et al. (Brain Imaging and Behavior, 2026)

Metagenomic analysis of urban water systems uncovers the interplay between antibiotic resistance genes and microbial communities in response to PFAS contamination - Kunfeng Zhang; Sheng Chang; Yinying Zhu; Hongru Shang; Qing Fu; Xiang Tu; Yanling Yu; Yujie Feng (Journal of Hazardous Materials, 2026)

Lactoferrin-derived hydrophobic peptide YIYT alleviates osteoporosis via synergistic activation of Wnt/β-catenin and BMP/Smad pathways - Zhihui Chang; Da Hong; Xiaoyu Ma; Baifeng Fu; Shuzhen Cheng; Ming Du (Food Bioscience, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Sulfobetaine-modified palladium nanozyme for alleviating ulcerative colitis via RONS scavenging and microbiome remodeling - Chaoyue Sun; Min Feng; Ting Yang; Hongjia Song; Jinbin Wang; Chang Peng; Haiyan Zhang; Xiangli Zhong; Zhao Fu (Chemical Engineering Journal, 2026)

NiFeS4/Ni3S4/NiS multiphase sulfides integrated with carbon nanotubes for efficient and high-performance electrode in cobalt-free rechargeable zinc–air batteries: A demonstration of rare compounds by an interrupted chemical reaction - Noto Susanto Gultom; Ji-En Liu; Celca Rahmatunnisa; Yen-Fu Chen; En-chi Chang; Dong-Hau Kuo (Chemical Engineering Journal, 2026)

No clear preferences for the lineal sex: A comparative study on the differences in progression of parity - Baisensen Zhang; Haiying Zhang; Yating Liu; Chang Fu; Qiao-Qiao He (Behavioral Ecology and Sociobiology, 2026)

Construction of engineered Streptomyces albulus by increasing ATP and NADH supply and efficient production of ε-poly-L-lysine from sweet potato powder - Boyan Li; Xiaofeng Yuan; Shijie Zhu; Di Zhang; Chang Xu; Cuiying Hu; Xin Ju; Taoyun Wang; Liangzhi Li; Jiaolong Fu (World Journal of Microbiology and Biotechnology, 2026)

Multi-stage pretreatment coupled with microwave-assisted formic acid hydrolysis for green preparation of xylose residue-based cellulose nanofibers - Haolong Zhang; Wenjing Bu; Ruimin Guo; Sai Zhang; Kai Fu; Zhining Li; Guizhuan Xu; Xiaoyang Zheng; Wei Chen; Chun Chang (Sustainable Chemistry and Pharmacy, 2026)

Numerical investigations of flow fields around polyethylene terephthalate (PET) nets using Improved Delayed Detached Eddy Simulation - Gang Wang; Zhi Wang; Chang-tao Guan; Zhao-qi Jiao; Jia-jun Hu; Lian-hui Wu; Xiao-yu Qu; Fu-kun Gui; De-jun Feng (Ocean Engineering, 2026)

Knowledge-embedded deep reinforcement learning for real-time dispatch of wind-solar-hydro hybrid generation systems - Yuanyu Ge; Jun Xie; Shuo Feng; Jiaqi Chang; Denghui Fu (Journal of Cleaner Production, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Development of a high-sensitivity dopamine sensor using copper tungstate nanoparticle-decorated carbon nanofibers on a glassy carbon electrode for analysis in various biological samples - Kiruthika Mariappan; Jing-Han Teng; Fu-Yi Chang; Shen Ming Chen; Jenn Fang Su; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2026)

Enhancing water quality and ecological sustainability through intelligent sustainable landscape fountains - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Chien-Hsun Chang; Chieh-Hsi Chen; Chien-Che Huang (Ecohydrology & Hydrobiology, 2026)

A novel gallic acid modification and high-temperature alkali activation mesoporous biochar enables ultrafast and high-capacity removal of short- and long-chain PFAS from water - Kunfeng Zhang; Sheng Chang; Yanling Yu; Hongru Shang; Xiang Tu; Qing Fu; Abdul Qadeer; Yujie Feng (Chemical Engineering Journal, 2026)

Three-dimensional network binder achieves strong adhesion and rapid lithium-ion transport for practical Si/C composite electrode - Bowen Chang; Yuan Xiao; Tianmin Wang; Mengjia Wang; Mingui Li; Fu-Ming Wang; Qunjie Xu; Qiaoxia Li (Chemical Engineering Journal, 2026)

A structural-preserving and scalable EBI strategy for functional cellulose copolymer films - Zhining Li; Liqin Yu; Shiqiang Zhao; Zhen Ma; Kai Fu; Haoyu Li; Haolong Zhang; Xiao Li; Yi Fan; Chun Chang (Chemical Engineering Journal, 2026)

Multi-omics dissection of procyanidin C1-driven microbiota-linked EPA-enriched phosphatidylcholine signaling in multi-tissue insulin resistance - Zhihao Liu; Qihao Li; Fu Zhao; Dapeng Zhang; Xinyue Li; Daozheng Fang; Haimeng Li; Qixiang Shang; Fengyan Chen; Zhiyuan Zhen; Yong Zhu; Chang-An Geng; et al. (Chemical Engineering Journal, 2026)

Synergistic binary acidity in metal sulfates drives efficient alcoholysis of high-solid xylose residues: An experimental and DFT investigation - Chun Chang; Xin Liu; Shuo Zang; Kai Fu; Zhen Ma; Xiaoyang Zheng; Huijuan Tian; Zhining Li (Biomass and Bioenergy, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Grazing exclusion reduces soil wind erosion in desert steppe through improving properties of vegetation and soil - Wenbang Gao; Yousheng Wang; Geng Zhang; Jianxin Fu; Lixing Zhang; Yaowen Chang (Soil and Tillage Research, 2026)

Toward a standardized and comparable life cycle dataset system for steel production in China - Huanyu Wang; Qiang Yue; Huimin Chang; Xiang Fu; Wei Ji; Changqing Xu; Heming Wang (Resources, Conservation and Recycling, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Comparative study on the ecotoxicity of nanoformulated and conventional emamectin benzoate to Raphidocelis subcapitata: A mechanistic disparity analysis - Jin Yang; Yiming Chang; Ruiqiang Fu; ManLi Yu; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Yanning Zhang; Xingang Liu (Environmental Pollution, 2026)

A coupled 3D DDA-MPM framework for soil-structure interaction modeling and its application in geotechnical hazards modeling - Hongyun Fan; Yuguang Fu; Wei Shen; Xiangyu Chang (Engineering Geology, 2026)

Geology and genesis of the Paodaoling intermediate-sulfidation epithermal gold deposit in the Chizhou district, Eastern China - Ke Huang; Guiqing Xie; Zhaoshan Chang; Liuan Duan; Shiqiang Huang; Bin Fu (Mineralium Deposita, 2026)

Subduction-accretion of sub-ridge mantle in the south Tibetan mélange zone - Zhen Zhang; Tong Liu; Chuan-Zhou Liu; Chang Zhang; Riccardo Tribuzio; Dong-Fang Song; Fu-Yuan Wu (Contributions to Mineralogy and Petrology, 2026)

Growth environment of the Pacific oyster (Crassostrea gigas) reefs recorded by shells and sediment since mid-Holocene on the coastal plain of the Western Bohai Sea, China - Yi-ming Huo; Yue Zhao; Chang-fu Fan; Yan-he Li; Bin Hu; Zhi-wen Shang; Fu Wang; Hong Wang (Geo-Marine Letters, 2026)

Neutral wind effects on nighttime mid-latitude electron density enhancement observed by FORMOSAT-3/COSMIC during the super quiet solar activity period of 2008–2010 - Fu-Yuan Chang; Jheng-Syun Chao; Jann-Yenq Liu (Advances in Space Research, 2026)

Short-term cold stress effects on antioxidant, metabolic, and immune responses in the red and white muscles of juvenile yellowfin tuna (Thunnus albacares) - Xuancheng Liu; Junhua Huang; Zhengyi Fu; Jie Chang; Zhenhua Ma (Frontiers in Marine Science, 2026)
This study aimed to examine the physiological responses of juvenile yellowfin tuna ( Thunnus albacares ) to short-term cold stress by comparing oxidative stress, metabolic regulation, and immune-related transcriptional responses in red and white muscles under two low-temperature conditions (24 °C and 18 °C) and a control temperature (30 °C). Juvenile tuna were exposed to these temperature conditions for 36 h, and muscle samples were collected at multiple time points to assess enzyme activities, biochemical indicators, and gene expression. Antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px), exhibited a biphasic response, characterized by an initial upregulation at 18 °C after 12 h followed by a decline under prolonged cold exposure. Elevated malondialdehyde (MDA) levels in the red muscle at 24 h indicated enhanced lipid peroxidation and oxidative stress. At 36 h, increased activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and acid phosphatase (ACP) in the red muscle reflected altered metabolic status and enhanced involvement of amino acid-related processes, whereas reduced lactate dehydrogenase (LDH) activity suggested suppression of anaerobic metabolic capacity under prolonged cold stress. Gene expression analysis revealed tissue-specific responses: the red muscle showed a pronounced and sustained induction of hspa1b and acadm , while the white muscle exhibited a faster but less persistent transcriptional response. In addition, the immune-related gene irf3 was downregulated in the red muscle but transiently upregulated in the white muscle. Overall, red muscle displayed slower yet more sustained regulation, whereas white muscle responded more rapidly but exhibited greater sensitivity to cold-induced biochemical perturbations. These findings highlight time- and tissue-specific mechanisms underlying tuna muscle responses to cold stress and provide insights relevant to adaptive management strategies for pelagic fish under climate change scenarios.

Complex variable solution for multi-step shallow tunnel excavation considering gravitational effects - Luo-bin Lin; Fu-quan Chen; Chang-jie Zheng; Shang-shun Lin (Tunnelling and Underground Space Technology, 2026)

Crustal structure and tectonic implications of the Southern Central Asian Orogenic Belt: New insights from gravity, magnetic, and magnetotelluric imaging - Chutong Chen; Na Li; Lingxiao Zhang; Hongying An; Chang’an Guo; Xing Fu; Songda Lei; Guicai Yang; Junjie Fan; Weiheng Yuan; Hao Wang; Bin Wang; et al. (Tectonophysics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Earthworm pretreatment enhances anaerobic biogas production through time-dependent structural modification of coal - Yunxia Niu; Daping Xia; Xiao Zhou; Bin Xu; Huizhen Chang; Kuo Jian; Rui Luo; Zhijia Yu; Haijiao Fu (Journal of Environmental Chemical Engineering, 2026)

Selective hydrogenolysis of lignin for sustainable production of 4-propylsyringol over N-doped Ceiba speciosa flower carbon supported Pd catalyst - Shipeng Gu; Wenjun Lei; Yanhuan Ke; Yan Fu; Jie Chang (Journal of Environmental Chemical Engineering, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Systematic monitoring model for zonal deformation of ultra-high arch dams driven by second-order idiosyncratic graph structures - Enhua Cao; Jianfeng Xue; Yangjia Li; Haotian Chang; Zhaoqing Fu; Cong Hu; Rongyao Yuan; Yangtao Li; Shaopei Hu; Tengfei Bao (Engineering Structures, 2026)

Study on the thermal insulation efficiency and ecological conservation effects of intelligent sustainable green walls - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; You-En Zhong; Zhi-Jia Feng (Energy and Buildings, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

Risk factors for Poor Response to Itraconazole in Onychomycosis Patients: A Prospective, Observational Study in China - Chang Miao; Yubo Ma; Xingyu Li; Tianshuo Zhao; Haijun Miao; Dong Yan; Luming Hai; Gang Wang; Yanyang Guo; Meng Fu (Mycopathologia, 2026)

Impact of media green attention on firm green transformation: evidence from firm-level financial news in China - Kai Chang; Haoxuan Fu; Mengfei Yang; Xinyi Cai (Environment, Development and Sustainability, 2026)

Comparison of cancer risks associated with JAK inhibitors and TNF inhibitors treatment in patients with rheumatoid arthritis: a systematic review and meta-analysis of real-world cohort studies - Fu-Yu Yang; Yu-Chang Liu; Min-You Wu; Yao-Cheng Wu; Cheng-Hsien Hung (Inflammation Research, 2026)

Decoding the gut-microbiota-muscle nexus: Multi-omics integration reveals mTOR driven flesh modulation in rice-fish co-cultured common carp (Cyprinus carpio) - Yinglin He; Bing Fu; Chang Fang; Niannian Zhang; Mengping Zheng; Yuting Yang; Shuping Zhang; Shijun Chen; Huirong Yang (Aquaculture, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Enhanced flotation upgrading of high-ash fine waste coal with a novel compound collector: High-value and clean utilization of waste - Zili Yang; Yuhao Chang; Yanzhen Fu; Qieyuan Gao; Guoxiao Wang; Yangchao Xia; Yaowen Xing; Xiahui Gui (Journal of Cleaner Production, 2026)

The construction of marine protected areas in China—Legal Dilemma, challenges and suggestions - Yen-Chiang Chang; Ben-chao Fu; Chingyu Huang; Jinhua Guo (Journal for Nature Conservation, 2026)

Promoting effects of gaseous CO2 and supercritical CO2 on the degradation of plastics: A review - Yanbing Liu; Jinwen Shi; Xinyu Jin; Wending Hou; Tomoyuki Kurioka; Tso-Fu Mark Chang; Masato Sone; Liejin Guo (Chemical Engineering Journal, 2026)

Unique roles of conductive/redox additives on humification in electric field-assisted composting - Tao Fu; Yueqiang Wang; Changya Chen; Chang Shen; Huayuan Shangguan; Xiaoming Liu; Zhen Yu (Bioresource Technology, 2026)

Effect of CPAP treatment on subjective cognitive decline in patients with mild obstructive sleep apnea syndrome - Liang Tan; Xin Zhang; Zhijian Fu; Chunyao Dong; Chang Zhou; Caiyun Hou; Yuanyuan Lin; Xiaolei Wang; Li Li; Jin Zhou (Sleep and Biological Rhythms, 2026)
There is no consensus on whether to use continuous positive airway pressure (CPAP) treatment for mild obstructive sleep apnea syndrome (OSAS). Our study aims to observe the efficacy and necessity of using CPAP treatment in mild OSAS patients complicated with subjective cognitive decline (SCD). From August 2021 to July 2022, patients with mild OSAS and SCD were randomized to the control group or the CPAP group, and followed up for 3 months. The primary results were evaluated using subjective cognitive decline questionnaire (SCD-Q), the Huashan version of the Auditory Verbal Learning Test (AVLT-H), and animal fluency test (AFT), which were tested at admission and three months after treatment, respectively. And plasma Aβ1–40 and Aβ1–42 levels were also measured at admission and 3 months after treatment. A total of 110 patients completed the final study, with 55 in the control group and 55 in the CPAP group. No significant differences in demographic data, Laboratory tests, AHI index, SCD-Q, AVLT-H, and AFT scores between the two groups before treatment. The SCD-Q score of patients in CPAP group significantly decreased after 3 months of treatment and was significantly lower than that of control group ( P <0.05). And the immediate memory score of AVLT-H in the treatment group was significantly increased after 3 months of treatment ( P < 0.05). The Aβ1–42/Aβ1–40 ratio in the treatment group significantly decreased after 3 months of treatment, and was significantly lower than that of control group ( P <0.05). Furthermore, there was linear correlation between SCD-Q score and Aβ1–42/Aβ1–40 ratio in all patients after 3 months of treatment ( P <0.001, r =0.584). Our findings suggested that CPAP treatment can significantly decrease the Aβ1–42/Aβ1–40 ratio, and improve SCD, which may play an important role in the prevention of dementia, but further research are warranted.

Soybean cultivation and crop rotation monitoring based on multi-source remote sensing data and Bi-LSTM enhanced model - Chang Chen; Chao Zhang; Lihua Zhao; Cuicui Yang; Xiaochuang Yao; Bin Fu (Computers and Electronics in Agriculture, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2025)

Multi-scale characterization and control factors of bedding-parallel fractures in continental shale reservoirs: Insights from the Qingshankou Formation, Songliao Basin, China - Xiaocen Su; Rukai Zhu; Jingya Zhang; Chang Liu; Lei Gong; Xiaohua Jiang; Xiaofei Fu; Mehdi Ostadhassan (Marine and Petroleum Geology, 2025)

Integrating lewis acid/base pairs and hydroxyfunctional groups as dual adsorption sites into porous biochar fiber for enhanced iodine capture - Hongquan Fu; Xiao Wang; Liping Li; Zhenyang Li; Jinming Chang; Fang Liao; Hejun Gao; Juan Zhang; Yunwen Liao (Journal of Water Process Engineering, 2025)

A comparative study on catalytic activation of peroxymonosulfate over polytype 2H-MoS2 and 3R-MoS2 - Shiting Li; Yuehan Wang; Chang Cai; Hong Huang; Honggen Peng; Xiaoxiao Fu; Zhimin Ao; Chunyang Nie (Journal of Environmental Chemical Engineering, 2025)

Efficient photocatalytic reduction of Hg (II) enabled by S-scheme Bi2O3/Bi/g-C3N4 heterojunctions with N, O dual vacancies - Guoju Chang; Yujing Zhou; Hui Wang; Shiyi Chen; Jialong Fu; Jing Sun; Shiyou Hao (Journal of Environmental Chemical Engineering, 2025)

Enhancing water quality and sustainable resource utilization through an AIoT-enabled intelligent circular agriculture system - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; Syuan-Ru Chen; Zhe-Dian Wu (Journal of Environmental Chemical Engineering, 2025)

Ore-forming mechanism of high-grade iron ore in Qidashan iron deposit, Liaoning Province: insights from the columbite-group minerals in granite and altered rocks - Yu-zeng Yao; Chang-ming Wei; Jing Liu; Jian-fei Fu; Sheng Xu (Journal of Asian Earth Sciences, 2025)

Effects of radio frequency explosion puffing on the texture of purple sweet potato chips and structural properties of pectin under different energy inputs and pressures - Chao Mao; Zhi Chang; Shijing Zhang; Pengfei Ye; Lei Yuan; Xiangwei Chen; Yequn Wang; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2025)

Effects of radio frequency explosion puffing on the texture of purple sweet potato chips and the physicochemical properties of the flour under different energy inputs and pressures - Chao Mao; Li Zhang; Shijing Zhang; Zhi Chang; Pengfei Ye; Tianshuo Yan; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Chemistry, 2025)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

Nano-thiophene-graphdiyne engineered buried interface toward homogeneous crystallization of perovskite films - Yutongyang Fu; Le Liu; Zhibin Yu; Rui Han; Yilin Chang; Yunxin Zhang; Wenfei Guo; Bin Huang; Jiajia Du; Wenfeng Yang; Tonggang Jiu (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Selective Adsorption of Cyanide From Highly Concentrated Sulphate and Thiocyanate Wastewater - Xiaoge Wang; Binchuan Li; Daxue Fu; Yongfeng Chang; Shuang Cui; Kuiren Liu; Xiaocai He; Jianshe Chen; Qing Han (Water, Air, & Soil Pollution, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Cranial and middle ear structures of the Early Cretaceous mammal Origolestes (Spalacotherioidea, Trechnotheria, Mammalia) - Zhe-Xi Luo; Chang-Fu Zhou; Peishu Li; April I. Neander (Palaeobiodiversity and Palaeoenvironments, 2025)
In this study we offer a new analysis of the internal cranial structures and the middle ear of the Early Cretaceous spalacotherioid mammal Origolestes lii , from the Yixian Formation of Liaoning, China. This anatomical study is based on CT scanning of a three-dimensionally preserved skull of this taxon. Spalacotherioid mammals are a group in the trechnotherian clade that includes modern therians such as marsupials and placentals. Fossils of these Mesozoic stem therians can yield useful information on the evolutionary origin of modern therian traits. Because cranial fossils of Mesozoic stem therians in three-dimensional preservation are scarce, and also because the internal cranial structures used to be difficult to examine, before CT scanning of fossils became available, the internal cranial structure was rarely documented in detail. Our CT scanning and visualisation of the skull of Origolestes lii have revealed new anatomical information of the orbital and sphenoid regions of the braincase, for this group. This is helpful for interpreting the comparative morphology of the skull structure among Mesozoic mammals. Furthermore, this specimen is a rare fossil in that it has preserved the petrosal articulation of the incus, as well as the Meckelian-attached middle ear. Evidence from our CT rendering and digital re-articulation demonstrates that a connection of the malleus to the ossified Meckel’s cartilage still existed in Origolestes lii .

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Thymus serpyllum extract exerts anticancer activities against colorectal cancer by modulating metastasis, cell cycle arrest, and apoptosis - Chao-Yuan Yao; Kai-Fu Chang; Ju-Huei Chien; Xiao-Fan Huang; Yu-Chi Chen; Ming-Chang Hsieh; Nu-Man Tsai (Molecular Biology Reports, 2025)

Correction: Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Muscle Development Transition and Myogenic Regulatory Factors Expression Profiling During Rapid Growth in Silver Pomfret (Pampus argenteus) - Chang Li; Chunlai Qin; Xinglong Chen; Yangfei Fu; Xiang Huang; Yuanbo Li; Shangliang Xu; Xiaojun Yan; Jiabao Hu; Yajun Wang (Journal of Ocean University of China, 2025)
Myogenic regulatory factors (MRFs) serve as crucial transcription factors that regulate muscle development and differentiation. Although MRFs have been extensively studied across various species, their specific role in the muscle development of silver pomfret ( Pampus argenteus ) has not been fully understood. To elucidate the role of MRFs in the muscle development of silver pomfret, we characterized the muscle growth pattern during the rapid growth phase of this organism (60–120 days post-hatching, Dph). The analysis revealed a distinct transition in growth mechanisms: Hyperplasia dominated muscle development before 90 Dph, whereas hypertrophy became predominant thereafter. The period between 80–90 Dph was a critical transition stage in the muscle growth pattern. Subsequently, five MRF family members, namely, myogenic determination 1 ( MyoD1 ), MyoD2 , myogenic factor 5 ( Myf5 ), Myf6 , and myogenin ( MyoG ), were initially identified in silver pomfret. MRFs exhibited evolutionary conservation and were specifically expressed in the muscle of the silver pomfret. Differential expressions of MRFs were observed across various stages of rapid growth and among individuals with differing growth rates. Upon the addition of exogenous regulatory factors, insulin-like growth factor 1 (IGF)-1 and transforming growth factor beta 1 (TGF-β1) in vitro , MRFs exhibited the most significant upregulation in response to 100 ng/mL of IGF-1. Conversely, Myf5 demonstrated the most pronounced down-regulation at 100 ng/mL of TGF-β1. For the remaining genes, the most effective suppression was achieved with 1 ng/mL of TGF-β1. These findings indicate the crucial role played by MRFs in the regulation of muscle growth and development. This study not only provides new insights into the functional roles of MRFs in fish muscle development but also establishes a foundation for the optimization of silver pomfret aquaculture strategies through the modulation of these factors.

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

ARR1/12-ETP1/2 model negatively regulates submergence-induced hypoxia response in A. thaliana - Meng Liu; Xuerui Li; Zeyu Cheng; Yuhang Wu; Wensen Fu; Yongqi Hu; Jin Yan; Songfeng He; Wenli Chang; Ruijia Zhang; Yingying Qian; Jianquan Liu; et al. (Journal of Plant Physiology, 2025)

Construction of a multiplex biosensor for the on-site rapid detection of phthalates in biological fluids based on single-stranded DNA aptamers - Kun Fu; Jia Zheng; Yichao Zhang; Chang Liu; Wenxiang Zhang; Siyu Chen (Journal of Hazardous Materials, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Machine learning-guided anti-photoaging peptides from Chinese giant salamander skin: Efficient preparation and mechanistic insights - Yongjie Zhou; Huijuan Zhang; Chunyue Zhao; Zixin Fu; Yuting Wang; Sam K.C. Chang; Yan Zhang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Food Chemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

A novel strategy based on mouse organoid biosensor for detecting umami substances and their synergistic effect - Minbo Li; Min Fan; Baifeng Fu; Zhihui Chang; Junjie Yi; Yingqi Xie; Wenwen Ren; Yu Tian; Qiyue Zhao; Shuzhen Cheng; Xianbing Xu; Ming Du (Food Chemistry, 2025)

3D DDA-MPM coupling method for fluid–solid interaction: Theory, validation and application in tunnels - Hongyun Fan; Liping Li; Yuguang Fu; Xiangyu Chang (Computers and Geotechnics, 2025)

All-round management of lead iodide toward efficient perovskite solar cells - Zhibin Yu; Le Liu; Yutongyang Fu; Yilin Chang; Jiajia Du; Zhiwei Ma; Tonggang Jiu (Chemical Engineering Journal, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Accelerating light-driven bioreaction with interfacial engineered microalgae-bacteria consortia: Unraveling positive charge-mediated biological interaction - Haixing Chang; Xueqing Gui; Meina Han; Jingwei Fu; Liandong Zhu; Shih-Hsin Ho (Chemical Engineering Journal, 2025)

A novel upcycling process of polystyrene wastes into benzaldehyde by catalyst-free laser flash depolymerization and in-line oxidation - Fu-Lu Chang; Lun Chen; Bin Hu; Fu-Rui Chen; Han Yang; Guang-Jian He (Chemical Engineering Journal, 2025)

Versatile nano-NH2-MIL-53(Al) tailored excellent fire resistance, mechanically robust, and ultraviolet to high-energy blue light blocking clear carboxymethyl cellulose films - Qiu Fu; Jingyuan Zhang; Ying Qin; Weimin Guo; Kuo Zhang; Tianyuan Xiao; Jiang Chang; Lijian Sun; Haiqiang Shi (Carbohydrate Polymers, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Hanging drop culture reprograms mesenchymal stem cell transcriptome to enhance cell delivery efficiency via attenuated pulmonary entrapment - Hsiang-Tzu Lee; Sheng-Yung Fu; Wei-Han Weng; Wei-Chen Chao; Yu-Pao Hsu; Nan-Ping Yang; Yu-Hsu Chen; Shau-Kwaun Chen; Chien-Wen Chang (Drug Delivery and Translational Research, 2025)
The three-dimensional (3D) culture system has emerged as an indispensable platform for modulating stem cell function in biomedicine, drug screening, and cell therapy. Despite a few studies confirming the functionality of 3D culture, the molecular factors underlying this process remain obscure. Here, we have utilized a hanging drop method to generate 3D spheroid-derived mesenchymal stem cells (3D MSCs) and compared them to conventionally 2D-cultured MSCs. The results showed that 3D MSCs exhibited distinct phenotypic features than 2D-cultured MSCs and expressed different transcriptional responses, as found from RNA-Seq analysis. Gene ontology (GO) annotations and KEGG pathway mapping pinpointed that the 3D MSCs responded more actively to incoming signals as they upregulated receptors and cytokine production while downregulating proteolysis-, cytoskeletal-, extracellular matrix-, and adhesion-related genes. Functionally, these MSCs also displayed enhanced chemotaxis and improved pulmonary transgression post-intravenous injection. This study provides mechanistic insights on addressing a significant limitation of MSC therapy: pulmonary entrapment after systemic delivery. Moreover, upregulated pluripotency-associated genes, such as Oct4, Sox2, and Nanog, suggest that the 3D MSCs possessed enhanced stemness and regenerative capacity. The results indicate that 3D spheroid culture reshapes MSC transcriptomic and functional profiles and emerges as a promising strategy for improving their therapeutic potential in regenerative medicine. Graphical abstract

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Retraction notice to “Effect of calcium and phosphorus on ammonium and nitrate nitrogen adsorption onto iron (hydr)oxides surfaces: CD-MUSIC model and DFT computation” [Chemosphere 357, June 2024, 142070] - Mengke Jia; Jie Ma; Qiongqiong Zhou; Lijie Liu; Xiaolei Jie; Hongen Liu; Shiyu Qin; Chang Li; Fuqing Sui; Haichao Fu; Haijiao Xie; Long Wang; et al. (Chemosphere, 2025)

Strongly enhanced topological quantum phases in dual-surface AlO -encapsulated MnBi2Te4 - Zichen Lian; Yongqian Wang; Yongchao Wang; Liangcai Xu; Xinlei Hao; Shuai Yang; Bohan Fu; Jinsong Zhang; Chang Liu; Yayu Wang (Science Bulletin, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Acidity-gradient controlled conversion of byproduct gypsum into high-purity whiskers: A synergistic process for wastewater treatment and resource recovery - Binchuan Li; Yan Li; Zihao Wang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Yina Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

Vanadium-driven surface engineering to suppress Sr segregation in perovskite ceramics for nuclear waste immobilization - Yinlin Chang; Tao Liu; Jingyuan Rao; Min Fu; Yijun Guo; Shuliang Zou; Dewen Tang; Zetian Tao (Journal of Environmental Chemical Engineering, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

Salmon leather collagen peptide alleviates UVA-induced photoaging via Nrf2/Keap1 pathway by enhancing antioxidant defense and preserving skin elasticity - Baifeng Fu; Yu Wan; Xiaoyu Ma; Zhihui Chang; Ximing Yang; Xinran Liu; Haixia Wu; Shuzhen Cheng; Ming Du (Food Bioscience, 2025)

Synthesis of expanded microcrystalline graphite/Mn0.4Zn0.6Fe2O4 composites for electromagnetic wave absorption - Mingzhe Liu; Bo Wang; Yujiang Wang; Binchuan Li; Daxue Fu; Yongfeng Chang; Jianshe Chen; Kuiren Liu; Qing Han; Xudong Lu; Cean Guo; Shicheng Wei (Chemical Engineering Journal, 2025)

Genome-wide Identification and Expression Analysis of the Argonaute Gene Family in Sugar Beet (Beta vulgaris L.) - Zengjuan Fu; Liang Wang; Xiaodong Li; Yuanyuan E; Yahui Liang; Bizhou Zhang; Shangmin Zhao; Hui Zhang; Wenzhe Zheng; Chen Bai; Mengyuan Sun; Ziqiang Zhang; et al. (Sugar Tech, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

Evaluating the ecological and agricultural benefits of intelligent sustainable green energy floating gardens: impacts on microorganisms and vegetable growth - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Hong-Bin Lai; Yi-Zhen Yu (Environmental Science and Pollution Research, 2025)

Impact of SNP Variants in PON-1 or UGT1A1 on Iron Chelation Therapy Outcomes and Zinc Status in Thalassemia Major Patients - Meng-Yao Lu; Wan-Fu Tsai; Chang-Shiann Wu; Chien-Sheng Wang; Nailis Syifa; Mong-Liang Lu; Jiahn-Haur Liao; Wei J. Chen; Kai-Hsin Lin; Tzu-Hua Wu (Biological Trace Element Research, 2025)

Chronic low-level exposure to Pb, Hg, and Cd mixture triggers brain premature aging in rat - Jie Xie; Lu Ouyang; Jiajun Li; Shuo Yang; Qi Li; Yue Li; Lingyu Yan; Yihong Fu; Qijun Li; Yuting Xia; Xinling Chen; Ziyang Fu; et al. (Toxicology, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Multi-objective interpretation machine learning framework for Synergistically optimizing energy consumption and surface quality in electrolytic copper foil production - Zhengwu Yang; Xinwan Zhang; Huawei Hu; Yaqi Shi; Wenxuan Xu; Huiting Huang; Wenzhuo Zhang; Dan Fu; Zhihao Lu; Daqing Jia; Dingming Chang; Lehua Zhang (Journal of Cleaner Production, 2025)

Petrogenesis of mafic to intermediate rocks within the crustal sequence of the Luqu ophiolite in the Yarlung-Tsangpo suture Zone, southern Tibet and implications for the Neo-Tethys evolution - Chang Zhang; Chuan-Zhou Liu; Tong Liu; Wen-Bin Ji; Zhen-Yu Zhang; Fu-Yuan Wu (Journal of Asian Earth Sciences, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Earth pressure on rotating-about-top excavation retaining walls adjacent to existing structures - Xin-yi Huang; Chang Chen; Fu-quan Chen; Yi-xing Kuang (Computers and Geotechnics, 2025)

Insight into the piezo-activation of peroxymonosulfate by 1T/2H-MoS2: piezopotential boosting the formation of Mo-peroxymonosulfate complexes as the major reactive species - Tian Jiang; Chang Cai; Honggen Peng; Jianjun Li; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2025)

Efficient mineralization of antibiotics by novel manganese oxide-based Fenton-like systems: Enhanced performance, toxicity reduction, and life-cycle sustainability - Fu-Qiao Yang; Xin-Tong Huang; Chang-Wei Bai; Zhi-Quan Zhang; Pi-Jun Duan; Fei Chen (Chemical Engineering Journal, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Techno-economic analysis and life cycle assessment of lignin derived 4-hydroxy-3,5-dimethoxyphenylacetic acid - Dexin Zhang; Pu Wang; Zhonghao Chen; Shihao Su; Yan Fu; Wenjun Lei; Jie Chang; Lei Wang (Chemical Engineering Journal, 2025)

Exploring the relative importance of climatic drivers on carbon sink capacity dynamics in the Three Gorges Reservoir Area, China - Xin Zheng; Yuanyuan Fu; Shaoqiang Wang; Lunche Wang; Zhijie Xie; Chang Liu (Stochastic Environmental Research and Risk Assessment, 2025)

Comparative analyses highlight wheat TaSPL4-D as a promising candidate gene to optimize plant architecture traits in rice - Li Li; Fu Shi; Lizhi Yin; Junli Chang; Mingjie Chen; Yuesheng Wang; Guangxiao Yang; Guangyuan He; Yin Li (Plant Cell Reports, 2025)

Aircraft Observations of Ice-Phase Microphysical Characteristics in Stratiform Clouds over the Qilian Mountains in Northwestern China - Yuyan Long; Tuanjie Hou; Baojun Chen; Shuangxi Fu; Rong Zhang; Shaofeng Hua; Yi Chang; Boyue Zhang (Advances in Atmospheric Sciences, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Zinc finger transcription factor ZNF384 mitigates LPS-induced ferroptosis and inflammation in lung epithelial cells by activating SESN2-mediated autophagy - Lu Shi; Hongxue Fu; Yingting Hao; Chang Liu; Fachun Zhou (Toxicology in Vitro, 2025)

Robust assessment of precipitation-temperature apparent scaling under global climate change - Zhijie Xie; Yuanyuan Fu; Hong S. He; Shaoqiang Wang; Lunche Wang; Chang Liu (Journal of Hydrology, 2025)

Canopy nitrogen and water addition affect fine-root survival strategies and carbon allocation in a warm-temperate forest in China - Wen Li; Yanzhu Su; Yiwen Qin; Fuwei Li; Tenglong Zhou; Yaqi He; Jianing Mao; Mengke Li; Chang Liu; Yifei Shi; Dandan Zhu; Chunyu Shen; et al. (Forest Ecology and Management, 2025)

High-efficient and reversible capture of protein by oxidized and carboxymethylated starch nanocrystals: Understanding interaction mechanism and regulating complexation - Wen-Xuan Hu; Jia-Yang Fu; Liang-Sen Liao; Ping Wang; Kexin Wang; Chang-Sen Jin; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Sustainable peroxymonosulfate activation by 1T/2H-MoS2 cathode for enhanced removal of organic pollutants: Performance and nonradical activation mechanism based on surface Mo-peroxymonosulfate complexes - Chang Cai; Tian Jiang; Honggen Peng; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Risk assessment of coastal dredging sediment plumes on the habitat of Indo-Pacific humpback dolphin (Sousa chinensis) - Chang He; Alessandro Stocchino; Zhen-Yu Yin; Francesco De Leo; Yin-Fu Jin; Xiang-Sheng Chen (Frontiers in Marine Science, 2025)
The Pearl River Estuary (PRE) and Hong Kong (HK) Waters are identified as two of the most important habitats worldwide for Indo-Pacific humpback dolphin ( Sousa chinensis ). However, the extremely rapid growth of coastal cities and near-shore reclamation lands posed great threats to delicate marine ecosystems and protected species. Dredging operations can exert non-negligible negative impacts on humpback dolphins, with high sediment concentrations standing out as a particularly significant threat. This study aims to apply a new risk assessment approach based on computational fluid dynamics (CFD) and unsupervised machine learning technique for quantitatively estimating the risk of high turbidity to marine mammals. As an extension, the risk to the natural habitat in PRE was statistically compared among five possible dredging locations according to HK reclamation projects. The results showed that sediment plumes could be enlarged quickly if dredging sites are close to places with high density of macro-vortices, such as the north corner of Lantau Island. In terms of temporal effects, dredging under scenarios with northeast wind has a higher probability of posing significant risks to dolphin habitats. In accordance with this strategy, reliable suggestions on the choice of construction location or period could be provided to the decision-makers before or during the coastal projects. The proposed strategy can also be flexibly extended to any coastal environment, serving as a valuable example for coastal and environmental management.

Petrogenesis and tectonic implication of the Neoproterozoic Shuimo alkaline-carbonatite complex from Northwestern margin of the Yangtze Block (China) - Bin Lin; Lian-Xun Wang; Yu-Fang Zhong; Xiao-Bing Qi; Xue-Wei Fu; Chang-Qian Ma (Precambrian Research, 2025)

Integrated coupling analysis and multi-objective optimization of mooring system for floating photovoltaic arrays - Huawei Han; Zhongxu Du; Gang Ma; Qiang Fu; Chang Zhang (Ocean Engineering, 2025)

Quantifying the effect of key factors on the shedding and decay rates of eDNA from the golden mussel - Yao Yang; Jiahao Zhang; Zhibing Chang; Mei Liu; Mengzhen Xu; Xinyi Zhou; Xudong Fu (Journal of Environmental Management, 2025)

SSRMF: A sparse spectral reconstruction enhanced matched filter for improving point-source methane emission detection in complex terrain - Ke Li; Kaixu Bai; Peng Fu; Penglong Jiao; He Chen; Xinqing Huang; Chaoshun Liu; Ni-Bin Chang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Mechanism study of the effects of astragaloside IV and quercetin on idiopathic pulmonary fibrosis - Ye Luo; Chang-jun Xu; Xing-hui Ai; Yu-ping Li; Xing Zhu; Chang-fu Yang (Journal of Natural Medicines, 2025)

Hierarchical Adaptive Fixed-Time Formation Control for Multiple Underactuated Autonomous Underwater Vehicles Under Uncertain Disturbances and Input Saturation - Jiacheng Chang; Lanyong Zhang; Yifan Tan; Xue Fu; Hongjun Yu (Journal of Marine Science and Engineering, 2025)
Recent advances in multiple autonomous underwater vehicles (AUVs) have highlighted formation control as a critical challenge for underwater collaborative operations. To address the inherent coupling between formation coordination and individual control in conventional approaches, this paper proposes a novel hierarchical framework of adaptive fixed-time formation control for multiple underactuated AUVs. This framework decouples AUVs’ formation requirements and individual control challenges into two distinct layers: the Collision-free Formation Trajectories Generation (CFTG) Layer and the Adaptive Trajectories Tracking (ATT) Layer. In the CFTG Layer, a consensus-based controller is developed to generate the desired trajectories for the AUVs to meet the requirements of complex formation tasks. And an improved artificial potential field method is proposed to ensure AUVs can reach the target point when the target is close to obstacles. In the ATT Layer, an auxiliary compensation system is designed to address the issue of input saturation. Furthermore, the adaptive fixed-time controllers are proposed to handle the uncertain parameters in the model, enabling underactuated AUVs to track the desired trajectory precisely. Both layers guarantee fixed-time convergence to increase the convergence speed. Simulations are conducted to demonstrate the effectiveness and better performance of the proposed method.

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

A systematic review on mechanism and regulation strategy of marine hydrodynamic noise: Advances, challenges, and perspectives - Xin Jin; Hua-long Huang; Yuan Tao; Fu-gui Zhang; Min Luo; Chang-yuan Fan; Tao Tang (Ocean Engineering, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Electric field-assisted aerobic composting: From basic principles to applications - Tao Fu; Huan Mi; Chang Shen; Shuqun Zhang; Huayuan Shangguan; Jiahuan Tang; Hao Lin; Zhen Yu (Journal of Environmental Management, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Method for planning subarea emission reduction strategies to improve ozone over a large area: A case of Taiwan - Tu-Fu Chen; Xin-Li Gong; Chang-You Tsai; Ken-Hui Chang (Atmospheric Environment, 2025)

Bytes drive green: decoding the global digital economy’s environmental impact - Gen-Fu Feng; Ping-Chuan Jiang; Zhu-jia Yin; Chun-Ping Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Modeling and Quantitative Assessment of Critical Defects in Shield Tunnels with Cascading Effects - Xiangyu Chang; Rui Zhang; Jianxiao Mao; Yuguang Fu; Hongyun Fan; Hao Wang (Geotechnical and Geological Engineering, 2025)

Pathotyping and molecular serotyping of clinical isolates of Glaesserella parasuis in Taiwan - Wei-Hao Lin; Chia-Hung Yen; Cheng-Yao Yang; Chuen-Fu Lin; Yung-Fu Chang; Chao-Nan Lin; Ming-Tang Chiou (Brazilian Journal of Microbiology, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

AmCERK1 and AmLYK3 interaction mediates CIP-induced defense responses in A. macrocephala - Lei Chen; Xuyan Fu; Kun Wu; Xiangbing Chang; Wei Tian (Journal of Plant Physiology, 2025)

Life cycle greenhouse gas emissions and mitigation opportunities of high-speed train in China - Zimeng Cai; Changqing Xu; Huimin Chang; Jing Guo; Chenling Fu; Nan Li; Dong Zhao; Ming Xu (Journal of Cleaner Production, 2025)

Identification of novel umami peptides from oyster hydrolysate and the mechanisms underlying their taste characteristics using machine learning - Baifeng Fu; Minbo Li; Zhihui Chang; Junjie Yi; Shuzhen Cheng; Ming Du (Food Chemistry, 2025)

3D printing of synthetic microbial consortium for boosting bioelectricity generation from starch - Xiao-Jing Wang; Jie Wang; Zhizhi Yang; Ye Zhang; Kai Cheng; Jun-Ying Han; Fu-Xiang Chang; Yang-Chun Yong (Chemical Engineering Journal, 2025)

Enhanced sphericity and uniformity in adenocarcinoma spheroids on chip via fibroblast co-culture for electrochemical drug screening - Cheol-Hwi Kim; Fu Nan Ju; Chang-Dae Kim; Hyungbin Son; Tae-Hyung Kim (Chemical Engineering Journal, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Forest litter decomposition stimulates heterotrophic nitrogen fixation by driving diazotrophic community interactions - Chang Pan; Shuikuan Bei; Zhe Hua; Mengtian Zhou; Zichen Wang; Ruoxian Fu; Xiaogang Li (Biology and Fertility of Soils, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Electric field as an activator of inoculated Bacillus clausii enhances humification during electric field-assisted aerobic composting - Jiahuan Tang; Huan Mi; Chang Shen; Keren Ding; Shuqun Zhang; Huayuan Shangguan; Tao Fu; Jie Ye; Hao Lin (Journal of Environmental Management, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

A review of redox-active polymers for selective electrochemical removal of uncharged organic pollutants from water - Zhen Qiu; Guanda Shen; Wenxin Yan; Xin Zeng; Maonan Jiang; Yongfu Li; Hai Xiang; Hailu Fu; Chang Liu; Bing Yu (Journal of Environmental Chemical Engineering, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

Fucoxanthin promotes the conversion efficiency of alpha-linolenic acid in feeding to docosahexaenoic acid in quail egg yolk - Wen-Lei Guo; Shuai-Shuai Fu; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Yu-Ming Wang; Tian-Tian Zhang (Food Chemistry, 2025)

A high-performance color conversion and UV to blue light blocking materials enabled by iron-coordinated cellulose - Lijian Sun; Jingyuan Zhang; Ying Qin; Weimin Guo; Kuo Zhang; Jiang Chang; Tianyuan Xiao; Wei Wang; Qiu Fu (Chemical Engineering Journal, 2025)

Exploration of relaxation time for the characterization of PEMFC by electrochemical impedance spectroscopy and extended irreversible thermodynamics - Yaorui Shen; Chaozheng Chang; Jianqin Fu; Xilei Sun (Chemical Engineering Journal, 2025)

Surface display of aspartate ammonia-lyase from Lactobacillus paracasei on Pichia pastoris - Chen-Chi Chang; Yi-Hao Huang; Hua-Kun Fu; Kai-Wei Chang; Shih-Hsuan Chen; Yu-Ting Yu; Xin-Ying Lau; Jhih-Ying Ciou; He-Yuan Hsieh; Yung-Ju Chen; Lu-Sheng Hsieh (World Journal of Microbiology and Biotechnology, 2025)

Landscape Effects on Local Species Richness of Woody Specialists in Subtropical Montane Cloud Forest of Taiwan - Yu‐Pei Tseng; David Zelený; Chang‐Fu Hsieh (Journal of Biogeography, 2025)
Aim How is the local species richness of woody specialists in vegetation plots located within subtropical montane cloud forests (SMCFs) affected by the landscape structure of the surrounding SMCF habitat patch? Location Subtropical montane cloud forests in Taiwan. Taxon Woody species specialised in growing in foggy conditions. Methods We used plant occurrence data from major herbaria together with fog frequency data to identify fog specialists of SMCFs in Taiwan. Subsequently, we extracted 20 × 20 m forest vegetation plots from the National Vegetation Database of Taiwan and calculated the richness of woody specialists in each of them. Using a published predicted SMCFs distribution map, we estimated the landscape context of SMCFs around each vegetation plot within circular buffer zones of increasing radius. The variables of landscape structure include those related to the area of SMCFs habitat (area and connectivity), surrounding heterogeneity (topographical heterogeneity and vegetation diversity) and edge effect (the nearest distance from the plot to the edge and the edge length). The multiple linear regression model was used to investigate which of the three mechanisms of landscape context has the strongest effect on the local richness of fog specialists. Results Only the area of SMCFs habitat patch shows a significant positive effect on the local species richness of woody specialists in the plot when considering all the landscape variables. Area per se might be a possible mechanism that supports this positive species‐area relationship. Additionally, the area of SMCFs patch is highly correlated with connectivity, indicating that larger SMCF patches enhance connectivity beyond buffer zones, sustaining species through the rescue effect from the regional species pool. Main Conclusions Patch size and connectivity are crucial for the species richness of woody specialists in SMCFs in Taiwan. For conservation, we recommend protecting larger, less fragmented SMCF patches to maintain biodiversity.

Emission factors and driving forces of provincial-level CO2 from electricity production and consumption in China from 2013 to 2020 - Ruoxi Xiong; Chenling Fu; Huimin Chang; Nan Li; Shen Qu; Dong Zhao; Changqing Xu; Jianchuan Qi; Ming Xu (Journal of Environmental Management, 2025)

Fabrication of soy protein isolate-konjac glucomannan emulsion gels to mimic the texture, rheological behavior and in vitro digestion of pork fat - Jiarui Zhao; Baoyue Chang; Jiayu Wen; Yidan Fu; Yu Luo; Jing Wang; Yan Zhang; Xiaonan Sui (Food Chemistry, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Glycolysis of waste polyurethane foam for preparing recycled polymer materials: Optimization and techno-economic evaluation - Chun Chang; Youfeng Jiang; Yucheng Lin; Kai Fu; Chunbao Xu; Shiqiang Zhao (Chemical Engineering Journal, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Genome-wide identification of the sugar beet (Beta vulgaris L.) DMP gene family and its potential role in abiotic stress - Pingan Han; Yue Chang; Kuangang Tang; Liang Wang; Zhijun Xiu; Jing Yang; Haibo Shi; Yahui Liang; Ruifen Sun; Shaofeng Su; Ziqiang Zhang; Zengjuan Fu; et al. (Genetic Resources and Crop Evolution, 2025)

Creep constitutive model of yellow sandstone under coupling action of unloading and wet-dry cyclic damage - Zhe Qin; Zhen Liu; Run-chang Zhang; Hou-li Fu (Journal of Mountain Science, 2025)

Unraveling the impact of urban expansion on vegetation carbon sequestration capacity: A case study of the Yangtze River Economic Belt - Jinyang Wang; Zhenfeng Shao; Peng Fu; Qingwei Zhuang; Jiahui Chang; Peiqing Jing; Zhiyu Zhao; Zhenpeng Xu; Siyuan Wang; Fei Yang (Sustainable Cities and Society, 2025)

Dramatic effect of extreme rainfall event and storm on microbial community dynamics in a subtropical coastal region - Madeline Olivia; Clara Natalie Annabel; Patrichka Wei-Yi Chen; Chih-hao Hsieh; Feng-Hsun Chang; Pei-Chi Ho; Chia-Te Chien; Chien-Fu Chao; Vladimir Mukhanov; An-Yi Tsai (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Antimicrobial perylenequinones isolated from the endophytic fungus Alternaria alstroemeriae - Yong-Fu Li; Fang Yue; Xu-Ri Wan; Chang Li; Yi Sun; Yue-Hu Pei (Phytochemistry Letters, 2025)

On-line hydropyrolysis gas chromatography-mass spectrometry (HyPy-GC–MS) for kerogen-bound biomarkers - Fu Wang; Yuhong Liao; Chang Samuel Hsu (Organic Geochemistry, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

High-entropy design of Ruddlesden-Popper structured LNO for enhanced performance in proton solid oxide fuel cells - Mingming Zhang; Yinlin Chang; Weiyuan Xiang; Jiani Liu; Xiangbo Deng; Jing Zhou; Min Fu; Zetian Tao (Fuel, 2025)

Maltodextrin vitamin E succinate: A novel antioxidant emulsifier for formulating functional nanoemulsions - Xiang Luo; Yuanyuan Chen; Zhe Jiang; Hongze Wu; David Julian McClements; Chang Zhang; Yanyan Zhou; Hongliang Fu; Xuguang Yin; Wenna Huang; Zhixin Wang; Lemao Yu; et al. (Food Chemistry, 2025)

PVA/chitosan-based multifunctional hydrogels constructed through multi-bonding synergies and their application in flexible sensors - Tiantian Wang; Bingbing Xu; Tong Yu; Yan Yu; Jiayi Fu; Yuhang Wang; Xianwu Gao; Zhebin Xue; Ruoxin Li; Guangtao Chang (Carbohydrate Polymers, 2025)

Unlocking the potential differences and effects of the anode and cathode regions on N2O emissions during electric field-assisted aerobic composting - Huayuan Shangguan; Chang Shen; Keren Ding; Xiangtian Peng; Huan Mi; Shuqun Zhang; Jiahuan Tang; Tao Fu; Hao Lin (Bioresource Technology, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Effect of ambient ozone and its interactions with ambient PM2.5 and temperature on peak expiratory flow in adults with asthma - Dongxia Jiang; Ying Shang; Zhengxiong Li; Xianlin Mu; Xuehu Han; Xinzhuo Xie; Guanglong Fu; Yunshu Zhang; Shaodan Huang; Chun Chang (Atmospheric Environment, 2025)

Underground laboratories · Deep underground observation · Scientific questions—Insights from observations of multi-physic fields in deep underground labs - Huiqi Ren; Yun Wang; Chang Chen; Guangyu Fu; Longqing Qiu; Lianghui Guo; Chengliang Xie; Yongsheng He; Heping Sun; Jiwen Teng (Science China Earth Sciences, 2025)

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

Laser flash pyrolysis of face mask waste to vinylidene-terminated PP wax and further functionalized as compatibilizer - Hao-Qin Zhang; Lun Chen; Chang-Qian Chen; Fu-Lu Chang; Yi-Xun Tian; Xia Jiang; Wei-Tao Huang; Bin Hu; Xian-Wu Cao; Xiao-Chun Yin; Guang-Jian He (Waste Management, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Screening and isolation of polyethylene microplastic degrading bacteria from mangrove sediments in southern China - Yinglin He; Chang Fang; Zeqian Zeng; Bing Fu; Ziyi Cui; Jun Wang; Huirong Yang (Science of The Total Environment, 2025)

Effects of tannic acid on physicochemical properties of gluten-free flour and the underlying mechanisms - Yanbin Guan; Yaqiong Wang; Xun Yang; Li Li; Fu Shi; Miao Li; Mingjie Chen; Yuesheng Wang; Guangxiao Yang; Junli Chang; Guangyuan He; Yin Li (Food Hydrocolloids, 2025)

Nonlinear finite element model updating and fourier neural operator for digital twin of reinforced concrete containment vessel under seismic excitations - Si Fu; Chang-Ching Chang; Chawit Kaewnuratchadasorn; Jiaji Wang; Chiun-Lin Wu; Yi-Lung Mo; Thomas T.C. Hsu (Engineering Structures, 2025)

Impact of in–situ bioelectric field on biogas production, membrane fouling and microbial community in an anaerobic membrane bioreactor under sulfadiazine stress - Haojie Huang; Yutong Sun; Qing Du; Fu Gao; Zi Song; Zhiwen Wang; Suyun Chang; Xinbo Zhang; Wenshan Guo; Huu Hao Ngo (Chemical Engineering Journal, 2025)

Cs-Doped BCCF perovskite with enhanced surface proton acid sites for high-performance R-PCECs - Yang Gao; Kechen Liu; Xuan Zhang; Qi Li; Yinling Chang; Min Fu; Zetian Tao (Chemical Engineering Journal, 2025)

All-natural hydrogel composed of carboxymethyl chitosan and oxidized dextran for promoting wound healing by immune-microenvironment regulation - Ming Li; Huamin Tang; Xiaoyuan Geng; Jiahua Zhou; Sitong Mou; Chang Li; Jing Chang; Minhui Xu; Chuanlin Wang; Runjia Fu; Yanhua Wang (Carbohydrate Polymers, 2025)

The Role of Intravenous Anesthetics for Neuro: Protection or Toxicity? - Kaixin Wang; Yafeng Wang; Tianhao Zhang; Bingcheng Chang; Daan Fu; Xiangdong Chen (Neuroscience Bulletin, 2025)
The primary intravenous anesthetics employed in clinical practice encompass dexmedetomidine (Dex), propofol, ketamine, etomidate, midazolam, and remimazolam. Apart from their established sedative, analgesic, and anxiolytic properties, an increasing body of research has uncovered neuroprotective effects of intravenous anesthetics in various animal and cellular models, as well as in clinical studies. However, there also exists conflicting evidence pointing to the potential neurotoxic effects of these intravenous anesthetics. The role of intravenous anesthetics for neuro on both sides of protection or toxicity has been rarely summarized. Considering the mentioned above, this work aims to offer a comprehensive understanding of the underlying mechanisms involved both in the central nerve system (CNS) and the peripheral nerve system (PNS) and provide valuable insights into the potential safety and risk associated with the clinical use of intravenous anesthetics.

The causal effect of losing irrigated water on farmland prices - Hung-Hao Chang; Brian Lee; Sheng-Fu Tsai (Paddy and Water Environment, 2025)

Organic matter determines the exchange of nutrients at sediment-water interface in coastal bays - Jiasen Zhong; Ehui Tan; Chunwei Fu; Guiyi Ma; Yongkai Chang; Zhixiong Huang; Jingchao Yin; Fengying Li; Jianzhong Su; Min Xu; Zhenzhen Zheng; Jian’an Liu; et al. (Acta Oceanologica Sinica, 2025)

National investigation of bisphenols in the surface soil in China - Chang-Yu Weng; Ying-Ying Zhang; Fu-Jie Zhu; Shi-Ming Jia; Wan-Li Ma (Science of The Total Environment, 2024)

Black phosphorus quantum dots induced neurotoxicity, intestinal microbiome and metabolome dysbiosis in zebrafish (Danio rerio) - Xiaonan Cao; Lili Chen; Yingxin Fan; Mengxiao Fu; Qiyan Du; Zhongjie Chang (Science of The Total Environment, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

PBAT biodegradable microplastics enhanced organic matter decomposition capacity and CO2 emission in soils with and without straw residue - Sha Chang; Chao Chen; Qing-Long Fu; Aoyu Zhou; Zhuyao Hua; Fengxiao Zhu; Shiyin Li; Huan He (Journal of Hazardous Materials, 2024)

Fundamental properties of the green solvent CO2 expanded ethyl lactate: Peng-Robinson equation of state, molecular dynamics simulation, and density functional theory studies - Guoxiao Cai; Yao Fu; Choji Fukuhara; Chang Yi Kong (Journal of Environmental Chemical Engineering, 2024)

Bifunctional reduced graphene oxide/polyelectrolytes/MoS2-AuNPs hybrids with Vis/NIR photocatalytic and photothermal activities for biosafe and efficient antibacterial applications - Meng Fu; Chang Luo; Qi Yuan; Zequn Ma; Quansheng Long; Baihui Liu; Dang Wu; Jingshui Xu; Xiangming Li (Journal of Environmental Chemical Engineering, 2024)

Electrodeposition of dense spherical Ni3P on nickel foam cathode enhance nitrate electrochemical reduction via promoting nitrate adsorption - Wenzhao Fu; Guangyuan Meng; Di Yin; Xinwan Zhang; Yaqi Shi; Zhengwu Yang; Dingming Chang; Peng Chen; Lehua Zhang (Journal of Environmental Chemical Engineering, 2024)

Modelling of mass transport in fractured crystalline rock using velocity interpolation and cell-jump particle tracking methods - Chieh-Chun Chang; Yi-Fu Chiou; Yu-Hsiang Shen; Yun-Chen Yu (Geomechanics for Energy and the Environment, 2024)

Establishment of a workflow for high-throughput identification of anti-inflammatory peptides from sea cucumbers - Bingxue Jiang; Jinqiu Liu; Zihao Zhu; Linlan Fu; Yaoguang Chang; Yanchao Wang; Changhu Xue (Food Research International, 2024)

Improvement of soil nutrient cycling by dominant plants in natural restoration of heavy metal polluted areas - Ting Li; Sichen Wang; Luoqi Zhao; Xinqi Yuan; Yuhan Gao; Denggao Fu; Chang'e Liu; Changqun Duan (Environmental Research, 2024)

Construction of ultra-smooth and void-free buried interface via bilateral chemical bridging for efficient and hysteresis-suppressed perovskite solar cells - Yao Yao; Fushen Lu; Zhibin Yu; Qinglin Du; Jiajia Du; Yilin Chang; Zhiwei Ma; Yutongyang Fu; Yu Li; Le Liu; Tonggang Jiu (Chemical Engineering Journal, 2024)

A bounding surface model of methane hydrate-bearing carbonate sand-silt mixtures - Lu Ma; Yuzhe Ren; Jincheng Ren; Shan Chang; Xuemin Zhu; Kaiyu Fu; Huan Ye; Bi Sun (Marine Georesources & Geotechnology, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

Identification of Central Genes and Regulatory Pathways Associated with Hyperlipidemia in Rats - Xinyue Fu; Xinni Song; Shufang Niu; Jiali Liu; Songli Shi; Hong Chang; Chuanming Zhang; Jun Qi; Peng Wang; Yingchun Bai; Wanfu Bai (Biochemical Genetics, 2024)

Improvements in source apportionment of multiple time-resolved PM2.5 inorganic and organic speciation measurements using constrained Positive Matrix Factorization - Chun-Sheng Huang; Yi-Hsien Liu; Ho-Tang Liao; Chia-Yang Chen; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Assessment of heavy metal contamination in the surface sediments, seawater and organisms of the Pearl River Estuary, South China Sea - Huanhuan Zhang; Dehao Tang; Jian He; Xiaohong Yang; Ziyue Feng; Yutao Fu; Xiaojie Yuan; Xiaohong Chang; Deqiang Teng; Fenfen Liu; Shengzhong Ma (Science of The Total Environment, 2024)

Evolution and legacy of East Asian aurochs - Jiawen Hou; Xiwen Guan; Xiaoting Xia; Yang Lyu; Xin Liu; Yuri Mazei; Ping Xie; Fengqin Chang; Xiaonan Zhang; Jialei Chen; Xinyi Li; Fengwei Zhang; et al. (Science Bulletin, 2024)

Estimation of breakout force of spudcan footing in structured clay - Yanan Xie; Dong Wang; Jingbin Zheng; Dengfeng Fu; Kuntan Chang (Ocean Engineering, 2024)

Degradation of thiosulfate ions in sodium aluminate solution photocatalyzed by Co-TiO2@ZIF-8 - Jingyi Hao; Binchuan Li; Jing Dai; Daxue Fu; Yongfeng Chang; Jianshe Chen; Na Xu; Kuiren Liu; Qing Han (Minerals Engineering, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

The impact and mechanism analysis of Clean Development Mechanism on the synergistic effects of pollution mitigation and carbon reduction - Yifei Xu; Jiachao Peng; Jiali Tian; Siyu Fu; Chang Hu; Shuke Fu; Yanzhen Feng (Environmental Research, 2024)

Metabolomics and microbiomics revealed the combined effects of different-sized polystyrene microplastics and imidacloprid on earthworm intestinal health and function - Huimin Fu; Lizhen Zhu; Lang Chen; Lan Zhang; Liangang Mao; Chi Wu; Yiming Chang; Jinhua Jiang; Hongyun Jiang; Xingang Liu (Environmental Pollution, 2024)

Central nervous system disturbances by thiamethoxam in Japanese quail (Coturnix japonica): In vivo, ex vivo, and in silico study - Yifan Pan; Yue Niu; Yongqi Fu; Shuaimeng Wang; Jing Chang; Wentao Liu; Weiyu Hao; Lu Yang; Peng Xu (Environmental Pollution, 2024)

Three birds with one stone: Fe(Ⅲ)-coordinated cross-linked antibiofouling cellulose composite membrane for synergistic photodynamic and Fenton-like water disinfection - Xiaomin Liao; Qin Zhong; Zhou Xu; Hongquan Fu; Jinming Chang; HeJun Gao; Yi Chen; Yunwen Liao (Chemical Engineering Journal, 2024)

Single-cell immune landscape of measurable residual disease in acute myeloid leukemia - Xiaodong Mo; Weilong Zhang; Guomei Fu; Yingjun Chang; Xiaohui Zhang; Lanping Xu; Yu Wang; Chenhua Yan; Mengzhu Shen; Qiuxia Wei; Changjian Yan; Xiaojun Huang (Science China Life Sciences, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Exploring the short-term effects of extreme temperatures on tuberculosis incidence in Shantou, China: a Coastal City perspective - Yaqian Su; Ruiming Chen; Zhuanghao Chen; Jianxiong Lin; Hui Fu; Zicheng Cao; Qiaocheng Chang; Liping Li; Suyang Liu (International Archives of Occupational and Environmental Health, 2024)

Stress Field Comparison in Deep Coal Mines: Roof Cutting Versus Traditional Methods - Jun Yang; Xu Chang; Yubing Gao; Qiang Fu; Shilin Hou; Hongxu Song; Hongyu Jin; Yuxuan Liu (Geotechnical and Geological Engineering, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Optimizing tradeoff strategies of soil microbial community between metabolic efficiency and resource acquisition along a natural regeneration chronosequence - Qiang Lu; Zhengfeng An; Beibei Zhang; Xiaoqiang Lu; Xia Mao; Jiaqi Li; Scott X. Chang; Yan Liu; Xiangxiang Fu (Science of The Total Environment, 2024)

Fabrication of catalytic ceramic nanofiber membrane with high permeability and superior catalytic performance - Yulong Yang; Wanyi Fu; Xixi Chen; Zhiwen Hu; Qibing Chang; Xihui Zhang (Journal of Environmental Chemical Engineering, 2024)

Zinc oxide nanoparticles and nano-hydroxyapatite enhanced Cd immobilization, activated antioxidant activity, improved wheat growth, and minimized dietary health risks in soil-wheat system - Guangxin Li; Ran Duan; Xinran Liang; Hongen Liu; Shiyu Qin; Long Wang; Haichao Fu; Peng Zhao; Chang Li (Journal of Environmental Chemical Engineering, 2024)

Preparation of plant-derived compounds/chitosan/gelatin antifungal film and investigation of its control effect on Zygosaccharomyces rouxii contamination in concentrated apple juice - Huxuan Wang; Xuanzhi Wang; Jing Dong; Jiaxuan Fu; Tiantian Zhao; Yanan Zhu; Dawei Chang (Food Bioscience, 2024)

Experimental Study on the Influence of Structural Planes on Rockbursts in Deep-Buried Hard-Rock Tunnels - Zhenrui Zhang; Shunchuan Wu; Haiyong Cheng; Longqiang Han; Xinke Chang; Xin Fu (Rock Mechanics and Rock Engineering, 2024)

Long-term green manuring increases soil carbon sequestration via decreasing qCO2 caused by lower microbial phosphorus limitation in a dry land field - Zhengbo Ma; Ting Liang; Haoran Fu; Qingxu Ma; Danna Chang; Jiudong Zhang; Zongxian Che; Guopeng Zhou; Weidong Cao (Agriculture, Ecosystems & Environment, 2024)

Norfloxacin affects inorganic nitrogen compound transformation in tailwater containing Corbicula fluminea - Junling Wei; Zijin Hong; Wei Li; Xiufang Yang; Zihao Fu; Xinyu Chen; Junxiang Hu; Zhangnan Jin; Bojiang Long; Xuexiu Chang; Yu Qian (Journal of Hazardous Materials, 2024)

Coupled physicochemical dual-crosslinking Ti3C2T composite aerogels for the selective adsorption of gallium ions in acid fly ash leaching - Xiaopei Zhang; Weifeng Liu; Chang Liang; Dongju Fu; Meiling Wang; Xuguang Liu (Journal of Hazardous Materials, 2024)

Acesulfame potassium triggers inflammatory bowel disease via the inhibition of focal adhesion pathway - Zhaodong Zhai; Yibo Zhang; Xujing Liang; Jingsheng Li; Zhiqi Chen; Jianbin Zhang; WeiCai Li; Teng Wang; Qianyi He; Fu Li; Qilin Meng; Jieqiong Cao; et al. (Journal of Hazardous Materials, 2024)

Understanding iodine adsorption sites on monolithic N/O co-doped carbon fibers with scaffolding structure - Hongquan Fu; Yue Tang; Qiao Yuan; Jingming Chang; Fang Liao; Juan Zhang; Hejun Gao; Yi Yang; Yunwen Liao (Fuel, 2024)

Real-time PCR method based on single-copy nuclear DNA sequences for the quantitative detection of pork adulteration in processed beef products - Lijuan Chang; Ping Huang; Jikai Liu; Chengping Fu; Wenjuan Liu; Yongfeng Gao; Yuanhong Li; Yongling Liu; Ailin Long (Food Control, 2024)

Environmental risk assessment of coastal dredging based on clustering of meteocean forcing - Chang He; Francesco De Leo; Alessandro Stocchino; Zhen-Yu Yin; Ana J. Abascal; Yin-Fu Jin (Coastal Engineering, 2024)

Integrating spatially distributed data into Positive Matrix Factorization to identify the hotspots of local emission sources - Chun-Sheng Huang; Ho-Tang Liao; Chang-Fu Wu (Atmospheric Research, 2024)

Unveiling the distinctive traits of functional rye centromeres: minisatellites, retrotransposons, and R-loop formation - Chang Liu; Shulan Fu; Congyang Yi; Yang Liu; Yuhong Huang; Xianrui Guo; Kaibiao Zhang; Qian Liu; James A. Birchler; Fangpu Han (Science China Life Sciences, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Construction of 3D spinel binary metal oxide flower decorated 1D halloysite nanotube electrocatalyst for the selective detection of arsenic drug pollutant roxarsone - Thangavelu Sakthi Priya; Shen-Ming Chen; Yuan-Fu Chang (Applied Clay Science, 2024)

Photosynthetic performance and antioxidant activity of Gracilariopsis lemaneiformis are sensitive to phosphorus deficiency in elevated temperatures - Di Zhang; Jia-Zhen Sun; Ming-Hui Fu; Chang-Jun Li (Frontiers in Marine Science, 2024)
Due to anthropogenic input of nutrients and emissions of greenhouse gases, macroalgae inhabiting coastal areas often experience drastic fluctuations in nutrients and seawater warming. In this work, we investigated the photosynthetic performance and antioxidant response of the commercially important red macroalgae Gracilariopsis lemaneiformis under four different nutrient conditions at 20°C and 23°C. Our results showed that the enrichment of NO 3 - and PO 4 3- (high concentrations of nitrogen (N) and phosphorus (P), denoted as HNHP) significantly enhanced photosynthesis and growth by up to 42% and 66% for net photosynthesis rate and 83% and 134% for relative growth rate (RGR) under 20°C and 23°C, respectively, compared with natural seawater (low concentrations of N and P, denoted as LNLP). However, enriching only with PO 4 3- (low concentration of N and high concentration of P, denoted as LNHP) or NO 3 - (high concentration of N and low concentration of P, denoted as HNLP) brought no significant change in RGR. A two-way ANOVA analysis revealed an interaction between nutrient variations and temperature, with elevated temperature intensifying the inhibition observed under HNLP conditions. To further elucidate this interaction, we assessed the damage and recovery processes of the photosynthetic apparatus, along with the antioxidant activities. The increased damage ( k ) and reduced recovery ( r ) rates of photosystem II (PSII) in both LNLP and HNLP conditions indicated a heightened susceptibility to photoinhibition in G. lemaneiformis , leading to reactive oxygen species (ROS) accumulation and exacerbated oxidative stress, culminating in decreased photosynthesis and growth rates. At higher temperatures, these phosphorus deficiency-induced inhibitions were amplified, as evidenced by increases in k values and ROS contents, coupled with a decrease in r values. In summary, our data suggest that the photosynthetic performance and growth of G. lemaneiformis are vulnerable to phosphorus deficiency, particularly in the context of future ocean warming. Consequently, phosphorus fertilization during cultivation warrants more attention.

Highly alkaline electrokinetic extraction: Characteristics of chromium mobilization, conversion and transport in high alkalinity soil - Junnian Wu; Changze Wang; Zihuang Lin; Naichen Li; Yupeng Fu; Jiang Li; Chang Chen; Yinliu Li (Chemosphere, 2024)

Temporal variation of mercury and methyl mercury in water and accumulation by phytoplankton in the eutrophic estuary, northern Taiwan - Tien Hsi Fang; Fu Wei Chang (Marine Pollution Bulletin, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Transparent and open-source aluminum life cycle inventory dataset for China - Jinliang Xie; Yuzhen Feng; Huimin Chang; Changqing Xu; Ruoxi Xiong; Zimeng Cai; Chenling Fu; Ziqian Xia; Jing Guo; Nan Li (Resources, Conservation and Recycling, 2024)

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

Photocatalytic reduction of carbon dioxide by BiTeX (X = Cl, Br, I) under visible-light irradiation - Yu-Yun Lin; Fu-Yu Liu; I-Chia Chen; Hwei-Yan Tsai; Jhen-Wei Huang; Jia-Hao Lin; Chiing-Chang Chen (Journal of Environmental Management, 2024)

Degradation behaviors of Nabumetone and its metabolite during UV/monochloramine process: Experimental and theoretical study - Xiang Tu; Yunsong Bai; Qing Fu; Sheng Chang; Kunfeng Zhang; Yang Pan; Ruiyang Xiao; Yifu Fu; Qi Zhang (Journal of Environmental Sciences, 2024)

The role of a novel secretory peptidoglycan recognition protein with antibacterial ability from the Chinese Oak Silkworm Antheraea pernyi in humoral immunity - Xutong Duan; Ting Fu; Chang Liu; Fuhui Wang; Chengbao Liu; Lin Zhao; JinZhu Yu; Xialu Wang; Rong Zhang (Insect Biochemistry and Molecular Biology, 2024)

Antimicrobial mechanism of morusin against Bacillus cereus and its potential as an antimicrobial agent - Sichen Liao; Guoli Gong; Jiapeng Fu; Jie Wang; Qi Qi; Lemei Hu; Chang Gao; Minmin Wang; Haoyue Cui; Jiaqiang Liu; Lu Tian (Food Bioscience, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

Thermal History of Cambrian Burgess Shale-Type Deposits: New Insights from the Early Cambrian Chengjiang and Qingjiang Fossils of South China - Yuheng Qiao; Linhao Cui; Guangyuan Xing; Dongjing Fu; Chao Chang; Robert Gaines; Xingliang Zhang (Journal of Earth Science, 2024)

Assessing the impact of rainfall on water quality in a coastal urban river utilizing the environmental fluid dynamics code - Qingqing Sun; Suyun Chang; Jingfu Wang; Jing-An Chen; Caiqing Qin; Weiwei Shi; Wen-Xi Zhang; Yutong Zhang; Fu-Jun Yue; Si-Liang Li (Urban Climate, 2024)

Risk assessment of e-waste - Liquid Crystal Monomers re-suspension caused by coastal dredging operations - Chang He; Alessandro Stocchino; Yuhe He; Kenneth Mei Yee Leung; Francesco De Leo; Zhen-Yu Yin; Yin-Fu Jin (Science of The Total Environment, 2024)

Plastid engineering with an efficient RNAi delivery system based on bacteriophage MS2 virus-like particles enhances plant resistance to cotton bollworm - Chunmei Jiang; Jinqiu Fu; Fujun Li; Kai Xia; Shengchun Li; Ling Chang; Ralph Bock; Jiang Zhang (Molecular Plant, 2024)

A novel AI-based model for real-time flooding image recognition using super-resolution generative adversarial network - Yuan-Fu Zeng; Ming-Jui Chang; Gwo-Fong Lin (Journal of Hydrology, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Carbon-in-carbon: Hybrid carbonized nanomaterials with multifunctional activities for the treatment of endophthalmitis - Hong-Jyuan Jian; Yi-Ru Chiou; Anisha Anand; Chien-Fu Chen; David Hui-Kang Ma; Jui-Yang Lai; Chih-Ching Huang; Huan-Tsung Chang (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Extracellular histones promote TWIK2-dependent potassium efflux and associated NLRP3 activation in alveolar macrophages during sepsis-induced lung injury - Jing Yu; Yu Fu; Nan Zhang; Jiameng Gao; Zhiyuan Zhang; Xuemei Jiang; Chang Chen; Zongmei Wen (Inflammation Research, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

RETRACTED: Effect of calcium and phosphorus on ammonium and nitrate nitrogen adsorption onto iron (hydr)oxides surfaces: CD-MUSIC model and DFT computation - Mengke Jia; Jie Ma; Qiongqiong Zhou; Lijie Liu; Xiaolei Jie; Hongen Liu; Shiyu Qin; Chang Li; Fuqing Sui; Haichao Fu; Haijiao Xie; Long Wang; et al. (Chemosphere, 2024)

Enhancing machine learning-based age estimation for Pacific bluefin tuna: An approach with data imputation and image augmentation strategies - Tsung-Hsiang Ma; Yi-Jay Chang; Jen-Chieh Shiao; Chien-Bang Jin; Yan-Fu Kuo (Fisheries Research, 2024)

Slip-line solution to seismic active earth pressure of narrow c-φ soils on gravity walls rotating about the bottom - Fu-quan Chen; Chang Chen; Wu-zhen Kang; Li Xu; Xi-bin Li (Soil Dynamics and Earthquake Engineering, 2024)

Distinct effects of canopy vs understory and organic vs inorganic N deposition on root resource acquisition strategies of subtropical Moso bamboo plants - Lin Wang; Baogang Zhang; Yunying Fang; Huajun Yin; Shenglei Fu; Scott X. Chang; Yanjiang Cai (Science of The Total Environment, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Construction of AgI/PCN-224 Z-scheme heterojunction for efficient photocatalytic degradation of tetracycline hydrochloride: Pathways, mechanism and theoretical calculations - Jia-Chang Lu; Xue-Lu Bai; Qing-Yun Zhao; Bing-Bing Lu; Ying Fu (Journal of Cleaner Production, 2024)

Clean and efficient preparation of metallic bismuth from methane-sulfonate electrolyte in the membrane electrolysis cell - Cong Chang; Shenghai Yang; Jie Dai; Jun Li; Caiping Fu; Jingtao Cui; Weizhi Zeng; Hong Liu; Jiaqi Qi; Wei Jin; Yongming Chen (Journal of Environmental Chemical Engineering, 2024)

Optimizing BP neural network algorithm for Pericarpium Citri Reticulatae (Chenpi) origin traceability based on computer vision and ultra-fast gas-phase electronic nose data fusion - Peng Chen; Rao Fu; Yabo Shi; Chang Liu; Chenlu Yang; Yong Su; Tulin Lu; Peina Zhou; Weitong He; Qiaosheng Guo; Chenghao Fei (Food Chemistry, 2024)

Recrystallized resistant starch by encapsulation with konjac glucomannan: Structural changes, digestibility, and its effect on glucose response and short-term satiety in mice - Ranran Chang; Zihang Wang; Lili Fu; Chuanjing Chen; Kunjie Xu; Aiguo Ma; Yaoqi Tian (Food Chemistry, 2024)

An intelligent indicating label using mulberry pigment, polylactic acid and rutile TiO2 nanoparticle for monitoring the freshness of cold fresh pork - Huxuan Wang; Jing Dong; Xuanzhi Wang; Jiaxuan Fu; Tiantian Zhao; Yanan Zhu; Dawei Chang; Yungang Cao (Food Bioscience, 2024)

Assessing the inundation risk of cultural heritages along the southwestern coast of Taiwan: present and future - Wen-Ray Su; Yu-Hua Chen; Huei-Shuin Fu; Tzu-Yin Chang; Wei-Bo Chen (Regional Environmental Change, 2024)

Functional responses of two species of predatory mites (Acari: Phytoseiidae) to eggs and first-instar nymphs of Bactericera Gobica Logniova (Homoptera: Psyllidae) - XiaoTong Fu; YuanZhi Cao; XinTong Dong; Jing Chang; ZhiJia Huo; RuiXia Meng (Experimental and Applied Acarology, 2024)

Effects of fuel and driving conditions on particle number emissions of China-VI gasoline vehicles: based on corrections to test results - Xiaohan Miao; Xin Zhang; Chang Wang; Jingyuan Li; Jie Zhao; Liang Qu; Yu Liu; Songbo Qi; Honglin Li; Mengqi Fu; Taosheng Jin (Environmental Monitoring and Assessment, 2024)

Increases in extreme precipitation expected in Northeast China under continued global warming - Zhijie Xie; Yuanyuan Fu; Hong S. He; Shaoqiang Wang; Lunche Wang; Chang Liu (Climate Dynamics, 2024)

Greenhouse gas emissions and their driving factors among different flowering Chinese cabbage (Brassica campestris L.) varieties - Yongzhou Hao; Jing Li; Zhen Li; Yutao Peng; Shahid Hussain; Tianhong Fu; Hongzhao Li; Jingjing Chang; Lei Chen; Baige Zhang (Environmental Science and Pollution Research, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Natural versus artificial seawater: Impacts on antioxidant capacity, muscle quality and gut microbiota of Acanthopagrus schlegelii during temporary rearing - Yunyun Pan; Chang Liu; Yawen Hong; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture, 2024)

Assessment of the stabilization effect of ferrous sulfate for arsenic-contaminated soils based on chemical extraction methods and in vitro methods: Methodological differences and linkages - Ziqi Geng; Pengfei Wang; Naiyi Yin; Xiaolin Cai; Yaqi Fu; Chuanfang Fan; Xuhui Chang; Yunpeng Li; Jingnan Ma; Yanshan Cui; Peter E. Holm (Science of The Total Environment, 2024)

Novel method for identifying the heaviest QED atom - Jing-Hang Fu; Sen Jia; Xing-Yu Zhou; Yu-Jie Zhang; Cheng-Ping Shen; Chang-Zheng Yuan (Science Bulletin, 2024)

The Cambrian microfossil Qingjiangonema reveals the co-evolution of sulfate-reducing bacteria and the oxygenation of Earth’s surface - Linhao Cui; Kelei Zhu; Ruiyun Li; Chao Chang; Laiyuan Wu; Wei Liu; Dongjing Fu; Peiyu Liu; Hao Qiu; Guoqiang Tang; Qiuli Li; Robert R. Gaines; et al. (Science Bulletin, 2024)

Interlayer manipulation of bio-inspired Ti3C2Tx nanocontainer through intercalation of amino acid molecules to dramatically boosting uranyl hijacking capability from seawater - Chang Liu; Ye Li; Miao Lei; Dongxue Liu; Bolin Li; Chengbin Fu; Junpeng Guo (Journal of Hazardous Materials, 2024)

Heavy metals in centralized drinking water sources of the Yangtze River: A comprehensive study from a basin-wide perspective - Kunfeng Zhang; Sheng Chang; Xiang Tu; Enrui Wang; Yanling Yu; Jianli Liu; Lu Wang; Qing Fu (Journal of Hazardous Materials, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Improving prediction of N2O emissions during composting using model-agnostic meta-learning - Shuai Shi; Jiaxin Bao; Zhiheng Guo; Yue Han; Yonghui Xu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Nana Jiang; Lei Sun; Xinda Liu; Wanying Liu; Nuo Chang; et al. (Science of The Total Environment, 2024)

Heat storage and release characteristics of a prototype CaCO3/CaO thermochemical energy storage system based on a novel fluidized bed solar reactor - Fuliang Nie; Tianzeng Ma; Qiangqiang Zhang; Zheshao Chang; Ting Ren; Khurshida F. Sayfieva; Mingkai Fu; Xin Li (Journal of Cleaner Production, 2024)

Existing levels of biodiversity and river location may determine changes from small hydropower developments - Qingyi Luo; Shuyin Li; Tsuyoshi Kinouchi; Naicheng Wu; Xiaocheng Fu; Chang Ling; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Journal of Environmental Management, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Sea urchin-like nitrogen doped hierarchically carbon materials derived from bimetallic-MOF for fast and efficient hydrogen production of formic acid - Jiachao Duan; Qiqi Liang; Yan Fu; Jie Chang (Fuel, 2024)

The effect of electron beam irradiation combined with slurry ice on physicochemical parameters and bacterial communities of shrimp (Litopenaeus vannamei) during refrigerated storage - Chang Liu; Yunyun Pan; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Control, 2024)

Identifying sensitive precursors of ozone formation using photochemical indicators and transition values comprised by continuous automatic monitoring data - Chang-You Tsai; Tu-Fu Chen; Ken-Hui Chang (Atmospheric Environment, 2024)

Development and Application of an Industrial Wastewater Profile Database - Pei-Yuan Hsieh; Gen-Shuh Wang; Wen-Huey Mi; Chun-Sheng Huang; Chang-Fu Wu (Water, Air, & Soil Pollution, 2024)

Hierarchically porous magnetic biochar as an amendment for wheat (Triticum aestivum L.) cultivation in alkaline Cd-contaminated soils: Impacts on plant growth, soil properties and microbiota - Haichao Fu; Shuanglong Ma; Long Wang; Weijie Xue; Shiwu Xiong; Fuqing Sui; Hongen Liu; Chang Li; Guangxin Li; Ran Duan; Peng Zhao (Chemosphere, 2024)

Study on mechanical characteristics of pipe umbrella support in shallow buried tunnels - Yun-Han Wu; Chang-Jin Xiao; Fu-Quan Chen; Gang Cai (Tunnelling and Underground Space Technology, 2024)

Hedscandines A-C, three undescribed indole alkaloids from Hedyotis scandens with their anti-MRSA activity - Yu-Jun Wang; Xue Chen; Yong Yin; Wei Zhou; Pei-Fu Zhou; Ling-Gao Zeng; Chang-Hua Hu; Guo-Ping Yin (Phytochemistry, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Effects of Flammulina velutipes polysaccharide with ice recrystallization inhibition activity on the quality of beef patties during freeze-thaw cycles: An emphasis on water status and distribution - Yin Fu; Yan Cao; Zhongyi Chang; Chunjing Zou; Deming Jiang; Hongliang Gao; Caifeng Jia (Meat Science, 2024)

Role of keystone drives polycyclic aromatic hydrocarbons degradation and humification especially combined with aged contaminated soil in co-composting - Jiayue Huang; Ziwei Jiang; Anyang Li; Fangzhi Jiang; Pengfei Tang; Jizhe Cui; Wenxuan Feng; Chang Fu; Qian Lu (Journal of Environmental Management, 2024)

Photocurable 3D-printed AgNPs/Graphene/Polymer nanocomposites with high flexibility and stretchability for ECG and EMG smart clothing - Jia-Wun Li; Ho-Fu Chen; Yu-Zhe Liu; Jui-Hsin Wang; Ming-Chang Lu; Chih-Wei Chiu (Chemical Engineering Journal, 2024)

Revealing the role of CCoAOMT1: fine-tuning bHLH transcription factors for optimal anther development - Zesen Lai; Jianzheng Wang; Ying Fu; Menghan Wang; Hong Ma; Shiqing Peng; Fang Chang (Science China Life Sciences, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Fish community composition detected using traditional fishing and eDNA in Dianchi Lake, Southwest China - Kai Zhang; Zhiqiang Xia; Zijin Hong; Zihao Fu; Qiuhan Li; Xuexiu Chang; Guangjie Chen; Hugh J. MacIsaac (Hydrobiologia, 2024)

Chimeric proteins of Mycoplasma hyopneumoniae as vaccine and preclinical model for immunological evaluation - Marcus Rebouças Santos; Leonardo Teófilo Toledo; Ênio José Bassi; Wagnner José Nascimento Porto; Gustavo Costa Bressan; Maria Aparecida S. Moreira; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2024)

Vertical variation of source-apportioned PM2.5 and selected volatile organic compounds near an elevated expressway in an urban area - Ho-Tang Liao; Chien-Mei Yen; Yu-Rui Chen; Jyun-De Wu; Shih-Wei Tsai; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Age Prediction Using Resting-State Functional MRI - Jose Ramon Chang; Zai-Fu Yao; Shulan Hsieh; Torbjörn E. M. Nordling (Neuroinformatics, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Activation or inhibition of NF-κB from the juvenile stage results in skewed sex ratios in common carp (Cyprinus carpio L.) - Lili Chen; Songtao Wang; Xiangyu Duan; Xiaonan Cao; Songyun Wang; Mengxiao Fu; Yingxin Fan; Yongfang Jia; Qiyan Du; Zhongjie Chang (Aquaculture, 2024)

Integrated transcriptomic, proteomic, and metabolomic approaches reveal the antifungal mechanism of methyl ferulate against Alternaria alternate - Hui Kong; Shuai Ge; Xia Chang; Saiqing Xu; Haishan Xu; Xincheng Fu; Rongrong Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Real-time spatiotemporal forecast of natural gas jet fire from offshore platform by using deep probability learning - Weikang Xie; Xiaoning Zhang; Jihao Shi; Xinyan Huang; Yuanjiang Chang; Asif Sohail Usmani; Fu Xiao; Guoming Chen (Ocean Engineering, 2024)

Nutrient recovery and pollutant removal using carboxymethyl cellulose/microfibrillated cellulose hydrogel: Templating effects of CaCO3 nanoparticles - Jialin Fu; Choe Peng Leo; Chun Kiat Chang (Journal of Water Process Engineering, 2024)

Carbonate clumped isotopes and blocking temperatures of marbles from the Backbone Range, Taiwan - Amzad Hussain Laskar; Tzen-Fu Yui; Mao-Chang Liang (Journal of Asian Earth Sciences, 2024)

Study on remediation of chromium contaminated soil by an improved electrokinetic extraction device with auxiliary liquid chamber - Junnian Wu; Zihuang Lin; Changze Wang; Yupeng Fu; Jiang Li; Yinliu Li; Chang Chen (Chemical Engineering Journal, 2024)

Process development and techno-economic analysis for mechanochemical recycling of poly(ethylene terephthalate) - Elisavet Anglou; Arvind Ganesan; Yuchen Chang; Kinga M. Gołąbek; Qiang Fu; William Bradley; Christopher W. Jones; Carsten Sievers; Sankar Nair; Fani Boukouvala (Chemical Engineering Journal, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Inter-relationships of obesity-related eating behavior with depression and anxiety among adults during the COVID-19 pandemic: A network analysis - Xue Wang; Yibo Wu; Li Fu; Xiao Fu; Chang Pang; Shuang Zang (Appetite, 2024)

Investigation on pyrolysis mechanism and emission characteristics of CO2, NOx and SO2 during co-pyrolysis of coal gangue and sodium alginate/sodium carboxymethylcellulose/chitosan/guar gum - Benkang Zhu; Xianshu Dong; Yuping Fan; Xiaomin Ma; Yuanpeng Fu; Ming Chang; Hongfei Xue (Fuel, 2024)

Achieving tunable time-dependent delayed emission color via dynamic competition between the matrix and carbon dots for anti-counterfeiting and multidimensional encryption - Yufeng Chang; Nian Fu; Mingjun Chen; You Zhang; Fuxing Li; Zhenyang Liu; Fenghe Wang; Gang Yue; Xu Li; Li Guan (Chemical Engineering Journal, 2024)

Electric field-assisted aerobic co-composting of chicken manure and kitchen waste: Ammonia mitigation and maturation enhancement - Chang Shen; Huayuan Shangguan; Tao Fu; Huan Mi; Hao Lin; Lingyan Huang; Jiahuan Tang (Bioresource Technology, 2024)

Response of the F2-peak electron density and height to plasma depletion bays in the equatorial nighttime ionosphere observed by FORMOSAT-7/COSMIC-2 - Fu-Yuan Chang; Jann-Yenq. Liu; Panthalingal-Krishnanunni Rajesh; Chi-Yen. Lin (Advances in Space Research, 2024)

Interaction of Typhoon-Driven Near-Inertial Waves with an Anticyclone in the Philippine Sea - Caue Lazaneo; Leif Thomas; Zoltan Szuts; Jesse Cusack; Kai-Fu Chang; Kipp Shearman (Oceanography, 2024)
The Philippine Sea in the western Pacific is a region with high mesoscale eddy kinetic energy that is buffeted by intense typhoons. Such typhoons generate strong near-inertial waves (NIWs), making this region ideal for studying interactions between typhoon-driven NIWs and mesoscale eddies. To study such interactions, a field campaign was conducted in the Philippine Sea that targeted an anticyclonic eddy after the passage of Super Typhoon Mawar. The study was part of the US Office of Naval Research Departmental Research Initiative ARCTERX (Island Arc Turbulent Eddy Regional Exchange). During the campaign, ship and float-based velocity measurements revealed layers of intense vertical shear oscillating at slightly sub-inertial frequencies in the anticyclone. The shear layers were stronger toward the eddy center and coincided with patches of elevated turbulence. An idealized numerical simulation initialized with a symmetric eddy modeled after observations and forced by reanalysis winds was used to study the formation of NIWs by Typhoon Mawar and their interactions with the eddy. The model captured the structure and vertical propagation of the observed shear layers and demonstrated how the dynamics of the NIWs in the anticyclone are consistent with NIW trapping following the theory of ζ-refraction. The simulated shear layers were not as intense as those that were observed and could not explain the patches of enhanced turbulence. Processes not included in the model, more specifically the internal tides that are particularly strong in the Philippine Sea, likely contribute to the discrepancy. Energy exchange between the NIWs and the anticyclone diagnosed using the model output was weak, suggesting that typhoon-driven NIWs play a secondary role in the energetics of eddies in the Philippine Sea, or that the idealized nature of the model limited wave-mean flow energy exchange.

Exploring the relative importance of preseason climatic drivers on spring phenology dynamics in the Greater Khingan Mountains, Northeast China - Yuanyuan Fu; Chang Liu; Hong S. He; Shaoqiang Wang; Lunche Wang; Zhijie Xie (International Journal of Climatology, 2023)
Exploring spring phenology dynamics driven by climate change is crucial for investigating land–climate feedback. However, a thorough assessment of the influence of climatic drivers on spring phenology remains lacking. Here, we investigated spatiotemporal variations at the start of the growing season (SOS) in the Greater Khingan Mountains, Northeast China, during 1982–2015 using the normalized difference vegetation index third‐generation dataset from Global Inventory Modelling and Mapping Studies. To investigate the influence of preseason climatic factors on the SOS, partial correlation analysis was employed to assess correlations as well as to identify dominant regional drivers. Overall, the SOS dates in the study area showed obvious regional characteristics from 1982 to 2015, with a gradual delay from north to south, with more than 90% of the SOS dates occurring from Julian days 125–140. Advancement trends were observed in all ecogeographical regions, thus accounting for 94.6% of the entire research area, with an average of 7.14 days in advance. The partial correlation analysis revealed spring phenology was most significantly influenced by preseason temperature, and temperature promoted the advancement of SOS in almost the entire study area, but for semi‐humid/semi‐arid regions, the effects of total precipitation was greatest. Interestingly, preseason radiation also dominated earlier SOS dates by a few pixels, albeit in a fragmented distribution. Generally, the preseason temperature had a prominent influence on the SOS dates across all ecogeographical regions, whereas the roles of preseason precipitation and radiation varied by region. In addition to analysing a single climatic factor, our study aimed to analyse the comprehensive impacts of climatic factors on spring phenological processes, with a focus on the composite effects, helping us to improve predictions of spring phenology and provide a better understanding of land–climate interactions.

Classification of five SARS-CoV-2 serotypes based on RBD antigenicities - Shixiong Hu; Chunli Wu; Xinkai Wu; Xuehui Ma; Chang Shu; Qian Chen; Anqi Zheng; Huiting Yang; Jian Lu; Pei Du; George Fu Gao; Qihui Wang (Science Bulletin, 2023)

Subduction of solidifying melt lens beneath ultraslow-spreading ridges revealed by (Grt-)amphibolites and dolerites in the Xiugugabu ophiolitic mélange, southwestern Tibet - Chang Zhang; Chuan-Zhou Liu; Wen-Bin Ji; Tong Liu; Zhen-Yu Zhang; Fu-Yuan Wu (Lithos, 2023)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Multifunctional 0D@2D (Mox-Mn)Sy-NPs@MXene hybrid electrode with high rate-capability and ultra-long cycling life for Li-ion battery and all Molybdenum-MXene-based 1.9 (V) asymmetric supercapacitor - Ghuzanfar Saeed; Asrar Alam; Shufeng Bo; Jun Su; Min Chang Kim; Liguo Zhang; Youngjoong Choi; Shrikant Sadavar; Hao Fu; Ho Seok Park; Kwang Ho Kim (Chemical Engineering Journal, 2023)

Thiocarbonyl fluoride generated in situ from difluorocarbene for cyclization of vicinal X-H substituted amines (X = N, O or S) - Jia-Lu Hu; Mu-Xian Fu; Ji-Chang Xiao; Jin-Hong Lin (Journal of Fluorine Chemistry, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Corrigendum to “In-situ self-assembled vaccine constructed with dual switchable nanotransformer for tumor immunotherapy” [Chem. Eng. J. 454 (2023) 140190] - Zipeng Zhang; Shuang Liang; Shunli Fu; Tong Gao; Weiwei Mu; Lili Chang; Shujun Liu; Yongjun Liu; Na Zhang (Chemical Engineering Journal, 2023)

Enterochromaffin Cell: Friend or Foe for Human Health? - Yang Yu; Yong-Chang Li; Fu-Chao Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2023)

Development and testing of a ground recognition system for tractor field operations - Chang-kai Wen; Hong-wei Wang; Chang-hai Luo; Wei-qiang Fu; Qing-zhen Zhu; Yan-xin Yin; Zhi-jun Meng (Computers and Electronics in Agriculture, 2023)

Machine learning strategy on activation energy of environmental heterogeneous reactions and its application to atmospheric formation of typical montmorillonite-bound phenoxy radicals - Wenxiao Pan; Jiamin Chang; Shuming He; Xian Liu; Jianjie Fu; Aiqian Zhang (Science of The Total Environment, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Aristolochic alkaloids from Piper macropodum and their anti-inflammatory activities - Chun-Yue Liu; Yong-Fu Lu; Si-Xuan Liu; Yong-Fu Li; Yan Dong; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2023)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

The epigenetic regulator Set9 harmonizes fungal development, secondary metabolism, and colonization capacity of Aspergillus flavus - Ling Hao; Mengjuan Zhang; Chi Yang; Xiaohua Pan; Dandan Wu; Hong Lin; Dongmei Ma; Yanfang Yao; Wangzhuo Fu; Jiarui Chang; Yanling Yang; Zhenhong Zhuang (International Journal of Food Microbiology, 2023)

General strategy for embedding metallic element, multi-metal or metal alloy nanoparticles into ordered mesoporous carbons via alcohol-soluble humins - Junyan Fu; Chang Chen; Richard Lee Smith; Xinhua Qi (Chemical Engineering Journal, 2023)

Mapping the gene of a maize leaf senescence mutant and understanding the senescence pathways by expression analysis - Yong Gao; Xia Shi; Yongyuan Chang; Yingbo Li; Xuehang Xiong; Hongmei Liu; Mengyuan Li; Weihua Li; Xuehai Zhang; Zhiyuan Fu; Yadong Xue; Jihua Tang (Plant Cell Reports, 2023)

Developmental toxicity of black phosphorus quantum dots in zebrafish (Danio rerio) embryos - Xiaonan Cao; Mengxiao Fu; Qiyan Du; Zhongjie Chang (Chemosphere, 2023)

Biomonitoring trace metal contamination in Guangzhou urban parks using Asian tramp snails (Bradybaena similaris) - Liqin Wu; Yexi Liang; Yi'an Chen; Shanming Fu; Yuanjun Huang; Zhenxin Chen; Xiangyang Chang (Chemosphere, 2023)

Influence of acid rain climate environment on deterioration of shear strength parameters of natural residual expansive soil - Jin Chang; Yong-Fu Xu; Jie Xiao; Lei Wang; Jian-Qing Jiang; Jian-Xiong Guo (Transportation Geotechnics, 2023)

Kinetin inhibits hepatic stellate cell activation and induces apoptosis via interactions with the TGF-β1/Smad signaling pathway - Fu-chang Jin; Jing-jing Chen; Qiu-xian Xu; Ming-Hui Zhou; Yi Lin; Qi-wei Zhang; Chang-chun Zhang; Zhen-gang Zhang (Toxicology and Applied Pharmacology, 2023)

Spatial distribution of heavy metal contaminants: The effects of water-sediment regulation in the Henan section of the Yellow River - Songtao Liu; Furong Yu; Tao Lang; Yuekun Ji; Yu Fu; Jianuo Zhang; Chang Ge (Science of The Total Environment, 2023)

Soil development following glacier retreat shapes metagenomic and metabolomic functioning associated with asynchronous C and N accumulation - Yu Huang; Wei Shi; Qi Fu; Yingbo Qiu; Jiayi Zhao; Jiaxin Li; Qian Lyu; Xian Yang; Jia Xiong; Wenzhi Wang; Ruiying Chang; Zhiyuan Yao; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Exploration of potential driving mechanisms of Comamonas testosteroni in polycyclic aromatic hydrocarbons degradation and remodelled bacterial community during co-composting - Fangzhi Jiang; Ziwei Jiang; Jiayue Huang; Pengfei Tang; Jizhe Cui; Wenxuan Feng; Chunjing Yu; Chang Fu; Qian Lu (Journal of Hazardous Materials, 2023)

Laboratory tidal microcosm deciphers responses of sediment archaeal and bacterial communities to microplastic exposure - Chang Fang; Yinglin He; Yuting Yang; Bing Fu; Sentao Pan; Fang Jiao; Jun Wang; Huirong Yang (Journal of Hazardous Materials, 2023)

Gellan gum-based functional films integrated with bacterial cellulose and nano-TiO2/CuO improve the shelf life of fresh-cut pepper - Fei Chen; Xia Chang; Haishan Xu; Xincheng Fu; Shenghua Ding; Rongrong Wang (Food Packaging and Shelf Life, 2023)

Revolutionizing wound healing: Ultrashort pulse electric fields in seconds for highly aligned extracellular matrix and efficient cell migration - Xiao-Wei Xiang; Hao-Tian Liu; Wei Liu; Ze-Yao Yan; Yu-Lian Zeng; Ya-Jun Wang; Jing Liu; Yu-Chen Chen; Sai-Xi Yu; Cai-Hui Zhu; Xiao-Nan Tao; Chen Wang; et al. (Chemical Engineering Journal, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

Rapid adaptive evolution of Bacillus coagulans to undetoxified corncob hydrolysates for lactic acid production and new insights into its high phenolic degradation - Jiaming Fu; Zijie Wang; Hongcheng Miao; Chang Yu; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2023)

Condensation retardation performance of metal-organic framework-based composite humidity-control materials in a radiation cooling room - Huibo Zhang; Lin Fu; Xinxin Wang; Jiang Chang (Building and Environment, 2023)

Nighttime wavenumber-four and plasma depletion bays observed by FORMOSAT-5/AIP, ICON/IVM, and COSMIC-2/RO data - Jann-Yenq Liu; Kai-Wen Kan; Chi-Kuang Chao; Fu-Yuan Chang (Advances in Space Research, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Measuring the route topography impact on real driving emissions based on neural network models - Hualong Xu; Li Zhang; Hong Chang; Jinlin Han; Dongmei Wu; Xiangkun Gong; Mingming Fu (Environmental Research, 2023)

Engineered active pure water with reduced hydrogen bonds catalyzes itself in green energy production of oxygen and hydrogen evolution reactions - Shih-Hao Yu; Chun-Chao Chang; Fu-Der Mai; Hui-Yen Tsai; Yu-Chuan Liu (Chemical Engineering Journal, 2023)

Coupling multifactor dominated the biochemical response and the alterations of intestinal microflora of earthworm Pheretima guillelmi due to typical herbicides - Xingping Chang; Furong Fu; Yang Sun; Lixia Zhao; Xiaojing Li; Yongtao Li (Environmental Science and Pollution Research, 2023)

Spatio-temporal variation and hazard assessment of potentially toxic metal element contamination in sediments and water before and after a water-level fluctuation cycle in the Three Gorges Reservoir, Wanzhou, China - Chang Liu; Qiaojuan Lan; Bin Yan; Jueqiao Wang; Huan Wang; Yan Wu; Chuan Fu; Yinhai Zhong; Chao Li; Shenglei Li (Environmental Monitoring and Assessment, 2023)

Generation of ultraslow-spreading oceanic crust traced by various mafic blocks from ophiolitic mélange in the Xigaze Ophiolites, southern Tibet - Chang Zhang; Chuan-Zhou Liu; Tong Liu; Wen-Bin Ji; Fu-Yuan Wu (Contributions to Mineralogy and Petrology, 2023)

Heterogeneous mantle beneath the Neo-Tethys Ocean revealed by ultramafic rocks from the Xiugugabu Ophiolite in the Yarlung-Tsangpo Suture Zone, southwestern Tibet - Chang Zhang; Chuan-Zhou Liu; Antoine Bénard; Othmar Müntener; Wen-Bin Ji; Tong Liu; Zhen-Yu Zhang; Wei-Qi Zhang; Fu-Yuan Wu (Contributions to Mineralogy and Petrology, 2023)

Spatiotemporal characteristics and influencing factors of net primary production from 2000 to 2021 in China - Chen Yang; Guohui Zhai; Meichen Fu; Chang Sun (Environmental Science and Pollution Research, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Effects of ball milling on biochar adsorption of contaminants in water: A meta-analysis - Jean Damascene Harindintwali; Chao He; Leilei Xiang; Qingyuan Dou; Yu Liu; Mingyi Wang; Xin Wen; Yuhao Fu; Mahbub Ul Islam; Scott X. Chang; Stephan Kueppers; Sabry M. Shaheen; et al. (Science of The Total Environment, 2023)

Developmental defects and potential mechanisms in F1 generation of parents exposed to difenoconazole at different life stages of zebrafish (Danio rerio) - Yiming Chang; Huimin Fu; Haitao Yu; Liangang Mao; Lan Zhang; Yanning Zhang; Lizhen Zhu; Jin Yang; Xingang Liu; Hongyun Jiang (Science of The Total Environment, 2023)

Response spectra for transient pore-pressure in a sandy seabed under random waves: Frequency-filtering effect - Jia-Hao Yu; Fu-Ping Gao; Chang-Fei Li (Ocean Engineering, 2023)

In suit establishment of Ti3C2 MXenes exchanger via Na+, K+ and NH4+ intercalation: Exceptionally UO22+ loading capability and hijacking mechanism - Chang Liu; Ye Li; Dongxue Liu; Miao Lei; Bolin Li; Chengbin Fu; Jun Zhang (Chemical Engineering Journal, 2023)

Constructing of a stable Ti3C2 MXenes nano-traps with ultrahigh and selectively uranyl encapsulation capability by polyethyleneimine intercalation - Chang Liu; Ye Li; Dongxue Liu; Miao Lei; Bolin Li; Chengbin Fu; Jun Zhang (Chemical Engineering Journal, 2023)

Unique ion rectifier intermediate enabled by ultrathin vermiculite sheets for high-performance Zn metal anodes - Jianwen Li; Shuang Zhou; Xinyu Meng; Yining Chen; Chunyan Fu; Alireza Azizi; Xiaoguang Zhao; Weimin Xie; Zhi Chang; Anqiang Pan (Science Bulletin, 2023)

The additive interactions between high-molecular-weight glutenin subunits and tannic acid improve the wheat quality - Yanbin Guan; Yaqiong Wang; Chuang Pan; Li Li; Fu Shi; Yuesheng Wang; Mingjie Chen; Guangxiao Yang; Guangyuan He; Junli Chang; Yin Li (Food Research International, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Causes of the discordance in the south-north distribution of the 2017 Jiuzhaigou earthquake sequences - Zhi-Tong Jin; Jia-Lu Liu; Yong-Ge Wan; Shu-Zhong Sheng; Fu-Chang Wang; Xiao-Tao Zhang; Gan Feng (Applied Geophysics, 2023)

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Aspergillus sp. R3, a new producer for cyclopyazonic acid, inhibits rice sheath blight fungus Rhizoctonia solani Kühn - Xiangyu Qin; Yuanhang Chang; Yao Wang; Jie Yang; Siming Nie; Na Guo; Jian Xu; Fengkun Cai; Chunjian Zhao; Yujie Fu (Physiological and Molecular Plant Pathology, 2023)

Heavy metals in influent and effluent from 146 drinking water treatment plants across China: Occurrence, explanatory factors, probabilistic health risk, and removal efficiency - Kunfeng Zhang; Sheng Chang; Qi Zhang; Yunsong Bai; Enrui Wang; Moli Zhang; Qing Fu; Liangliang Wei; Yanling Yu (Journal of Hazardous Materials, 2023)

Transcriptomics and gas chromatography-mass spectrometry metabolomics reveal the mechanism of heat shock combined with 1-methylcyclopropene to regulate the cuticle wax of jujube fruit during storage - Shuai Ge; Rongrong Wang; Lvzhu Yang; Hui Kong; Xia Chang; Xincheng Fu; Yang Shan; Shenghua Ding (Food Chemistry, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A Novel Method of Combined Deep Hole Blasting for Gob-Side Roadway Protection - Jun Yang; Qiang Fu; Yubing Gao; Xing Wu; Xu Chang; Changjiang Li (Rock Mechanics and Rock Engineering, 2023)

Combined ecotoxicological effects of different-sized polyethylene microplastics and imidacloprid on the earthworms (Eisenia fetida) - Huimin Fu; Lizhen Zhu; Liangang Mao; Lan Zhang; Yanning Zhang; Yiming Chang; Xingang Liu; Hongyun Jiang (Science of The Total Environment, 2023)

PFO5DoDA disrupts hepatic homeostasis primarily through glucocorticoid signaling inhibition - Chang Wang; Huayu Fu; Jun Yang; Lei Liu; Fenghong Zhang; Chunyu Yang; Hongyuan Li; Jiamiao Chen; Qi Li; Xiaolin Wang; Yaorui Ye; Nan Sheng; et al. (Journal of Hazardous Materials, 2023)

Integrated effects of co-evolutions among climate, land use and vegetation growing dynamics to changes of runoff quantity and quality - Di Chang; Shuo Li; Zhengqing Lai; Fanjin Fu; Xinlong Qi (Journal of Environmental Management, 2023)

Modulating photothermal properties by integration of fined Fe–Co in confined carbon layer of SiO2 nanosphere for pollutant degradation and solar water evaporation - Rongrong Du; Hongyang Zhu; Hongyao Zhao; Hao Lu; Chang Dong; Mengting Liu; Fu Yang; Jun Yang; Jun Wang; Jianming Pan (Environmental Research, 2023)

Experimental analysis of sand-bearing muck blockages inside single circle earth pressure balance shield chambers - Chang Ji; Longlong Fu; Shunhua Zhou; Qiyu Yao; Chao He (Tunnelling and Underground Space Technology, 2023)

A linkage between early Silurian Nb-REE enriched alkaline magmatism and Neoproterozoic subduction metasomatized mantle in South Qinling, Central China - Jian-Hui Su; Xin-Fu Zhao; Xiao-Chun Li; Sheng-Ren Chang; Yuan-Bao Wu; Carl Spandler (Lithos, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Correction: Identification of extracellular vesicles from J strain and wild isolate of Mycoplasma hyopneumoniae - Luiz Fernando Lino de Souza; Glaziele Campbell; Guilherme Gabriel Souza Arthuso; Natália Fialho Gonzaga; Camilla Ribeiro Alexandrino; Viviane Sisdelli Assao; Maria Aparecida Scatamburlo Moreira; Maura Da Cunha; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2023)

SLIT3 knockdown inhibited TGF-β-induced hepatic stellate cells activation by down-regulating YAP signal - Xiling Fu; Jiabao Chang; Damin Jiao; Mengying Zhu; Yuqi Ma (Molecular & Cellular Toxicology, 2023)
Objective Liver fibrosis is a chronic liver disease caused by a variety of pathophysiological. However, there are no effective treatments to combat it. HSCs are a major source of fibrotic cells and exploring the mechanisms of HSC activation may provide new strategies for the treatment of liver fibrosis. Objectives To explore the role and underlying mechanism of SLIT3 in HSCs fibrosis. Results GSE163211 dataset analysis identified aberrant expression of SLIT3 in NASH F1-F4 tissues and SLIT3 expression level was positively correlated with fibrosis-related proteins. In vitro experiments showed that TGF-β induced upregulation of SLIT3 in LX-2 cells. Knockdown of SLIT3 significantly inhibited TGF-β-induced α-SMA, COL1A2, and COL1A1 expression, inhibited excessive cell proliferation and migration, and suppressed YAP activity. Conclusion Collectively, our findings suggest that SLIT3 deficiency alleviates TGF-β-induced HSCs activation by inhibiting YAP activity.

Integrated membrane electrochemical reactor-membrane distillation process for enhanced landfill leachate treatment - Zhongsen Yan; Zhengshi Zhu; Haiqing Chang; Gongduan Fan; Qiankun Wang; Xianzhi Fu; Fangshu Qu; Heng Liang (Water Research, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

The ester derivatives of ferulic acid exhibit strong inhibitory effect on the growth of Alternaria alternata in vitro and in vivo - Hui Kong; Xincheng Fu; Xia Chang; Zemin Ding; Yang Yu; Haishan Xu; Rongrong Wang; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2023)

Ultrasonication significantly enhances grafting efficiency of chitosan-ferulic acid conjugate and improves its film properties under Fenton system - Haishan Xu; Xincheng Fu; Hui Kong; Fei Chen; Xia Chang; Zemin Ding; Rongrong Wang; Yang Shan; Shenghua Ding (Food Research International, 2023)

In-situ self-assembled vaccine constructed with dual switchable nanotransformer for tumor immunotherapy - Zipeng Zhang; Shuang Liang; Shunli Fu; Tong Gao; Weiwei Mu; Lili Chang; Shujun Liu; Yongjun Liu; Na Zhang (Chemical Engineering Journal, 2023)

An interfacial gas-enrichment strategy for mitigating hydrate adhesion and blockage - Rui Ma; Senbo Xiao; Yuanhao Chang; Yuequn Fu; Jianying He; Zhiliang Zhang (Chemical Engineering Journal, 2023)

A novel ternary deep eutectic solvent pretreatment for the efficient separation and conversion of high-quality gutta-percha, value-added lignin and monosaccharide from Eucommia ulmoides seed shells - Cong-Jia Duan; Xu Han; Yuan-Hang Chang; Jian Xu; Gan-Lu Yue; Ying Zhang; Yu-Jie Fu (Bioresource Technology, 2023)

Environmental Factors Influence the Effects of Biochar on the Bioavailability of Cd and Pb in Soil Under Flooding Condition - Honghong Li; Zhou Li; Limei Huang; Xiaoming Mao; Yuxuan Dong; Shilong Fu; Rong Su; Yihan Chang; Chuan Zhang (Water, Air, & Soil Pollution, 2023)

An Efficient Protocol for Agrobacterium-Mediated Transformation and Regeneration of Sugar Beet (Beta vulgaris L.) based on Blade–Petiole Transition Zone Explants - Ziqiang Zhang; Huizhong Zhang; Liang Wang; Bizhou Zhang; Zengjuan Fu; Shangmin Zhao; E Yuanyuan; Wenzhe Zheng; Hui Zhang; Pingan Han; Wenjin Chen; Yue Chang; et al. (Sugar Tech, 2023)

Mesenchymal stem cells suppressed skin and lung inflammation and fibrosis in topoisomerase I-induced systemic sclerosis associated with lung disease mouse model - Nithya Ganesan; Yu-Di Chang; Shih-Chieh Hung; Joung-Liang Lan; Jiunn-Wang Liao; Shih Tsung Fu; Chen-Chen Lee (Cell and Tissue Research, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Pathology, Enzyme Activity and Immune Responses after Cryptocaryon irritans Infection of Golden Pompano Trachinotus ovatus (Linnaeus 1758) - Hua-Yang Guo; Wen-Fu Li; Ke-Cheng Zhu; Bao-Suo Liu; Nan Zhang; Bo Liu; Jing-Wen Yang; Dian-Chang Zhang (Journal of Marine Science and Engineering, 2023)
Golden pompano (Trachinotus ovatus) has become an economically important fish in China in the past decade. However, Cryptocaryon irritans, a parasitic ciliate, causes considerable economic losses in the mariculture of T. ovatus. To characterize the pathogenesis of C. irritans in T. ovatus, the pathological properties, immune-related enzyme activity and expression of the NEMO gene was analysed. The results from the histological sections showed that there was considerable metamorphosis and hyperplasia in the parasitized sites (skin) with leukocyte aggregation and mucous cell increases after C. irritans infection. Moreover, the activities of four enzymes, that is, alkaline phosphatase (AKP), acid phosphatase (ACP), superoxide dismutase (SOD) and lysozyme (LZM), were significantly increased in different tissues after C. irritans infection. Furthermore, the ORF of T. ovatus NF-kappa-B essential modulator (ToNEMO) measures 1650 bp, encoding 548 amino acids. The ToNEMO transcripts were universally expressed in all examined tissues, with higher levels being observed in the immune-relevant and central nervous tissues. The mRNA levels of ToNEMO after C. irritans infection were significantly increased in the gill, skin, liver, spleen and head kidney. These results suggested that ToNEMO might be involved in immune responses and helped to elucidate the physiological response after the C. irritans infection of fish.

Clostridium butyricum-fermented Chinese herbal medicine enhances the immunity by modulating the intestinal microflora of largemouth bass (Micropterus salmoides) - Xiaolin Meng; Huimin Cai; Heng Li; Fu You; Aixia Jiang; Wenpan Hu; Keke Li; Xindang Zhang; Yanmin Zhang; Xulu Chang; Guokun Yang; Zhigang Zhou (Aquaculture, 2023)

Insight into advanced oxidation processes for the degradation of fluoroquinolone antibiotics: Removal, mechanism, and influencing factors - Zonglin Li; Junsen Wang; Jiajun Chang; Bomin Fu; Hongtao Wang (Science of The Total Environment, 2023)

The distinct resistance mechanisms of cyanobacteria and green algae to sulfamethoxazole and its implications for environmental risk assessment - Yibo Zhang; Ming Li; Fang Chang; Malan Yi; Hongmei Ge; Jie Fu; Chenyuan Dang (Science of The Total Environment, 2023)

Nonclimacteric ripening characteristics of ‘Jen-Ju Bar’ guava conferred by a defect in the expression of the system-2 ACC synthase gene PgACS1 - Kuo-En Chen; You-Fu Liu; Yu-Chang Liu; Margo Sulistio; Chyi-Chuann Chen; Chun-Ta Wu (Postharvest Biology and Technology, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

Inulin reduces liver triacylglycerol by increasing lipid droplet lipolysis in fat-loaded mice - Bingbing Chen; Yumeng Shi; Kai Zhang; Yanzhong Chang; Pengcheng Fu; Pingsheng Liu; Shuyan Zhang (Food Research International, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

A new multi-identification system based on a poly(l-cysteine) sensor for simultaneous detection of multiple steroid hormones in serum - Xia Cui; Zhimin Luo; Miao Guo; Jiameng Xu; Lu Wang; Guoning Chen; Gege Wang; Chun Chang; Aiguo Zeng; Jia Zhang; Qiang Fu (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Combined nonlinear wave and current induced instantaneously-liquefied soil depth in a non-cohesive seabed - Li-Jing Yang; Fu-Ping Gao; Chang-fei Li (Coastal Engineering, 2023)

Grading patterning perovskite nanocrystal-polymer composite films for robust multilevel information encryption and decryption - Jiaxing Fu; Jingyun Feng; Bori Shi; Yongfeng Zhou; Chang Xue; Mengying Zhang; Yabing Qi; Weijia Wen; Jinbo Wu (Chemical Engineering Journal, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Metabarcoding reveals the differential sensitivity of planktonic microbiome to environmental filtering and biointeraction in Sansha Yongle blue hole - Tianying Chen; Yunyun Zhuang; Chang Chen; Xuewei Mao; Ruping Ge; Hongju Chen; Jianwei Chen; Liang Fu; Zuosheng Yang; Guangxing Liu (Frontiers in Marine Science, 2022)
The Sansha Yongle blue hole (SYBH) is the world’s deepest blue hole known so far and its unique hydrochemical characteristics make it a valuable site for studying biodiversity and ecological processes. Here, we used metabarcoding approach to investigate the diversity, assembly mechanism and co-occurrence pattern of planktonic microbiome in SYBH. Our results revealed the distinct separation of communities from upper oxic, middle oxic and suboxic-anoxic layer and significant day-night difference was detected in the upper-layer community of microeukaryotes, indicating potential diel migration. Stochastic processes played a significant role in the community assembly of microeukaryotes, while deterministic processes dominated in prokaryotes, confirming the stronger environmental filtering on prokaryotes as also suggested by the correlation with environmental variables. Microeukaryotes were less sensitive to environments but significantly affected by cross-domain biointeraction. When comparing the subcommunities of different abundance, we found that abundant taxa were widespread while rare taxa were habitat-specific. In co-occurrence network, over 87% of the interactions and 19 out of 20 keystone OTUs (Operational Taxonomic Units) were affiliated to moderate or rare taxa, suggesting the importance of non-abundant taxa in maintaining community stability. The predominant positive edges in the network pointed to that interspecies cooperation may be one of the ecological strategies in SYBH. Overall, we highlight the divergent assembly pattern and different driving forces in shaping plankton microbiome in SYBH, which may advance current understanding on diversity and dynamics of marine life in blue hole ecosystems.

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Physiological and transcriptomic responses to starvation in the corallivorous crown-of-thorn starfish - Litong Yang; Ying Zhang; Huizhen Chen; Qian Gao; Peng Luo; Jianxing Hu; Fanyu Zheng; Yunyu Yuan; Liang Fu; Chang Chen (Frontiers in Marine Science, 2022)
The outbreak of coral-eating Acanthaster spp., commonly known as the Crown-of-Thorn Starfish (CoTS), contributes to a significant proportion of coral loss in the tropical Indo-Pacific region. After the dramatic loss of coral due to their predation, CoTS is expected to face food shortages before coral recovers, which is usually accompanied by the sudden disappearance of its population. To reveal the response of CoTS to starvation stress, we conducted a four-month starvation experiment to investigate the physiological and molecular changes in the stomach tissue by combining the metabolites and enzyme activity measurements with transcriptome analysis. The results showed that the concentrations of primary metabolites and associated enzyme activities, as well as the amount of total antioxidant were not significantly altered between fed and starved CoTS in any case. However, starvation suppressed the expression of the genes involved in glycolysis and citrate cycle, development and movement, but enhanced that of the genes associated with sleep promotion, immunity, lysosome and glucose supply. This suggests that long-term starvation may induce CoTS to enter into a dormancy-like status characterized by reduced unnecessary physical activities for survival, accelerated recycling of nutrients, and enhanced immunity.

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Phosphorus fractionation and adsorption characteristics in drinking water reservoir inlet river sediments under human disturbance - Zihao Fu; Zijin Hong; Junling Wei; Yukai Liao; Songlin You; Yifan Wang; Jianjing Lv; Huan Feng; Marek Kolenčík; Xuexiu Chang; Yu Qian (Journal of Soils and Sediments, 2022)

Household solid fuel use with diabetes and fasting blood glucose levels among middle-aged and older adults in China - Yuxiong Chen; Siqin Feng; Zhen’ge Chang; Yakun Zhao; Jia Fu; Yijie Liu; Siqi Tang; Yitao Han; Yanbo Liu; Yuanxun Zhang; Shuyang Zhang; Zhongjie Fan (Environmental Science and Pollution Research, 2022)

Use of an Effective Variance Chemical Mass Balance Model for Source Apportionment of Metal Elements in a Polluted River - Pei-Yuan Hsieh; Chi-Chang Ho; Gen-Shuh Wang; Yuan-Cheng Hsu; Di-Wen Wang; Yu-Man Shang; Chang-Fu Wu (Environmental Processes, 2022)

Understorey light environment impacts on seedling establishment and growth in a typhoon-disturbed tropical forest - Kuo-Jung Chao; Yung-Chiau Lin; Guo-Zhang Michael Song; Chien-Hui Liao; Yau-Lun Kuo; Chang-Fu Hsieh; Eugene W. Schupp (Plant Ecology, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Establishment of a set of wheat-rye addition lines with resistance to stem rust - Chang Liu; Jing Wang; Shulan Fu; Long Wang; Hongwei Li; Mian Wang; Yuhong Huang; Qinghua Shi; Yonghong Zhou; Xianrui Guo; Congle Zhu; Jing Zhang; et al. (Theoretical and Applied Genetics, 2022)

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

Spatiotemporal variation in nitrogen and phosphorus levels and microbial community in the upstream water transport channel to the Douhe Reservoir - Yueting Fan; Qing Fu; Shusong Zhang; Moli Zhang; Sheng Chang; Shaoyan Zhao; Minling Wang (Environmental Science and Pollution Research, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Genome-wide transcriptome analysis and characterization of the cytochrome P450 flavonoid biosynthesis genes in pigeon pea (Cajanus cajan) - Jie Yang; Hongquan Li; Ruijin Ma; Yuanhang Chang; Xiangyu Qin; Jian Xu; Yujie Fu (Planta, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Identification of extracellular vesicles from J strain and wild isolate of Mycoplasma hyopneumoniae - Luiz Fernando Lino de Souza; Glaziele Campbell; Guilherme Gabriel Souza Arthuso; Natália Fialho Gonzaga; Camilla Ribeiro Alexandrino; Viviane Sisdelli Assao; Maria Aparecida Scatamburlo Moreira; Maura Da Cunha; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2022)

Effects of postnatal exposure to tetrabromobisphenol A on testis development in mice and early key events - Yuanyuan Li; Mengqi Dong; Yiming Xiong; Qing Chang; Xuanyue Chen; Xufeng Fu; Xinghong Li; Zhanfen Qin (Archives of Toxicology, 2022)

Three-dimensional modelling of stress relaxation of soft clay under complex loading conditions - Jian Li; Dong-Mei Zhang; Pierre-Yves Hicher; Chang-Fu Wei (European Journal of Environmental and Civil Engineering, 2022)

Transcriptome Analysis of Sophora davidii Leaves in Response to Low-Phosphorus Stress - Xin Zhao; Li-Juan Huang; Li-Li Zhao; Pu-Chang Wang; Xiao-Fu Sun (Journal of Plant Growth Regulation, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Hemecitones A and B: two phenanthrenes with cytotoxicity from Hemerocallis fulva (L.) L - Rao Fu; Xia Wang; Biao Zhao; Min Yang; Jing Gou; Chang-Ying Tian (Natural Product Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Effects of varying temperature on rhythmic expression of abiotic stress-responding genes in Tibetan hulless barley - Jing Cai; Tianliang Chang; Yi Zhao; Hongyan He; Jiaxing Li; Qianqian Xi; Jiayi Fu; Yuwei Zhao (Acta Physiologiae Plantarum, 2022)

Decomposition and decoupling research of Chinese power sector carbon emissions through the consumption accounting principle - Keliang Chang; Guijing Chen; Zifang Du; Fujun Hou; Jiaqi Li; Fu Chen (Environmental Science and Pollution Research, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

Research and application of a comprehensive forecasting system for tunnels in water-bearing fault fracture zones: a case study - Chang-fu Huang; Shuai-long Zhang; Shun-chuan Wu; Yong-tao Gao (Arabian Journal of Geosciences, 2022)

Two new species of Chalciporus (Boletaceae, Boletales) from tropical China - Chang Xu; Zhi-Qun Liang; Hui-Jing Xie; Shuai Jiang; Xin-Hua Fu; Nian-Kai Zeng (Mycological Progress, 2021)

Major influence of hydroxyl and nitrate radicals on air pollution by environmentally persistent free radicals - Wenxiao Pan; Jiamin Chang; Shuming He; Qiao Xue; Xian Liu; Jianjie Fu; Aiqian Zhang (Environmental Chemistry Letters, 2021)

Methacrylic functionalized hybrid carbon nanomaterial for the selective adsorption and detection of progesterone in wastewater - Xia Cui; Hua Shu; Lu Wang; Guoning Chen; Jili Han; Qianqian Hu; Kamran Bashir; Zhimin Luo; Chun Chang; Jia Zhang; Qiang Fu (Environmental Science and Pollution Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

A dissipative particle dynamics simulation of water/oil flow characteristics in nano-sized shale slits - Jiuzhu Wu; Wei Fu; Qun Yan; Yuanyuan Chen; Guangtao Chang; Huixian Zhang (Arabian Journal of Geosciences, 2021)

Suppression of multiple reflection–refraction waves in the shallow low-velocity zone via vertical source combination - Suoliang Chang; Zhen Qu; Sheng Zhang; Yanning Fu; Qiang Chen (Acta Geophysica, 2021)

Phylogeography of the wide‐host range panglobal plant pathogen Phytophthora cinnamomi - Shankar K. Shakya; Niklaus J. Grünwald; Valerie J. Fieland; Brian J. Knaus; Jerry E. Weiland; Cristiana Maia; André Drenth; David I. Guest; Edward C.Y. Liew; Colin Crane; Tun‐Tschu Chang; Chuen‐Hsu Fu; et al. (Molecular Ecology, 2021)
Various hypotheses have been proposed regarding the origin of the plant pathogen Phytophthora cinnamomi . P . cinnamomi is a devastating, highly invasive soilborne pathogen associated with epidemics of agricultural, horticultural and forest plantations and native ecosystems worldwide. We conducted a phylogeographic analysis of populations of this pathogen sampled in Asia, Australia, Europe, southern and northern Africa, South America, and North America. Based on genotyping‐by‐sequencing, we observed the highest genotypic diversity in Taiwan and Vietnam, followed by Australia and South Africa. Mating type ratios were in equal proportions in Asia as expected for a sexual population. Simulations based on the index of association suggest a partially sexual, semi‐clonal mode of reproduction for the Taiwanese and Vietnamese populations while populations outside of Asia are clonal. Ancestral area reconstruction provides new evidence supporting Taiwan as the ancestral area, given our sample, indicating that this region might be near or at the centre of origin for this pathogen as speculated previously. The Australian and South African populations appear to be a secondary centre of diversity following migration from Taiwan or Vietnam. Our work also identified two panglobal, clonal lineages PcG1‐A2 and PcG2‐A2 of A2 mating type found on all continents. Further surveys of natural forests across Southeast Asia are needed to definitively locate the actual centre of origin of this important plant pathogen.

Evaluation of Regional Surface Energy Budget Over Ocean Derived From Satellites - Seiji Kato; Fred G. Rose; Fu-Lung Chang; David Painemal; William L. Smith (Frontiers in Marine Science, 2021)
The energy balance equation of an atmospheric column indicates that two approaches are possible to compute regional net surface energy flux. The first approach is to use the sum of surface energy flux components F net,c and the second approach is to use net top-of-atmosphere (TOA) irradiance and horizontal energy transport by the atmosphere F net,t . When regional net energy flux is averaged over the global ocean, F net,c and F net,t are, respectively, 16 and 2 Wm –2 , both larger than the ocean heating rate derived from ocean temperature measurements. The difference is larger than the estimated uncertainty of F net,t of 11 Wm –2 . Larger regional differences between F net,c and F net,t exist over tropical ocean. The seasonal variability of energy flux components averaged between 45°N and 45°S ocean reveals that the surface provides net energy to the atmosphere from May to July. These two examples demonstrates that the energy balance can be used to assess the quality of energy flux data products.

The spatial variation of soil bacterial community assembly processes affects the accuracy of source tracking in ten major Chinese cities - Teng Yang; Yu Shi; Jun Zhu; Chang Zhao; Jianmei Wang; Zhiyong Liu; Xiao Fu; Xu Liu; Jiangwei Yan; Meiqing Yuan; Haiyan Chu (Science China Life Sciences, 2021)

A Survey on How Ocular Surface Demodex Infestation Interactively Associates with Diabetes Mellitus and Dry Eye Disease - Chang Huang; Shuze Chen; Sheng Fu; Yingli Li; Zhenhao Li; Siqi Li; Xiaoqian Liang; Zihong Wang; Zhoucheng Wang; Yifan Chen; Qixin Deng; Guoguo Yi; et al. (Acta Parasitologica, 2021)
Purpose Prevention of ocular surface (OS) Demodex infestation plays an important role in OS hygiene and variety of factors may be associated with it, in which diabetes mellitus (DM) or dry eye disease (DED) has caught the attention of most scholars. However, there has been no research on whether there was a potential interaction between DM and DED in the process of OS Demodex infestation. This cross-sectional study was implemented in Zhujiang Hospital of Southern Medical University. Methods Ophthalmologic interviews, questionnaires, and examinations were conducted. Factors including general information, DM status, dry eye condition, etc. were collected to study the correlation of DM and DED on OS Demodex infestation. Results After statistical analysis, we found that both DM ( P P = 0.013 R = 0.197, P R = 0.299, P P Conclusion This study provides a new evidence-based basis for clinical prevention and management of OS Demodex infestation.

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

The Integration of Carbon Price Between European and Chinese Markets: What are the Implications? - Yunpeng Wang; Qiang Fu; Chun-Ping Chang (International Journal of Environmental Research, 2021)

Response of growth characteristics and endogenous hormones of Sophora davidii to low-phosphorus stress - Xin Zhao; Li-Li Zhao; Li-Juan Huang; Xiao-Fu Sun; Pu-Chang Wang (Acta Physiologiae Plantarum, 2021)

Importation of taxadiene synthase into chloroplast improves taxadiene production in tobacco - Jinqiu Fu; Wenbo Xu; Wei Huang; Bipeng Wang; Shengchun Li; Jiang Zhang; Ling Chang (Planta, 2021)

Comparisons of Subjective and Objective Measures of Free-Living Daily Physical Activity and Sedentary Behavior in College Students - Ya-Wen Hsu; Chia-Chang Liu; Yen-Jung Chang; Yi-Ju Tsai; Wan-Chi Tsai; You Fu (Journal of Science in Sport and Exercise, 2021)

Enrichment and purification of red pigments from defective mulberry fruits using biotransformation in a liquid-liquid-solid three-phase system - Xue-Jiao Zhou; Chang-Tong Zhu; Lu-Yue Zhang; Shuai You; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2021)

Genetic diversity of porcine circovirus 3 strains and the first detection of two different PCV3 strains coinfecting the same host in Minas Gerais, Brazil - Viviane Sisdelli Assao; Marcus Rebouças Santos; Nívia Carolina Lopes Rosado; Gustavo Costa Bressan; Juliana Lopes Rangel Fietto; Yung-Fu Chang; Pedro Marcus Pereira Vidigal; Abelardo Silva-Júnior (Archives of Virology, 2021)

A dissipative particle dynamics study:influence of fluid-solid interaction force on micro-flow in shale slits - Jiuzhu Wu; Wei Fu; Qun Yan; Yuanyuan Chen; Yanjiao Hu; Zixuan Wang; Guangtao Chang; Huixian Zhang; Deqiang Wang (Arabian Journal of Geosciences, 2021)

Construction and characterization of an infectious cDNA clone of enterovirus 71: a rapid method for rescuing infectious virus based on stable cells expressing T7 polymerase - Meixian Fu; Jinjin Bai; Shuang Gao; Zhangmei Chang; Xin Zhou; Jian-Er Long (Archives of Virology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Planting models and mulching material strategies to reduce bundle sheath cell leakage and improve photosynthetic capacity and maize production in semi-arid climate - Lixin Fu; Honglei Ren; Shengjun Xu; Shaoxin Hu; Jianfei Yang; Chang Liu (Environmental Science and Pollution Research, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Effects of Cedrus atlantica extract on acute myeloid leukemia cell cycle distribution and apoptosis - Pei-Hsiu Hung; Ming-Chang Hsieh; Shan-Chih Lee; Xiao-Fan Huang; Kai-Fu Chang; Szu-Yin Chen; Ming-Shih Lee; Nu-Man Tsai (Molecular Biology Reports, 2020)

A Near Infrared Spectroscopy System for Assessing Rehabilitation on Peripheral Arterial Occlusion Patients - Shao-Hung Lu; Cheng-Lun Tsai; Tieh-Cheng Fu; Po-Hung Chang; Shao-Ming Lu (Journal of Medical and Biological Engineering, 2020)
Purpose A near-infrared spectroscopy system was developed to evaluate peripheral arterial occlusive disease (PAOD). The wireless device can take measurements when patients are doing rehabilitation exercise. Methods Two LED modules with wavelengths of 740 nm, 808 nm and 850 nm were placed over 32 mm away from the photodiode to detect the deep backscattering from muscle tissue. The absorbance difference from the extent of tissue oxygenation was extracted using a modified Beer’s law. Measurements taken on different muscle groups were applied to determine which branch of artery is occluded. Results The changes in oxygenation of gastrocnemius and tibialis anterior muscle were recorded when PAOD patients were riding a stationary bicycle. The drop in oxygenation with exercise generally should recover within 15 min of continuing exercise. Otherwise, the artery is not capable to provide enough blood supply to the exercising muscles. Since gastrocnemius is the primary muscle used in biking exercise, the compensatory vasodilation in gastrocnemius leads to hypoperfusion in tibialis anterior muscle. Conclusion This NIRS system is helpful for detecting the changes in tissue oxygenation during exercise. Muscle hypoxia was more obvious during exercise when the artery had some degree of occlusion.

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Three-dimensional ISAR image reconstruction technique based on radar network - Xiao-Wen Liu; Qun Zhang; Yu-Fu Yin; Yi-Chang Chen; Feng Zhu (International Journal of Remote Sensing, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Experimental Investigation on Vortex-Induced Vibration of a Flexible Pipe under Higher Mode in an Oscillatory Flow - Haojie Ren; Mengmeng Zhang; Jingyun Cheng; Peimin Cao; Yuwang Xu; Shixiao Fu; Chang Liu (Journal of Marine Science and Engineering, 2020)
Different from the previous studies of the vortex-induced vibration (VIV) dominated by first mode of flexible pipe in an oscillatory flow, the features of a higher mode dominated are experimentally investigated in the ocean basin. The flexible pipe is forced to harmonically oscillate with different combinations of a period and amplitude. The design dominant mode consists of first and second modes under the maximum reduced velocity (VR) of approximately 5.5 with a KC number ranging from 22 to 165. The VIV responses between only the excited first mode and the excited higher mode are compared and studied using displacement reconstruction and wavelet transform methods. The discrepancies of spatial and temporal response between smaller and larger KC numbers (KC = 56 and 121) are first observed. The strong alternate mode dominance and lock-in phenomena occur in the case of larger KC numbers, while they cannot be observed in the case of smaller KC numbers under higher modes. The VIV dominant frequency in the in-line (IL) direction is found to be always triple the oscillatory flow frequency and not twice that in the cross flow (CF) direction. The dominant frequency in the CF direction can be predicted by the Strouhal law, and the Strouhal number is approximately 0.18 under VR = 5.5, which is not affected by the excited mode. Moreover, differences of response motion trajectory are also revealed in this paper. The present work improves the basic understanding of vessel motion induced VIV and provides helpful references for developing prediction methods of VIV in an oscillatory flow.

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

An enhanced index for evaluating natural joint roughness considering multiple morphological factors affecting the shear behavior - Leibo Song; Quan Jiang; Li-fu Li; Chang Liu; Xiao-pei Liu; Jun Xiong (Bulletin of Engineering Geology and the Environment, 2020)

Taxonomy of the yeast genus Vanderwaltozyma and proposal of Vanderwaltozyma meishanica sp. nov., Vanderwaltozyma huisunica sp. nov., and Vanderwaltozyma molinica sp. nov. - Chin-Feng Chang; Yi-Ru Liu; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

Trajectory-Assisted Source Apportionment of Winter-Time Aerosol Using Semi-continuous Measurements - Ho-Tang Liao; Chang-Fu Wu (Archives of Environmental Contamination and Toxicology, 2020)

Antiproliferative effect of 2-Hydroxy-6-tridecylbenzoic acid from ginkgo biloba sarcotestas through the aryl hydrocarbon receptor pathway in triple-negative breast cancer cells - Dayu Zhou; Chunying Jiang; Chenghao Fu; Ping Chang; Bin Yang; Jiadi Wu; Xiaohui Zhao; Shiliang Ma (Natural Product Research, 2020)

Graphical Representation and Explanation of the Conductivity Tensor of Anisotropic Media - Chang-fu Yang; Lin-jiang Qin (Surveys in Geophysics, 2020)

ZmMYC2 exhibits diverse functions and enhances JA signaling in transgenic Arabidopsis - Jingye Fu; Lijun Liu; Qin Liu; Qinqin Shen; Chang Wang; Panpan Yang; Chenying Zhu; Qiang Wang (Plant Cell Reports, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Experimental Study on Water Absorption and Weakening of Silurian Argillite - Zhigang Li; Guangli Xu; Xin Zhao; Yongpeng Fu; Chang Su (Geotechnical and Geological Engineering, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

The Ribosomal Protein RPLP0 Mediates PLAAT4-induced Cell Cycle Arrest and Cell Apoptosis - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Ming-Cheng Lee; Yi-Ying Lin; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2019)

Biologically active oligostilbenes from the stems of Vatica mangachapoi and chemotaxonomic significance - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Survey of lead concentration in tap water on a university campus - Fu-Chun Chang; Yi-Pin Lin (Environmental Science and Pollution Research, 2019)

Late Cretaceous magmatism and porphyry Mo–Cu polymetallic mineralization in the Tongchanggou Intrusion, Geza Arc, Southwestern China - Xue-long Liu; Jian-hang Chen; Wen-chang Li; Na Zhang; Shuai-shuai Wang; Chang-zhen Zhang; Ying Luo; Zhen-huan Li; Fu-cheng Yang (Arabian Journal of Geosciences, 2019)

An Approach to Assess the Stability of Unsaturated Multilayered Coastal-Embankment Slope during Rainfall Infiltration - Jian-feng Zhu; Chang-fu Chen; Hong-yi Zhao (Journal of Marine Science and Engineering, 2019)
This study aims to develop a simple but effective approach to investigate the stability of an unsaturated and multilayered coastal-embankment slope during the rainfall, in which a Random Search Algorithm (RSA) based on the random sampling idea of the Monte Carlo method was employed to obtain the most dangerous circular sliding surface, whereas the safety factor of the unsaturated slope was calculated by the modified Morgenstern–Price method. Firstly, two typical distributions of matric suction were illustrated and the associated methods for determining the strength parameters of unsaturated soil were developed. Based on this, the Morgenstern–Price method was further modified to calculate the safety factor, and RSA was adopted to locate the most dangerous sliding surface of the unsaturated multilayered coastal-embankment slope. Finally, the slope breaking process under rainfall infiltration was simulated through continuously searching the critical slip surfaces under different groundwater levels by RSA. The results indicated that the stability of the unsaturated embankment slope was gradually deteriorated with the increase of rainfall infiltration. It was also found that both of the distributions of the matrix suction (ua-uw) and the suction angle (φb) had significant effects on the safety factor of the embankment slope. Basically, linear distribution of (ua-uw) along the depth and linear relationship between φb and (ua-uw) should be adopted in assessing the stability of the unsaturated multilayered coastal-embankment slope.

Cold-inducible MaC2H2s are associated with cold stress response of banana fruit via regulating MaICE1 - Yan-Chao Han; Chang-Chun Fu (Plant Cell Reports, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Reconsideration of Neo-Tethys evolution constrained from the nature of the Dazhuqu ophiolitic mantle, southern Tibet - Tong Liu; Fu-Yuan Wu; Chuan-Zhou Liu; Chang Zhang; Wen-Bin Ji; Yang Xu (Contributions to Mineralogy and Petrology, 2019)

Centrifugal model tests and numerical simulations for barrier dam break due to overtopping - Tian-long Zhao; Sheng-shui Chen; Chang-jing Fu; Qi-ming Zhong (Journal of Mountain Science, 2019)

Differential proteomic analysis reveals the mechanism of Musa paradisiaca responding to salt stress - Fu-Sang Ji; Lu Tang; Yuan-Yuan Li; Wen-Chang Wang; Zhen Yang; Xin-Guo Li; Chuansheng Zeng (Molecular Biology Reports, 2019)

Assessment of empirical equations of the compression index of muddy clay: sensitivity to geographic locality - Chang–fu Huang; Qun Li; Shun–chuan Wu; Yang Liu; Jian–yu Li (Arabian Journal of Geosciences, 2019)

Orientation Behavior and Regulatory Gene Expression Profiles in Migratory Agrotis ipsilon (Lepidoptera: Noctuidae) - Hong Chang; Jiang Long Guo; Xiao Wei Fu; You Ming Hou; Kong Ming Wu (Journal of Insect Behavior, 2019)

A pilot study of river design for slope stability and frog ecology - Yuan-Hsiou Chang; Tsai-Fu Chuang (Landscape and Ecological Engineering, 2019)

Cystobasidium keelungensis sp. nov., a novel mycosporine producing carotenogenic yeast isolated from the sea surface microlayer in Taiwan - Chin-Feng Chang; Ching-Fu Lee; Shiu-Mei Liu (Archives of Microbiology, 2019)

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

Nramp5 expression and functionality likely explain higher cadmium uptake in rice than in wheat and maize - Fu-Qing Sui; Jia-Dong Chang; Zhong Tang; Wen-Ju Liu; Xin-Yuan Huang; Fang-Jie Zhao (Plant and Soil, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Impacts of Climate Change and Varietal Replacement on Winter Wheat Phenology in the North China Plain - Zhan-biao Wang; Jing Chen; Wen-jie Tong; Chang-chun Xu; Fu Chen (International Journal of Plant Production, 2018)

Variably evolved gabbroic intrusions within the Xigaze ophiolite (Tibet): new insights into the origin of ophiolite diversity - Tong Liu; Fu-Yuan Wu; Chuan-Zhou Liu; Riccardo Tribuzio; Wen-Bin Ji; Chang Zhang; Yang Xu; Wei-Qi Zhang (Contributions to Mineralogy and Petrology, 2018)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Two thymol derivatives from the flower buds of Lonicera japonica and their antibacterial activity - Jing Yang; Yong-Chao Li; Xiu-Ren Zhou; Xin-Juan Xu; Qing-Yun Fu; Chang-Zhong Liu (Natural Product Research, 2018)

The impacts of environmental governance on political turnover of municipal party secretary in China - Gen-Fu Feng; Minyi Dong; Jun Wen; Chun-Ping Chang (Environmental Science and Pollution Research, 2018)

3-D DEM simulations of drained triaxial tests on inherently anisotropic granulates - Mingjing Jiang; An Zhang; Chang Fu (European Journal of Environmental and Civil Engineering, 2018)

Identification of Fusarium species associated with soybean root rot in Sichuan Province, China - Xiaoli Chang; Hao Dai; Duiping Wang; Huanhuan Zhou; Wanqin He; Yao Fu; Faisal Ibrahim; You Zhou; Guoshu Gong; Jing Shang; Jizhi Yang; Xiaoling Wu; et al. (European Journal of Plant Pathology, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Transdimensional Bayesian inversion of time-domain airborne EM data - Zong-Hui Gao; Chang-Chun Yin; Yan-Fu Qi; Bo Zhang; Xiu-Yan Ren; Yong-Chao Lu (Applied Geophysics, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Platelet transfusion refractoriness after T-cell-replete haploidentical transplantation is associated with inferior clinical outcomes - Qiang Fu; Lanping Xu; Xiaohui Zhang; Yu Wang; Yingjun Chang; Kaiyan Liu; Xiaojun Huang (Science China Life Sciences, 2018)

Development and validation of a loop-mediated isothermal amplification assay for the detection of Mycoplasma bovis in mastitic milk - Aqeela Ashraf; Muhammad Imran; Tahir Yaqub; Muhammad Tayyab; Wasim Shehzad; Claro N. Mingala; Yung-Fu Chang (Folia Microbiologica, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

Mutation of I176R in the E coding region weakens Japanese encephalitis virus neurovirulence, but not its growth rate in BHK-21 cells - Yuyong Zhou; Rui Wu; Qin Zhao; Yung-Fu Chang; Xintian Wen; Yao Feng; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Archives of Virology, 2018)

A new dihydrochalcone glycoside from the stems of Homalium stenophyllum - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2018)

Pullout Performances of Grouted Rockbolt Systems with Bond Defects - Chang Xu; Zihan Li; Shanyong Wang; Shuren Wang; Lei Fu; Chunan Tang (Rock Mechanics and Rock Engineering, 2018)

3D forward modeling and response analysis for marine CSEMs towed by two ships - Bo Zhang; Chang-Chun Yin; Yun-He Liu; Xiu-Yan Ren; Yan-Fu Qi; Jing Cai (Applied Geophysics, 2018)

Sealed tube promoted coupling of camptothecin and norcantharidin acid ester and their preliminary biological activity evaluation in vitro - Xian H. Wang; Fu H. Yang; Chang K. Zhao; Lei Gao; Chan Li (Medicinal Chemistry Research, 2018)

A new isoflavone from the roots of Ficus auriculata - Cui-Cui Qi; Yan-Hui Fu; Wen-Hao Chen; Guang-Ying Chen; Chun-Yan Dai; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Laboratory investigation and simulation of breakthrough curves in karst conduits with pools - Xiaoer Zhao; Yong Chang; Jichun Wu; Fu Peng (Hydrogeology Journal, 2017)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

The nitrate‐reduction gene cluster components exert lineage‐dependent contributions to optimization of Sinorhizobium symbiosis with soybeans - Li Xue Liu; Qin Qin Li; Yun Zeng Zhang; Yue Hu; Jian Jiao; Hui Juan Guo; Xing Xing Zhang; Biliang Zhang; Wen Xin Chen; Chang Fu Tian (Environmental Microbiology, 2017)
Summary Receiving nodulation and nitrogen fixation genes does not guarantee rhizobia an effective symbiosis with legumes. Here, variations in gene content were determined for three Sinorhizobium species showing contrasting symbiotic efficiency on soybeans. A nitrate‐reduction gene cluster absent in S. sojae was found to be essential for symbiotic adaptations of S. fredii and S . sp. III. In S. fredii , the deletion mutation of the nap (nitrate reductase), instead of nir (nitrite reductase) and nor (nitric oxide reductase), led to defects in nitrogen‐fixation (Fix – ). By contrast, none of these core nitrate‐reduction genes were required for the symbiosis of S . sp. III. However, within the same gene cluster, the deletion of hemN1 (encoding oxygen‐independent coproporphyrinogen III oxidase) in both S. fredii and S . sp. III led to the formation of nitrogen‐fixing (Fix + ) but ineffective (Eff – ) nodules. These Fix + /Eff – nodules were characterized by significantly lower enzyme activity of glutamine synthetase indicating rhizobial modulation of nitrogen‐assimilation by plants. A distant homologue of HemN1 from S. sojae can complement this defect in S. fredii and S . sp. III, but exhibited a more pleotropic role in symbiosis establishment. These findings highlighted the lineage‐dependent optimization of symbiotic functions in different rhizobial species associated with the same host.

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Influence of Thread Design on Dental Implant Osseointegration Assayed Using the Lan-Yu Mini-Pig Model - Shih-Kang Chien; Shui-Sang Hsue; Chih-Shing Lin; Tzong-Fu Kuo; Duen-Jeng Wang; Jen-Chang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Construction and characterization of Gal-chitosan graft methoxy poly (ethylene glycol) (Gal-CS-mPEG) nanoparticles as efficient gene carrier - Jiting Jin; Wandong Fu; Miaofei Liao; Baoqin Han; Jing Chang; Yan Yang (Journal of Ocean University of China, 2017)

Coamorphous Loratadine-Citric Acid System with Enhanced Physical Stability and Bioavailability - Jin Wang; Ruimiao Chang; Yanan Zhao; Jiye Zhang; Ting Zhang; Qiang Fu; Chun Chang; Aiguo Zeng (AAPS PharmSciTech, 2017)

A Novel Spatiotemporal Statistical Downscaling Method for Hourly Rainfall - Gwo-Fong Lin; Ming-Jui Chang; Chian-Fu Wang (Water Resources Management, 2017)

An analysis of patents for anesthetic laryngoscopes - Cheng-dong Ji; Xin Pan; Yuan-chang Xiong; Xuan Guo; Shu-wen Qian; Chang Xu; Qiang-qiang Fu; Zhi-ping Yang; Yu Ma; Yue-zhu Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Optimized decellularization protocol including α-Gal epitope reduction for fabrication of an acellular porcine annulus fibrosus scaffold - Lien-Chen Wu; Yi-Jie Kuo; Fu-Wen Sun; Chia-Hsien Chen; Chang-Jung Chiang; Pei-Wei Weng; Yang-Hwei Tsuang; Yi-You Huang (Cell and Tissue Banking, 2017)

Field testing of the surface electromagnetic prospecting system - Qing-Yun Di; Chang-Min Fu; Zhi-Guo An; Cheng Xu; Ya-Lu Wang; Zhong-Xing Wang (Applied Geophysics, 2017)

Lateral dynamic response of a partially embedded pile subjected to combined loads in saturated soil - An-Feng Hu; Peng Fu; Chang-Qing Xia; Kang-He Xie (Marine Georesources & Geotechnology, 2017)

Detection of exercise periodic breathing using thermal flowmeter in patients with heart failure - Tieh-Cheng Fu; Wen-Chen Lin; Jong-Shyan Wang; Chao-Hung Wang; Chun-Tien Chang; Cheng-Lun Tsai; Yun-Shien Lee; Kang-Ping Lin (Medical & Biological Engineering & Computing, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Preparation and Evaluation of Diosgenin Nanocrystals to Improve Oral Bioavailability - Cui-zhe Liu; Jin-hua Chang; Lin Zhang; He-fei Xue; Xi-gang Liu; Pei Liu; Qiang Fu (AAPS PharmSciTech, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

A dramatic blood plasticity in hibernating and 14-day hindlimb unloading Daurian ground squirrels (Spermophilus dauricus) - Huan-Xin Hu; Fang-Ying Du; Wei-Wei Fu; Shan-Feng Jiang; Jin Cao; Shen-Hui Xu; Hui-Ping Wang; Hui Chang; Nandu Goswami; Yun-Fang Gao (Journal of Comparative Physiology B, 2017)

Phylogeny and biogeography of the genus Cephalenchus (Tylenchomorpha, Nematoda) - Tiago J. Pereira; Xue Qing; Kuei‐Fu Chang; Manuel Mundo‐Ocampo; Juvenil E. Cares; Erik J. Ragsdale; Chau N. Nguyen; James G. Baldwin (Zoologica Scripta, 2017)
The phylogenetic position of Cephalenchus is enigmatic with respect to other tylench nematodes. In this study, Cephalenchus populations representing 11 nominal species were sampled worldwide for molecular and morphological characterization. Species identification was based on light microscopy ( LM ) and scanning electron microscopy ( SEM ). Molecular analyses were based on the genes (i.e. 18S, 28S, 5.8S) and internal transcribed spacers ( ITS ‐1 and ITS ‐2) of the ribosomal RNA ( rRNA ). Phylogenetic analyses (i.e. full and reduced alignments) of either concatenated or single genes always supported the monophyly of Cephalenchus . A sister relationship between Cephalenchus and Eutylenchus excretorius was recovered by most analyses, although branch support varies depending on the dataset used. The position of Cephalenchus + E. excretorius within Tylenchomorpha nevertheless remains ambiguous, thus highlighting the importance of sampling additional genes as well as taxa. Placement of Cephalenchus + E. excretorius as sister of Tylenchinae or Boleodorinae could not be rejected on the basis of 18S and 28S rRNA genes. Within Cephalenchus , amphidial opening morphology shows congruence with molecular‐based phylogenetic relationships, whereas the number of lines in the lateral field is likely to be a convergent trait. Morphometric analyses clearly distinguished short tail from medium–long tail species, and SEM observations seem to suggest a relation between tail length and amphidial opening. In addition, molecular phylogenies support the non‐monophyly of Cephalenchus cephalodiscus , Cephalenchus cylindricus , Cephalenchus daisuce and Cephalenchus leptus . The known extent of Cephalenchus diversity is increased with the inclusion of two new species, and the biogeography of the genus is discussed.

Pyrosequencing of rpoB uncovers a significant biogeographical pattern of rhizobial species in soybean rhizosphere - Xing Xing Zhang; Hui Juan Guo; Jian Jiao; Pan Zhang; Hui Yang Xiong; Wen Xin Chen; Chang Fu Tian (Journal of Biogeography, 2017)
Aim Most culture‐independent studies of bacterial biogeography have been at genus or higher taxonomic levels, although many important processes mediated by bacteria are at the strain or species level, such as the competitive nodulation of rhizobia on legumes. Here, at the intra‐species level, we characterized the structural variation in rhizobial populations in soybean rhizosphere under field conditions across 32 sampling sites in three eco‐regions. Location North‐east (Heilongjiang), north (Hebei–Shandong) and south (Jiangxi) China. Methods The intra‐species diversity of rhizobia in soybean rhizospheres was investigated by rpoB pyrosequencing. Soybean nodule isolates were characterized using repetitive extragenic palindromic PCR , restriction fragment length polymorphism of 16S‐23S intergenic sequences and rpoB PCR sequencing. Patterns and processes of biogeography of identified rhizobia were studied. Results Significant biogeographical patterns of rhizosphere rhizobia at the species level were found, and the abundant species in the rhizosphere were generally the dominant microsymbionts in soybean nodules. The distribution of rhizobial species in the rhizosphere across eco‐regions correlated with combined effects of spatial, vegetative, edaphic and climatic variables. Gene flow and genetic differentiation analyses revealed that there was no dispersal limitation among geographical populations of the same rhizobial species, and drift or subsequent diversification might be involved in shaping the biogeographical pattern in addition to environmental factors. Main conclusions These results constitute the first report of the existence of rhizobial biogeography in legume rhizospheres at the species level, contrasting with most studies, which focused on nodule isolates. The method developed in this study could be used to uncover, at high resolution, the diversity of local rhizobial populations in soils. This information is crucial for choosing suitable strains or species as inoculants for a specific legume host under local field conditions. Moreover, a similar strategy could be used to study other bacteria with important ecological functions.

Geochemistry and petrogenesis of Triassic mineralized porphyries in the Geza of the Sanjiang orogenic belt, southwestern China - Xue-long Liu; Wen-chang Li; Na Zhang; Fu-cheng Yang (International Geology Review, 2017)

Evaluation of Osseointegration in Titanium and Zirconia-Based Dental Implants with Surface Modification in a Miniature Pig Model - Tzong-Fu Kuo; Hung-Chieh Lu; Chien-Fang Tseng; Jen-Chang Yang; Sea-Fue Wang; Thomas Chung-Kuang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Role of the lipid-regulated NF-κB/IL-6/STAT3 axis in alpha-naphthyl isothiocyanate-induced liver injury - Zhong-Ze Fang; Naoki Tanaka; Dan Lu; Chang-Tao Jiang; Wei-Hua Zhang; Chunze Zhang; Zuo Du; Zhi-Wei Fu; Peng Gao; Yun-Feng Cao; Hong-Zhi Sun; Zhi-Tu Zhu; et al. (Archives of Toxicology, 2017)

Bound PAHs in Sediment and Related Environmental Significance - Jian-yang Guo; Jing-an Chen; Jing-fu Wang; Feng-chang Wu (Archives of Environmental Contamination and Toxicology, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Constitutive expression of a plant ferredoxin-like protein (pflp) enhances capacity of photosynthetic carbon assimilation in rice (Oryza sativa) - Hsiang Chang; Hsiang-En Huang; Chin-Fu Cheng; Mei-Hsuan Ho; Mang-Jye Ger (Transgenic Research, 2017)

Risk of parkinsonism induced by flunarizine or cinnarizine: a population-based study - Hsiu-Li Lin; Hsiu-Chen Lin; Yuan-Fu Tseng; Shih-Chang Chen; Chien-Yeh Hsu (European Journal of Clinical Pharmacology, 2017)

Di-2-ethylhexyl phthalate induced oxidative damage involving FasL-associated apoptotic pathway in mouse spermatogenic GC-2spd cells - Xiao Tang; Kun Tong; Lishan Zhu; Guoqing Fu; Wei Chang; Ting Zhou; Zhibing Zhang; Ling Tong; Ling Zhang; Yuqin Shi (Molecular & Cellular Toxicology, 2016)

Research on sequence stratigraphy, hydrogeological units and commingled drainage associated with coalbed methane production: a case study in Zhuzang syncline of Guizhou province, China - Xin Li; Xuehai Fu; Yanyan Ge; Xixi Chang (Hydrogeology Journal, 2016)

Papaya CpERF9 acts as a transcriptional repressor of cell-wall-modifying genes CpPME1/2 and CpPG5 involved in fruit ripening - Chang-Chun Fu; Yan-Chao Han; Xiu-Ye Qi; Wei Shan; Jian-Ye Chen; Wang-Jin Lu; Jian-Fei Kuang (Plant Cell Reports, 2016)

Redistribution of Cav2.1 channels and calcium ions in nerve terminals following end-to-side neurorrhaphy: ionic imaging analysis by TOF–SIMS - Chiung-Hui Liu; Hung-Ming Chang; To-Jung Tseng; Chyn-Tair Lan; Li-You Chen; Su-Chung Youn; Jian-Jr Lee; Fu-Der Mai; Jui-Feng Chou; Wen-Chieh Liao (Histochemistry and Cell Biology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Increased interhemispheric resting-state functional connectivity after sleep deprivation: a resting-state fMRI study - Yuanqiang Zhu; Zhiyan Feng; Junling Xu; Chang Fu; Jinbo Sun; Xuejuan Yang; Dapeng Shi; Wei Qin (Brain Imaging and Behavior, 2016)

GSK-3β promotes PA-induced apoptosis through changing β-arrestin 2 nucleus location in H9c2 cardiomyocytes - Fen Chang; Jing Liu; Hui Fu; Jinlan Wang; Fang Li; Hongwei Yue; Wenjing Li; Jing Zhao; Deling Yin (Apoptosis, 2016)

Genetic and antigenic characterization of fragments of the pheasant immunoglobulin Y heavy chain constant region - Zhenzhen Zhai; Xingliang Ma; Lingling Yang; Jinfeng Ti; Daozhen Song; Shijun Fu; Dapeng Li; Weishan Chang; Jing Zhai (Genes & Genomics, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Dispersion function of Rayleigh waves in porous layered half-space system - Shou-Guo Yan; Fu-Li Xie; Chang-Zheng Li; Bi-Xing Zhang (Applied Geophysics, 2016)

Sodium orthovanadate suppresses palmitate-induced cardiomyocyte apoptosis by regulation of the JAK2/STAT3 signaling pathway - Jing Liu; Hui Fu; Fen Chang; Jinlan Wang; Shangli Zhang; Yi Caudle; Jing Zhao; Deling Yin (Apoptosis, 2016)

Effects of area size, heterogeneity, isolation, and disturbances on urban park avifauna in a highly populated tropical city - Hsiang-Yi Chang; Ya-Fu Lee (Urban Ecosystems, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Construction and pilot screening of a signature-tagged mutant library of Sinorhizobium fredii - Dan Wang; Yuan Chun Wang; Li Juan Wu; Jian Xin Liu; Pan Zhang; Jian Jiao; Hui Yan; Tao Liu; Chang Fu Tian; Wen Xin Chen (Archives of Microbiology, 2016)

A reciprocating motion-driven rotation mechanism for the ATP synthase - Jiafeng Liu; Xinmiao Fu; Zengyi Chang (Science China Life Sciences, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Retraction Note to: Relationships of LDLR genetic polymorphisms with cerebral infarction: a meta-analysis - Hai-Cheng Yan; Wei Wang; Chang-Wu Dou; Fu-Ming Tian; Song-Tao Qi (Molecular Biology Reports, 2015)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Conformational Preferences of π–π Stacking Between Ligand and Protein, Analysis Derived from Crystal Structure Data Geometric Preference of π–π Interaction - Yuan Zhao; Jue Li; Hui Gu; Dongqing Wei; Yao-chang Xu; Wei Fu; Zhengtian Yu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Analysis of methylation-sensitive amplified polymorphism in different cotton accessions under salt stress based on capillary electrophoresis - Baohua Wang; Rong Fu; Mi Zhang; Zhenqian Ding; Lei Chang; Xinyu Zhu; Yafeng Wang; Baoxiang Fan; Wuwei Ye; Youlu Yuan (Genes & Genomics, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Direct interspecies electron transfer accelerates syntrophic oxidation of butyrate in paddy soil enrichments - Huijuan Li; Jiali Chang; Pengfei Liu; Li Fu; Dewen Ding; Yahai Lu (Environmental Microbiology, 2015)
Summary Syntrophic interaction occurs during anaerobic fermentation of organic substances forming methane as the final product. H 2 and formate are known to serve as the electron carriers in this process. Recently, it has been shown that direct interspecies electron transfer ( DIET ) occurs for syntrophic CH 4 production from ethanol and acetate. Here, we constructed paddy soil enrichments to determine the involvement of DIET in syntrophic butyrate oxidation and CH 4 production. The results showed that CH 4 production was significantly accelerated in the presence of nano Fe 3 O 4 in all continuous transfers. This acceleration increased with the increase of nano Fe 3 O 4 concentration but was dismissed when Fe 3 O 4 was coated with silica that insulated the mineral from electrical conduction. Nano Fe 3 O 4 particles were found closely attached to the cell surfaces of different morphology, thus bridging cell connections. Molecular approaches, including DNA ‐based stable isotope probing, revealed that the bacterial S yntrophomonadaceae and G eobacteraceae , and the archaeal M ethanosarcinaceae , M ethanocellales and M ethanobacteriales , were involved in the syntrophic butyrate oxidation and CH 4 production. Among them, the growth of G eobacteraceae strictly relied on the presence of nano Fe 3 O 4 and its electrical conductivity in particular. Other organisms, except M ethanobacteriales , were present in enrichments regardless of nano Fe 3 O 4 amendment. Collectively, our study demonstrated that the nano Fe 3 O 4 ‐facilitated DIET occurred in syntrophic CH 4 production from butyrate, and G eobacter species played the key role in this process in the paddy soil enrichments.

The assessment of high recharge areas using DO indicators and recharge potential analysis: a case study of Taiwan’s Pingtung plain - Jui-Pin Tsai; Yu-Wen Chen; Liang-Cheng Chang; Wen-Fu Chen; Chung-Jung Chiang; You-Cheng Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Occurrence of triclosan in the tropical rivers receiving the effluents from the hospital wastewater treatment plant - Gordon C. C. Yang; Hsin-Jen Tsai; Fu-Kuei Chang (Environmental Monitoring and Assessment, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Relationship between gene expression of UDP-glucose pyrophosphorylase and agar yield in Gracilariopsis lemaneiformis (Rhodophyta) - Lianpeng Chang; Zhenghong Sui; Feng Fu; Wei Zhou; Jinguo Wang; Kyoung Ho Kang; Shu Zhang; Jinhua Ma (Journal of Applied Phycology, 2014)

Establishment of a structural equation model for ground-level ozone: a case study at an urban roadside site - Kun-Ming Lin; Tai-Yi Yu; Len-Fu Chang (Environmental Monitoring and Assessment, 2014)

The effects of Typhoon Morakot on concentration of airborne particulates derived from unvegetated riverbanks - Kun-Ming Lin; Wang-Kun Chen; Tai-Yi Yu; Len-Fu Chang (Natural Hazards, 2014)

Serological report of pandemic and seasonal human influenza virus infection in dogs in southern China - Xin Yin; Fu-Rong Zhao; Dong-Hui Zhou; Ping Wei; Hui-Yun Chang (Archives of Virology, 2014)

Characterizing and locating air pollution sources in a complex industrial district using optical remote sensing technology and multivariate statistical modeling - Pao-Erh Paul Chang; Jen-Chih Rena Yang; Walter Den; Chang-Fu Wu (Environmental Science and Pollution Research, 2014)

Two new eunicellin-based diterpenoids from the South China Sea gorgonian Muricella sibogae Nutting - Yuan-Ming Zhou; Min Chen; Xiu-Mei Fu; Yu-Chun Fang; Chang-Yun Wang (Natural Product Research, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

RETRACTED ARTICLE: Relationships of LDLR genetic polymorphisms with cerebral infarction: a meta-analysis - Hai-Cheng Yan; Wei Wang; Chang-Wu Dou; Fu-Ming Tian; Song-Tao Qi (Molecular Biology Reports, 2014)

Nucleoside derivatives from the marine-derived fungus Aspergillus versicolor - Min Chen; Xiu-Mei Fu; Chui-Jian Kong; Chang-Yun Wang (Natural Product Research, 2014)

The promoter and the 5′-untranslated region of rice metallothionein OsMT2b gene are capable of directing high-level gene expression in germinated rice embryos - Chung-Shen Wu; Dai-Yin Chen; Chung-Fu Chang; Min-Jeng Li; Kuei-Yu Hung; Liang-Jwu Chen; Peng-Wen Chen (Plant Cell Reports, 2014)

Improvement of pseudo-static method for slope stability analysis - Chang-wei Yang; Jian-jing Zhang; Xiao Fu; Chuan-bin Zhu; Jun-wei Bi (Journal of Mountain Science, 2014)

GIS and SBF for estimating groundwater recharge of a mountainous basin in the Wu River watershed, Taiwan - HSIN-FU YEH; HUNG-I LIN; SHING-TSZ LEE; MIN-HSIANG CHANG; KUO-CHIN HSU; CHENG-HAW LEE (Journal of Earth System Science, 2014)

Re–Os isotope and platinum-group element geochemistry of the Pobei Ni–Cu sulfide-bearing mafic–ultramafic complex in the northeastern part of the Tarim Craton - Sheng-Hong Yang; Mei-Fu Zhou; Peter C. Lightfoot; Ji-Feng Xu; Christina Yan Wang; Chang-Yi Jiang; Wen-Jun Qu (Mineralium Deposita, 2014)

Naphtho[1,2-b]furan-4,5-dione inhibits MDA-MB-231 cell migration and invasion by suppressing Src-mediated signaling pathways - Pei-Chien Tsai; Chiao-Lun Chu; Yaw-Syan Fu; Chih-Hua Tseng; Yeh-long Chen; Long-Sen Chang; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2014)

UV-irradiation mutation of tetraspores of Gracilariopsis lemaneiformis and screening of thermotolerant strains - Feng Fu; Zheng-Hong Sui; Wei Zhou; Jin-Guo Wang; Lian-Peng Chang; Shu-Fang Ci (Journal of Applied Phycology, 2014)

40 Ar– 39 Ar age and geochemistry of subduction-related mafic dikes in northern Tibet, China: petrogenesis and tectonic implications - Bin Liu; Chang-Qian Ma; Jin-Yang Zhang; Fu-Hao Xiong; Jian Huang; Hong-An Jiang (International Geology Review, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

Assessment of landscape patterns affecting land surface temperature in different biophysical gradients in Shenzhen, China - Miaomiao Xie; Yanglin Wang; Qing Chang; Meichen Fu; Minting Ye (Urban Ecosystems, 2013)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Classified Separation of Flash Pyrolysis Oil - Xianwei Zheng; Yan Fu; Jie Chang; Shengyou Liang (BioEnergy Research, 2013)

Identifying and characterizing Yarrowia keelungensis sp. nov., an oil-degrading yeast isolated from the sea surface microlayer - Chin-Feng Chang; Chih-Chen Chen; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2013)

New 18-oxygenated polyhydroxy steroid from a South China Sea soft coral Sarcophyton sp. - Ling-Ling Sun; Xiu-Mei Fu; Xiu-Bao Li; Qian Xing; Chang-Yun Wang (Natural Product Research, 2013)

Changes to depositional palaeoenvironments within the Qikou depression (Bohaiwan Basin, China): carbon and oxygen isotopes in lacustrine carbonates of the Palaeogene Shahejie Formation - Yang Yang; Fu-Hong Gao; Xiu-Gang Pu; Chang-Wei Chen; Wen-Liang Xu (International Geology Review, 2013)

Petrogenetic and tectonic significance of Permian calc-alkaline lamprophyres, East Kunlun orogenic belt, Northern Qinghai-Tibet Plateau - Fu-Hao Xiong; Chang-Qian Ma; Hong-An Jiang; Bin Liu; Jin-Yang Zhang; Qin Zhou (International Geology Review, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

Identification of the proteins in green cotton fiber using a proteomics-based approach - Yan-Jun Li; Fu-Xin Wang; Ya-Qin Wang; Yong-Chang Liu; Xin-Yu Zhang; Yu-Qiang Sun; Jie Sun (Biotechnology Letters, 2013)

Research on the imaging of concrete defect based on the pulse compression technique - Chang-Zheng Li; Bi-Xing Zhang; Fang-Fang Shi; Fu-Li Xie (Applied Geophysics, 2013)

Effects of nitric oxide on the germination of cucumber seeds and antioxidant enzymes under salinity stress - Huai-Fu Fan; Chang-Xia Du; Ling Ding; Yan-Li Xu (Acta Physiologiae Plantarum, 2013)

Developmental expression and possible functional roles of mouse Nlrp4e in preimplantation embryos - Bo-hao Chang; Xu Liu; Jun Liu; Fu-sheng Quan; Ze-kun Guo; Yong Zhang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Console video games, postural activity, and motion sickness during passive restraint - Chih-Hui Chang; Wu-Wen Pan; Fu-Chen Chen; Thomas A. Stoffregen (Experimental Brain Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Altered Expression of Carbonic Anhydrase-Related Protein XI in Neuronal Cells Expressing Mutant Ataxin-3 - Mingli Hsieh; Wei-Hsiu Chang; Chi-Fu Hsu; Isao Nishimori; Cheng-Liang Kuo; Tomoko Minakuchi (The Cerebellum, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

A Novel Endogenous Induction of ColE7 Expression in a csrA Mutant of Escherichia coli - Hao-Wei Chang; Tsung-Yeh Yang; Guang-Sheng Lei; Kin-Fu Chak (Current Microbiology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Sequence analysis of infectious bronchitis virus isolates from the 1960s in the United States - Shankar Mondal; Yung-Fu Chang; Udeni Balasuriya (Archives of Virology, 2013)

Effect of dehydroepiandrosterone administration on recovery from mix-type exercise training-induced muscle damage - Yi-Hung Liao; Kun-Fu Liao; Chung-Lan Kao; Chung-Yu Chen; Chih-Yang Huang; Wei-Hsiang Chang; John L. Ivy; Jeffrey R. Bernard; Shin-Da Lee; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

An enormous Jurassic turtle bone bed from the Turpan Basin of Xinjiang, China - Oliver Wings; Márton Rabi; Jörg W. Schneider; Leonie Schwermann; Ge Sun; Chang-Fu Zhou; Walter G. Joyce (The Science of Nature, 2012)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

PTPN22 C1858T and the risk of psoriasis: a meta-analysis - Yu-Fu Chen; Jeffrey S. Chang (Molecular Biology Reports, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The UDP glucose: flavonoid-3-O-glucosyltransferase (UFGT) gene regulates anthocyanin biosynthesis in litchi (Litchi chinesis Sonn.) during fruit coloration - Zhi Chang Zhao; Gui Bing Hu; Fu Chu Hu; Hui Cong Wang; Zhuan Ying Yang; Biao Lai (Molecular Biology Reports, 2012)

Association between MTHFR C677T polymorphism and osteonecrosis of the femoral head: a meta-analysis - Xi-fu Shang; Hong Su; Wei-wei Chang; Chen-cheng Wang; Qin Han; Zhi-wei Xu (Molecular Biology Reports, 2012)

Human influence on the population decline and loss of genetic diversity in a small and isolated population of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) - Zong Fei Chang; Mao Fang Luo; Zhi Jin Liu; Jing Yuan Yang; Zuo Fu Xiang; Ming Li; Linda Vigilant (Genetica, 2012)

Effects of low environmental salinity on the cellular profiles and expression of Na+, K+-ATPase and Na+, K+, 2Cl− cotransporter 1 of branchial mitochondrion-rich cells in the juvenile marine fish Monodactylus argenteus - Chao-Kai Kang; Fu-Chen Liu; Wen-Been Chang; Tsung-Han Lee (Fish Physiology and Biochemistry, 2012)

Five novel species of the anamorphic genus Candida in the Cyberlindnera clade isolated from natural substrates in Taiwan - Chin-Feng Chang; Yi-Ru Liu; Shan-Fu Chen; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2012)

The multi-scale spatial variance of soil moisture in the semi-arid Loess Plateau of China - Xueling Yao; Bojie Fu; Yihe Lü; Ruiying Chang; Shuai Wang; Yafeng Wang; Changhong Su (Journal of Soils and Sediments, 2012)

Distinctive Mesorhizobium populations associated with Cicer arietinum L. in alkaline soils of Xinjiang, China - Jun Jie Zhang; Kai Lou; Xiang Jin; Pei Hong Mao; En Tao Wang; Chang Fu Tian; Xin Hua Sui; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2012)

The origin of mafic microgranular enclaves and their host granodiorites from East Kunlun, Northern Qinghai-Tibet Plateau: implications for magma mixing during subduction of Paleo-Tethyan lithosphere - Fu-Hao Xiong; Chang-Qian Ma; Jin-Yang Zhang; Bin Liu (Mineralogy and Petrology, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Identification of transcriptome profiles and signaling pathways for the allelochemical juglone in rice roots - Wen-Chang Chi; Shih-Feng Fu; Tsai-Lien Huang; Yun-An Chen; Chi-Cien Chen; Hao-Jen Huang (Plant Molecular Biology, 2011)

Soil Carbon Sequestration Potential for “Grain for Green” Project in Loess Plateau, China - Ruiying Chang; Bojie Fu; Guohua Liu; Shuguang Liu (Environmental Management, 2011)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

PKCα take part in CCR7/NF-κB autocrine signaling loop in CCR7-positive squamous cell carcinoma of head and neck - Zhao Zhen-jin; Li Peng; Liu Fa-yu; Sun Liyan; Sun Chang-fu (Molecular and Cellular Biochemistry, 2011)

Urban green space planning based on computational fluid dynamics model and landscape ecology principle: A case study of Liaoyang City, Northeast China - Yuan Zhou; Tiemao Shi; Yuanman Hu; Chang Gao; Miao Liu; Shilei Fu; Shizhe Wang (Chinese Geographical Science, 2011)

2010 oil spill: trajectory projections based on ensemble drifter analyses - Yu-Lin Chang; Leo Oey; Fang-Hua Xu; Hung-Fu Lu; Ayumi Fujisaki (Ocean Dynamics, 2011)

Crop nitrogen use and soil mineral nitrogen accumulation under different crop combinations and patterns of strip intercropping in northwest China - Chun-Jie Li; Yu-Ying Li; Chang-Bing Yu; Jian-Hao Sun; Peter Christie; Min An; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Analyzing coastal wetland change in the Yancheng National Nature Reserve, China - Chang-Qing Ke; Dong Zhang; Fu-Qiang Wang; Shu-Xing Chen; Christance Schmullius; Wolfgang-Martin Boerner; Hui Wang (Regional Environmental Change, 2011)

Important Role of Catalase in the Production of β-carotene by Recombinant Saccharomyces cerevisiae under H2O2 Stress - Guo-liang Yan; Heng-yu Liang; Zhi-qun Wang; Xiao-fan Yang; Dan Liu; Jin-fu Liu; Chang-qing Duan (Current Microbiology, 2011)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

Tetrahymena Gene Expression Database (TGED): A resource of microarray data and co-expression analyses for Tetrahymena - Jie Xiong; XingYi Lu; YuMing Lu; HongHui Zeng; DongXia Yuan; LiFang Feng; Yue Chang; Bowen Josephine; Martin Gorovsky; ChengJie Fu; Wei Miao (Science China Life Sciences, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Association of facial skin aging and vitamin D levels in middle-aged white women - Anne Lynn S. Chang; Teresa Fu; Omar Amir; Jean Y. Tang (Cancer Causes & Control, 2010)

The impact of naturalized legumes on plant communities in Northern Taiwan: are we worrying too much? - Jenn-Kuo Tsai; Hao-Ting Sun; Chiao-Fen Chen; Chang-Fu Hsieh; Shan-Huah Wu (Plant Ecology, 2010)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)

Recurrent Cerebellar Hemorrhage: Case Report and Review of the Literature - Yung-Tsan Wu; Ming-Fu Hsieh; Heng-Yi Chu; Shao-Chi Lu; Shin-Tsu Chang; Tsung-Ying Li (The Cerebellum, 2010)

Lowland rainforests in southern Taiwan and Lanyu, at the northern border of Paleotropics and under the influence of monsoon wind - Wei-Chun Chao; Guo-Zhang M. Song; Kuo-Jung Chao; Chi-Cheng Liao; Su-Wei Fan; Shan-Huah Wu; Tsung-Hsin Hsieh; I-Fang Sun; Yau-Lun Kuo; Chang-Fu Hsieh (Plant Ecology, 2010)

A spontaneous high expression of heat shock cognate 70 (HSC 70) in zebrafish Danio rerio larvae arising from tissue-specific translation of preexisting mRNA - Lung-Yin Hsu; Fu-Lung Yeh; Tun-Yuan Cheng; You-Hsin Chang; Shiu-Mei Liu; Todd Hsu (Fisheries Science, 2010)

Selection and characterization of a high-temperature tolerant strain of Porphyra haitanensis Chang et Zheng (Bangiales, Rhodophyta) - Xing-Hong Yan; Feng Lv; Chang-Jun Liu; Yue-Fu Zheng (Journal of Applied Phycology, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

NP-184[2-(5-methyl-2-furyl) benzimidazole], a novel orally active antithrombotic agent with dual antiplatelet and anticoagulant activities - Heng-Lan Kuo; Jin-Cherng Lien; Ching-Hu Chung; Chien-Hsin Chang; Shyh-Chyi Lo; I-Chun Tsai; Hui-Chin Peng; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

An improved nitrogen difference method for estimating biological nitrogen fixation in legume-based intercropping systems - Chang-Bing Yu; Yu-Ying Li; Chun-Jie Li; Jian-Hao Sun; X. H. He; Fu-Suo Zhang; Long Li (Biology and Fertility of Soils, 2010)

Sleeping Sites of Rhinopithecus brelichi at Yangaoping, Guizhou - Zuo-Fu Xiang; Shuai-Guo Nie; Zong-Fei Chang; Fu-Wen Wei; Ming Li (International Journal of Primatology, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Candida neustonensis sp. nov., a novel ascomycetous yeast isolated from the sea surface microlayer in Taiwan - Chin-Feng Chang; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2010)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Isolation and characterization of polymorphic microsatellite markers in the yellow catfish, Pelteobagrus fulvidraco - Guang-Fu Hu; Hong-Wei Liang; Zhong Li; Chang-Zhong Wang; Qin-Chao Wu; Xiang-Jiang Liu; Xiang-Zhong Luo; Gui-Wei Zou (Conservation Genetics Resources, 2009)

Disinfection by-product formation and mutagenic assay caused by preozonation of groundwater containing bromide - Winn-Jung Huang; Chia-Yu Chang; Fu-Hsiang Shih (Environmental Monitoring and Assessment, 2009)

Intercropping alleviates the inhibitory effect of N fertilization on nodulation and symbiotic N2 fixation of faba bean - Yu-Ying Li; Chang-Bin Yu; Xu Cheng; Chun-Jie Li; Jian-Hao Sun; Fu-Suo Zhang; Hans Lambers; Long Li (Plant and Soil, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Kazachstania wufongensis sp. nov., an ascosporogenous yeast isolated from soil in Taiwan - Ching-Fu Lee; Cheng-Hsu Yao; Yi-Ru Liu; Shuh-Sen Young; Ku-Shang Chang (Antonie van Leeuwenhoek, 2009)

Late Mesozoic magmatism from the Daye region, eastern China: U–Pb ages, petrogenesis, and geodynamic implications - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Chang-Qian Ma; Zorano Sérgio de Souza; Paulo Vasconcelos (Contributions to Mineralogy and Petrology, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

An overview of the Semi-arid Climate and Environment Research Observatory over the Loess Plateau - Jianping Huang; Wu Zhang; Jinqing Zuo; Jianrong Bi; Jinsen Shi; Xin Wang; Zhoulin Chang; Zhongwei Huang; Su Yang; Beidou Zhang; Guoyin Wang; Guanghong Feng; et al. (Advances in Atmospheric Sciences, 2008)

Establishment of a cDNA library from Bambusa edulis Murno in vitro-grown shoots - Nein-Tzu Liu; Fu-Hui Wu; Hsin-Sheng Tsay; Wei-Chin Chang; Choun-Sea Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Group Time Delay in the Reflection of P-Polarized Electromagnetic Plane Waves at a Stratigraphic Interface - Fu-Ping Liu; Rui-Zhong Li; Jin-yao Li; Hui-Guo Chen; Chang-Chun Yang (Mathematical Geosciences, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Differentiation of commercial strains of Agaricus species in China with inter-simple sequence repeat marker - Xue-Juan Guan; Lu Xu; Yan-Chun Shao; Zhuo-Ren Wang; Fu-Sheng Chen; Xin-Chang Luo (World Journal of Microbiology and Biotechnology, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Origin of the Tongshankou porphyry–skarn Cu–Mo deposit, eastern Yangtze craton, Eastern China: geochronological, geochemical, and Sr–Nd–Hf isotopic constraints - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Paulo Vasconcelos; Chang-Qian Ma; Xiao-Dong Deng; Zorano Sérgio de Souza; Yong-Xin Zhao; Gang Wu (Mineralium Deposita, 2008)

Molecular cloning and tissue distribution of three estrogen receptors from the cyprinid fish Varicorhinus barbatulus - Keng-Yen Fu; Chung-Yuan Chen; Chi-Tsai Lin; Whei-Meih Chang (Journal of Comparative Physiology B, 2008)

Iridovirus Bcl-2 protein inhibits apoptosis in the early stage of viral infection - Pei-Wen Lin; Yi-Jen Huang; Joseph Abraham Christopher John; Ya-Nan Chang; Chung-Hsiang Yuan; Wen-Ya Chen; Chiao-Hwa Yeh; San-Tai Shen; Fu-Pang Lin; Wen-Huei Tsui; Chi-Yao Chang (Apoptosis, 2008)

Antitumor Effect of Paclitaxel-Loaded PEGylated Immunoliposomes Against Human Breast Cancer Cells - Tao Yang; Min-Koo Choi; Fu-De Cui; Seung-Jin Lee; Suk-Jae Chung; Chang-Koo Shim; Dae-Duk Kim (Pharmaceutical Research, 2007)

Purification and characterization of a psychrophilic glutathione reductase from Antarctic ice microalgae Chlamydomonas sp. Strain ICE-L - Yu Ding; Jin-Lai Miao; Quan-Fu Wang; Zhou Zheng; Guang-You Li; Ji-Chang Jian; Zao-He Wu (Polar Biology, 2007)

Evaluation of dermal absorption and protective effectiveness of respirators for xylene in spray painters - Fu-Kuei Chang; Mei-Lien Chen; Shu-Fang Cheng; Tung-Sheng Shih; I-Fang Mao (International Archives of Occupational and Environmental Health, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Identification and expression analysis of hepcidin-like cDNAs from pigeon (Columba livia) - Yu Ming Fu; Su Ping Li; Yue Feng Wu; Yan Zhong Chang (Molecular and Cellular Biochemistry, 2007)

Designing environmental monitoring networks to measure extremes - Howard Chang; Audrey Qiuyan Fu; Nhu D. Le; James V. Zidek (Environmental and Ecological Statistics, 2007)

Genetic diversity of rhizobia associated with Vicia faba in three ecological regions of China - Chang Fu Tian; En Tao Wang; Tian Xu Han; Xin Hua Sui; Wen Xin Chen (Archives of Microbiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Characterization of symbiotic and endophytic bacteria isolated from root nodules of herbaceous legumes grown in Qinghai–Tibet plateau and in other zones of China - Feng Ling Kan; Zhong Yi Chen; En Tao Wang; Chang Fu Tian; Xin Hua Sui; Wen Xin Chen (Archives of Microbiology, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Protein kinase C-ζ regulation of GLUT4 translocation through actin remodeling in CHO cells - Xiao-Jun Liu; Chang Yang; Nishith Gupta; Jin Zuo; Yong-Sheng Chang; Fu-De Fang (Journal of Molecular Medicine, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Isolation of a human gallbladder cancer cell clone with high invasive phenotype in vitro and metastatic potential in orthotopic model and inhibition of its invasiveness by heparanase antisense oligodeoxynucleotides - Xin-Zhong Chang; Zhan-Min Wang; Jin-Ming Yu; Fu-Guo Tian; Wei Jin; Yi Zhang; Jie Yu; Lian-Fang Li; Xiao-Feng Liu; Zhi-Wei Li; Zhi-Min Shao (Clinical & Experimental Metastasis, 2007)

Mechanism and effect of channel evolution at estuary of Weihe River to Huanghe River - Jing-yi Li; Chang-wei Shi; Xi-bao Xu; Zhi-jun Fu (Chinese Geographical Science, 2006)

Phylogenetic and Biochemical Studies Reveal a Potential Evolutionary Origin of Small Heat Shock Proteins of Animals from Bacterial Class A - Xinmiao Fu; Wangwang Jiao; Zengyi Chang (Journal of Molecular Evolution, 2006)

Plant regeneration of Chorispora bungeana via somatic embryogenesis - Jianhui Wang; Lizhe An; Ruoyu Wang; Daqun Yang; Jing Si; Xuanying Fu; Jianfeng Chang; Shijian Xu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Paragonimus skrjabini Chen, 1959 (Digenea: Paragonimidae) and related species in eastern Asia: a combined molecular and morphological approach to identification and taxonomy - David Blair; Chang Zhengshan; Chen Minggang; Cui Aili; Wu Bo; Takeshi Agatsuma; Moritoshi Iwagami; David Corlis; Fu Chengbin; Zhan Ximei (Systematic Parasitology, 2005)

An efficient mannose selection protocol for tomato that has no adverse effect on the ploidy level of transgenic plants - Marina Sigareva; Rody Spivey; Michael G. Willits; Catherine M. Kramer; Yin-Fu Chang (Plant Cell Reports, 2004)

Concentration Profiles of Acidic and Basic Air Pollutants Around an Industrial Park of Taiwan - Chuen-Jinn Tsai; Shankar G. Aggarwal; Chung-Tso Chang; I-Fu Hung (Water, Air, & Soil Pollution, 2004)

The interfacial mass transfer resistances of the ozone dry deposition over the field soil of Taichung county in Taiwan - Hsin-Min Chang; Len-Fu W. Chang; Fu-Tien Jeng (Environmental Science and Pollution Research, 2002)

G561 site-directed deletion mutant chitinase from Aeromonas caviae is active without its 304 C-terminal amino acid residues - Fu-Pang Lin; Woan-Yuan Juang; Keng-Hao Chang; Hsing-Chen Chen (Archives of Microbiology, 2001)

Phosphomannose isomerase: An efficient selectable marker for plant transformation - Janet Reed; Laubra Privalle; M. Luann Powell; Moez Meghji; John Dawson; Erik Dunder; Janet Sutthe; Allan Wenck; Karen Launis; Catherine Kramer; Yin-Fu Chang; Genevieve Hansen; et al. (In Vitro Cellular & Developmental Biology - Plant, 2001)

Analysis of mitochondrial DNA of an endangered beech species, Fagus hayatae Palibin ex Hayata - Sumie Kato; Takayoshi Koike; Thomas T. Lei; Chang-Fu Hsieh; Kunihiko Ueda; Tetsuo Mikami (New Forests, 2000)

Allelopathic Potential of Acacia confusa and Related Species in Taiwan - Chang-Hung Chou; Chiu-Yu Fu; Shin-Yi Li; Yu-Fa Wang (Journal of Chemical Ecology, 1998)

Cloning, Expression and Sequence Analysis of the Classical Swine Fever Virus Nucleocapsid Protein - Jau-Jin Liu; Min-Liang Wong; Po-Fu Chen; Tien-Jye Chang (Virus Genes, 1998)

Relations of soil properties to topography and vegetation in a subtropical rain forest in southern Taiwan - Zueng-Sang Chen; Chang-Fu Hsieh; Feei-Yu Jiang; Tsung-Hsin Hsieh; I-Fang Sun (Plant Ecology, 1997)